(23)Na MRI reveals persistent sodium accumulation in tumefactive MS lesions - Huhn, Konstantin; Mennecke, Angelika; Linz, Peter; Tschunko, Franz; Kästle, Nicola; Nagel, Armin Michael; Uder, Michael; Dörfler, Arnd; Linker, Ralf; Engelhorn, Tobias (Journal of the Neurological Sciences, 2017)
Chronic inflammatory demyelinating diseases of the CNS typically show a limited lesion size. However, extended lesions may appear with an atypical configuration. Large lesions with a diameter>2cm accompanied by tumor-like edema are entitled "tumefactive" and may occur in multiple sclerosis (MS) and other demyelinating diseases. Historically, differential diagnosis often requires histological analysis. Therefore, advanced imaging techniques are warranted to allow for a precise non-invasive diagnosis. Cerebral sodium ((23)Na) MRI was recently described as a new method to investigate in vivo sodium accumulation. Indicating extended sodium levels in MS lesions, (23)Na MRI is a promising differential diagnostic tool further elucidating the role of sodium in demyelinating lesions.Repetitive (23)Na MRI measurements in a MS patient with a tumefactive demyelinating lesion providing insight into the medium-term course of cerebral sodium levels.(23)Na MRI depicts persistent lesional sodium accumulation after anti-inflammatory treatment and provides the opportunity of a non-invasive, in vivo analysis of sodium levels in inflammatory CNS lesions without need for contrast enhancing media. As a result of the extended dimension, tumefactive lesions may have an appropriate size for the analysis of inflammatory demyelination by (23)Na MRI with sufficient resolution.
EVALuna2:14686

3T-MRI in patients with pharmacoresistant epilepsy and a vagus nerve stimulator: a pilot study - Roesch, Julie; Hamer, Hajo; Mennecke, Angelika; Kasper, Burkhard; Engelhorn, Tobias; Dörfler, Arnd; Graf, Wolfgang (Epilepsy Research, 2015)
For safe 3T-MRI of patients with VNS (vagus nerve stimulator), specific conditions are mandatory. However, application of these conditions can lead to a loss of image quality. In this work, we evaluated the diagnostic value of 3T-MRI in VNS patients with pharmacoresistant epilepsy.Using a transmit-and-receive head coil and adapting our sequences to allow for low SAR (specific absorption rate), we examined 15 patients with pharmacoresistant epilepsy. Diagnostic quality was assessed by comparison of the SNR (signal to noise ratio) and CNR (contrast to noise ratio) of the hippocampus, the grey-white matter contrast and epileptogenic lesions to images of patients without VNS acquired with our routine 3T-MRI protocol and the 32-channel head coil.3T-MRI is feasible in VNS-patients. Image quality is adequate for detection and follow-up of epileptogenic lesions such as ganglioglioma or PNH (periventricular nodular heterotopia). Due to a significant reduction of SNR and CNR, the diagnostic value for subtle lesions may be decreased. Overall, the feasibility of 3T-MRI is beneficial in the diagnostic workup and follow-up of epilepsy-patients with VNS.
EVALuna2:22359

A Comparison of Single- and Multiparametric MRI Models for Differentiation of Recurrent Glioblastoma from Treatment-Related Change - Eisenhut, Felix; Engelhorn, Tobias; Arinrad, Soheil; Brandner, Sebastian; Coras, Roland; Putz, Florian; Fietkau, Rainer; Dörfler, Arnd; Schmidt, Manuel (Diagnostics, 2021)
To evaluate single- and multiparametric MRI models to differentiate recurrent glioblastoma (GBM) and treatment-related changes (TRC) in clinical routine imaging. Selective and unselective apparent diffusion coefficient (ADC) and minimum, mean, and maximum cerebral blood volume (CBV) measurements in the lesion were performed. Minimum, mean, and maximum ratios(CBV) (CBVlesion to CBVhealthy white matter) were computed. All data were tested for lesion discrimination. A multiparametric model was compiled via multiple logistic regression using data demonstrating significant difference between GBM and TRC and tested for its diagnostic strength in an independent patient cohort. A total of 34 patients (17 patients with recurrent GBM and 17 patients with TRC) were included. ADC measurements showed no significant difference between both entities. All CBV and ratios(CBV) measurements were significantly higher in patients with recurrent GBM than TRC. A minimum CBV of 8.5, mean CBV of 116.5, maximum CBV of 327 and ratio(CBV) (minimum) of 0.17, ratio(CBV) (mean) of 2.26 and ratio(CBV) (maximum) of 3.82 were computed as optimal cut-off values. By integrating these parameters in a multiparametric model and testing it in an independent patient cohort, 9 of 10 patients, i.e., 90%, were classified correctly. The multiparametric model further improves radiological discrimination of GBM from TRC in comparison to single-parameter approaches and enables reliable identification of recurrent tumors.
CRIS-Team WoS Importer:2022-01-07

Acute Stroke With Large Vessel Occlusion and Minor Clinical Deficits: Prognostic Factors and Therapeutic Implications - Volbers, Bastian; Gröger, Rebecca; Engelhorn, Tobias; Marsch, Armin; Macha, Kosmas; Schwab, Stefan; Dörfler, Arnd; Lang, Stefan; Kallmünzer, Bernd (Frontiers in Neurology, 2021)
Background and Purpose: The optimal acute management of patients with large vessel occlusion (LVO) and minor clinical deficits on admission [National Institutes of Health Stroke Scale (NIHSS) <= 4] remains to be elucidated. The aim of the present study was to investigate the prognostic factors and therapeutic management of those patients.
CRIS-Team WoS Importer:2021-11-19

A framework for voxel-based morphometric analysis of the optic radiation using diffusion tensor imaging in glaucoma - El-Rafei, Ahmed Mohamed Ibrahim; Engelhorn, Tobias; Wärntges, Simone; Dörfler, Arnd; Hornegger, Joachim; Michelson, Georg (Magnetic Resonance Imaging, 2011)
EVALuna2:21060

Age-dependent clinical outcomes in primary versus oral anticoagulation-related intracerebral hemorrhage - Sprügel, Maximilian; Kuramatsu, Joji; Gerner, Stefan T.; Sembill, Jochen; Madzar, Dominik; Reindl, Caroline; Bobinger, Tobias; Müller, Tamara; Hölter, Philip; Lücking, Hannes; Engelhorn, Tobias; Huttner, Hagen (International Journal of Stroke, 2019)
Aims This study determined the influence of age on bleeding characteristics and clinical outcomes in primary spontaneous (non-OAC), vitamin K antagonist-related (VKA-) and non-vitamin K antagonist oral anticoagulant-related (NOAC-) ICH. Methods Pooled individual patient data of multicenter cohort studies were analyzed by logistic regression modelling and propensity-score-matching (PSM) to explore the influence of advanced age on clinical outcomes among non-OAC-, VKA-, and NOAC-ICH. Primary outcome measure was functional outcome at three months assessed by the modified Rankin Scale, dichotomized into favorable (mRS = 0-3) and unfavorable (mRS = 4-6) functional outcome. Secondary outcome measures included mortality, hematoma characteristics, and frequency of invasive interventions. Results In VKA-ICH 33.5% (670/2001), in NOAC-ICH 44.2% (69/156) and in non-OAC-ICH 25.2% (254/1009) of the patients were >= 80 years. After adjustment for treatment interventions and relevant parameters, elderly ICH patients comprised worse functional outcome at three months (adjusted odds ratio (aOR) in VKA-ICH: 1.49 (1.21-1.84); p < 0.001; NOAC-ICH: 2.01 (0.95-4.26); p = 0.069; non-OAC-ICH: 3.54 (2.50-5.03); p < 0.001). Anticoagulation was significantly associated with worse functional outcome below the age of 70 years, (aOR: 2.38 (1.78-3.16); p < 0.001), but not in patients of >= 70 years (aOR: 1.21 (0.89-1.65); p = 0.217). The differences in initial ICH volume and extent of ICH enlargement between OAC-ICH and non-OAC-ICH gradually decreased with increasing patient age. Conclusions As compared to elderly ICH-patients, in patients <70 years OAC-ICH showed worse clinical outcomes compared to non-OAC-ICH because of larger baseline ICH-volumes and extent of hematoma enlargement. Treatment strategies aiming at neutralizing altered coagulation should be aware of these findings.
CRIS-Team WoS Importer:2020-01-28

Angiographic C-arm CT visualization of the Woven EndoBridge cerebral aneurysm embolization device (WEB): first experience in an animal aneurysm model - Struffert, Tobias; Lang, Sabine; Adamek, Edyta; Engelhorn, Tobias; Strother, C. M.; Dörfler, Arnd (Clinical Neuroradiology, 2014)
Improvements in the imaging capabilities of angiographic C-arm computed tomography (CT) using flat detector angiographic (FD-CT) systems now provide a means for the in vivo visualization of devices used for the treatment of intracranial aneurysms. One such device, the WEB embolization device, is made of a braided mesh of nitinol wires, the size of which are near to the limits of visualization using conventional x-ray fluoroscopy. Our hypothesis was that the imaging of these implants C-arm CT would provide useful information regarding their positioning and deployment.In five New Zealand white rabbits elastase induced aneurysms were created and subsequently treated using a WEB. Imaging was performed using digital subtraction angiography (DSA), X-ray imaging and two different Angiographic C-arm CT protocols. The images were evaluated by two neuroradiologists using an evaluation scale.The mesh of the WEB was barely visible on the DSA or x-ray fluoroscopy images. Volume rendering technique (VRT) reconstruction and multiplanar reconstruction (MPR) of images done using the C-arm CT protocols clearly delineated the shape and structure of the device. Contrast-enhanced MPR and VRT reconstructions allowed assessment of the status of blood flow in the aneurysms. Beam hardening artifacts caused by platinum markers on the WEB were present.In vivo C-arm CT imaging of the WEB is feasible and allows precise determination of the position and deployment status of the device. On contrast-enhanced images the occlusion status of aneurysms and the positioning of the WEB in relationship to the parent artery can be evaluated. C-arm-CT may serve as a minimal-invasive follow-up imaging modality.
EVALuna2:22996

Association of non-contrast CT markers with long-term functional outcome in deep intracerebral hemorrhage. - Kölbl, Kathrin; Hock, Stefan; Xu, Mingming; Sembill, Jochen; Mrochen, Anne; Balk, Stefanie; Lang, Stefan; Volbers, Bastian; Engelhorn, Tobias Martin; Kallmünzer, Bernd; Kuramatsu, Joji (Frontiers in Neurology, 2024)
OBJECTIVE: Hematoma expansion (HE) is the most important therapeutic target during acute care of patients with intracerebral hemorrhage (ICH). Imaging biomarkers such as non-contrast CT (NCCT) markers have been associated with increasing risk for HE. The aim of the present study was to evaluate the influence of NCCT markers with functional long-term outcome and with HE in patients with deep (basal ganglia and thalamus) ICH who represent an important subgroup of patients at the highest risk for functional deterioration with HE due to the eloquence of the affected brain region. METHODS: From our prospective institutional database, all patients maximally treated with deep ICH were included and retrospectively analyzed. NCCT markers were recorded at diagnostic imaging, ICH volume characteristics were volumetrically evaluated, and all patients received follow-up imaging within 0-48 h. We explored associations of NCCT makers with unfavorable functional outcome, defined as modified Rankin scale 4-6, after 12 months and with HE. Bias and confounding were addressed by multivariable regression modeling. RESULTS: In 322 patients with deep ICH, NCCT markers were distributed as follows: irregular shape: 69.6%, heterogenous density: 55.9%, hypodensities: 52.5%, island sign: 19.3%, black hole sign: 11.5%, and blend sign: 4.7%. Upon multivariable regression analyses, independent associations were documented with the functional outcome for irregular shape (aOR: 2.73, 95%CI: 1.42-5.22, p = 0.002), heterogenous density (aOR: 2.62, 95%CI: 1.40-4.90, p = 0.003) and island sign (aOR: 2.54, 95%CI: 1.05-6.14, p = 0.038), and with HE for heterogenous density (aOR: 5.01, 95%CI: 1.93-13.05, p = 0.001) and hypodensities (aOR: 3.75, 95%CI: 1.63-8.62, p = 0.002). CONCLUSION: NCCT markers are frequent in deep ICH patients and provide important clinical implications. Specifically, markers defined by diverging intra-hematomal densities provided associations with a 5-times higher risk for HE and a 2.5-times higher likelihood for unfavorable functional long-term outcome. Hence, these markers allow the identification of patients with deep ICH at high risk for clinical deterioration due to HE.
EVALuna2:552372

Automated Pupillometry Identifies Absence of Intracranial Pressure Elevation in Intracerebral Hemorrhage Patients - Giede-Jeppe, Antje; Sprügel, Maximilian; Huttner, Hagen; Borutta, Matthias; Kuramatsu, Joji; Hölter, Philip; Engelhorn, Tobias; Schwab, Stefan; Koehn, Julia (Neurocritical Care, 2020)
Introduction Although automated pupillometry is increasingly used in critical care settings, predictive value of automatically assessed pupillary parameters during different intracranial pressure (ICP) levels and possible clinical implications are unestablished. Methods This retrospective cohort study at the neurocritical care unit of the University of Erlangen-Nuremberg (2016-2018) included 23 nontraumatic supratentorial (intracerebral hemorrhage) ICH patients without signs of abnormal pupillary function by manual assessment, i.e., absent light reflex. We assessed ICP levels by an external ventricular drain simultaneously with parameters of pupillary reactivity [i.e., maximum and minimum apertures, light reflex latency (Lat), constriction and redilation velocities (CV, DV), and percentage change of apertures (per-change)] using a portable pupillometer (NeurOptics (R)). Computed tomography (CT) scans were analyzed to determine lesion location, size, intraventricular hemorrhage, hydrocephalus, midline shift, and compression or absence of the basal cisterns. We performed receiver operating characteristics analysis to investigate associations of ICP levels with pupillary parameters and to determine best cutoff values for prediction of ICP elevation. After dichotomization of assessments according to ICP values (normal: < 20 mmHg, elevated: >= 20 mmHg), prognostic performance of the determined cutoff parameters of pupillary function versus of CT-imaging findings was analyzed by calculating sensitivity, specificity, positive and negative predictive values (logistic regression, corresponding ORs with 95% CIs). Results In 23 patients (11 women, median age 59.0 (51.0-69.0) years), 1,934 assessments were available for analysis. A total of 74 ICP elevations >= 20 mmHg occurred in seven patients. Best discriminative thresholds for ICP elevation were: CV < 0.8 mm/s (AUC 0.740), per-change < 10% (AUC 0.743), DV < 0.2 mm/s (AUC 0.703), and Lat > 0.3 s (AUC 0.616). Positive predictive value of all four parameters to indicate ICP elevation ranged between 7.2 and 8.3% only and was similarly low for CT abnormalities (9.1%). We found high negative predictive values of pupillary parameters [CV: 99.2% (95% CI 98.3-99.6), per-change: 98.7% (95% CI 97.8-99.2), DV: 98.0% (95% CI 97.0-98.7), Lat: 97.0% (95% CI 96.0-97.7)], and CT abnormalities [99.7% (95% CI 99.2-99.9)], providing evidence that both techniques adequately identified ICH patients without ICP elevation. Conclusions Our data suggest an association between noninvasively detected changes in pupillary reactivity and ICP levels in sedated ICH patients. Although automated pupillometry and neuroimaging seem not sufficient to noninvasively indicate ICP elevation, both techniques, however, adequately identified ICH patients without ICP elevation. This finding may facilitate routine management by saving invasive ICP monitoring or repeated CT controls in patients with specific automated pupillometry readings.
CRIS-Team WoS Importer:2021-01-08

Automatic Segmentation of the Optic Radiation using DTI in Glaucoma Patients - El-Rafei, Ahmed Mohamed Ibrahim; Hornegger, Joachim; Engelhorn, Tobias; Dörfler, Arnd; Wärntges, Simone; Michelson, Georg (Computational Vision and Medical Image Processing - VipIMAGE 2009, 2009)

Automatic Segmentation of the Optic Radiation Using DTI in Healthy Subjects and Patients with Glaucoma - El-Rafei, Ahmed Mohamed Ibrahim; Engelhorn, Tobias; Wärntges, Simone; Dörfler, Arnd; Hornegger, Joachim; Michelson, Georg (Computational Vision and Medical Image Processing, 2011)

Brain MRI Lesions are Related to Bowel Incontinence in Multiple Sclerosis - Fröhlich, Katharina; Linker, Ralf; Engelhorn, Tobias; Dörfler, Arnd; Lee, De-Hyung; Huhn, Konstantin; Schwab, Stefan; Hilz, Max-Josef; Seifert, Frank; Winder, Klemens (Journal of Neuroimaging, 2018)
BACKGROUND AND PURPOSE: Bowel incontinence in multiple sclerosis might be associated with specific lesion sites. This study intended to determine associations between bowel incontinence and cerebral multiple sclerosis lesions using a voxel-wise lesion symptom mapping analysis. METHODS: We conducted a retrospective study of multiple sclerosis patients with self-reported bowel incontinence and matched controls. Lesions were manually outlined on T2-weighted MRI scans and transformed into stereotaxic space. We performed a voxel-wise subtraction analysis subtracting the lesion overlap of patients without from patients with bowel incontinence. Finally, we compared the absence or presence of bowel incontinence between patients with and without lesions in a given voxel using the Liebermeister test. RESULTS: A total of 51 patients were included in the study. The analysis yielded associations between bowel incontinence and lesions in the supramarginal gyrus of the left secondary somatosensory cortex and another lesion cluster in the right parahippocampal gyrus and amygdala. CONCLUSIONS: Our analysis indicates associations between bowel incontinence and lesions in the left supramarginal gyral area contributing to integrating anorectal-visceral sensation and in the right parahippocampal gyrus and amygdala contributing to generating visceral autonomic arousal states. Moreover, our results suggest left hemispheric dominance of sensory visceral integration, while limbic areas of the right hemisphere seem to contribute to the autonomic component of the defecation process. A limitation of our study is the retrospective evaluation of the bowel incontinence status based on medical records. Further research should evaluate the bowel incontinence status in multiple sclerosis patients prospectively to overcome the limitations of the current study.
EVALuna2:36318

Can flat-detector CT after successful endovascular treatment predict long-term outcome in patients with large vessel occlusion? An Alberta Stroke Programme Early CT Score–based study - Knott, Michael; Hölter, Philip; Hock, Stefan; Mühlen, Iris; Gerner, Stefan; Sprügel, Maximilian; Huttner, Hagen; Schwab, Stefan; Engelhorn, Tobias; Dörfler, Arnd (Neurological Sciences, 2022)
Purpose: Recent studies postulate a high prognostic value of the Alberta Stroke Programme Early CT Score (ASPECTS) applied on non-contrast whole-brain flat-detector CT (FDCT) after successful endovascular treatment (EVT). The aim of this study was the evaluation of long-term patient outcome after endovascular treatment using postinterventional FDCT. Methods: Using a local database (Stroke Research Consortium in Northern Bavaria, STAMINA), 517 patients with successful endovascular treatment (modified Thrombolysis in Cerebral Infarction (mTICI) ≥ 2B) due to acute ischaemic stroke (AIS) and large vessel occlusion (LVO) of the anterior circulation were recruited retrospectively. In all cases, non-contrast FDCT after EVT was analysed with special focus at ASPECTS. These results were correlated with the functional outcome in long-term (modified Rankin Scale (mRS) shift from pre-stroke to 90 days after discharge). Results: A significant difference in FDCT-ASPECTS compared to the subgroup of favourable vs. unfavourable outcome (Δ mRS) (median ASPECTS 10 (10–9) vs. median ASPECTS 9 (10–7); p = 0,001) could be demonstrated. Multivariable regression analysis revealed FDCT-ASPECTS (OR 0.234, 95% CI − 0.102–0.008, p = 0.022) along with the NHISS at admission (OR 0.169, 95% CI 0.003–0.018, p = 0.008) as independent factors for a favourable outcome. Cut-off point for a favourable outcome (Δ mRS) was identified at an ASPECTS ≥ 8 (sensitivity 90.6%, specificity 35%). Conclusion: For patients with LVO and successful EVT, FDCT-ASPECTS was found to be highly reliable in predicting long-term outcome.
CRIS-Team Scopus Importer:2022-12-02
Keywords: ASPECTS; Endovascular treatment; Flat-detector CT; Stroke

Cerebral Ischemia in Patients on Direct Oral Anticoagulants - Macha, Kosmas; Marsch, Armin; Siedler, Gabriela; Breuer, Lorenz; Strasser, Erwin; Engelhorn, Tobias; Schwab, Stefan; Kallmünzer, Bernd (Stroke, 2019)
Background and Purpose- In patients with ischemic stroke on therapy with vitamin K antagonists, stroke severity and clinical course are affected by the quality of anticoagulation at the time of stroke onset, but clinical data for patients using direct oral anticoagulants (DOACs) are limited. Methods- Data from our registry including all patients admitted with acute cerebral ischemia while taking oral anticoagulants for atrial fibrillation between November 2014 and October 2017 were investigated. The activity of vitamin K antagonists was assessed using the international normalized ratio on admission and categorized according to a threshold of 1.7. DOAC plasma levels were measured using the calibrated Xa-activity (apixaban, rivaroxaban, and edoxaban) or the Hemoclot-assay (dabigatran) and categorized into low (<50 ng/mL), intermediate (50-100 ng/mL), or high (>100 ng/mL). Primary objective was the association between anticoagulant activity and clinical and imaging characteristics. Results- Four hundred sixty patients were included (49% on vitamin K antagonists and 51% on DOAC). Patients on vitamin K antagonists with low international normalized ratio values had higher scores on the National Institutes of Health Stroke Scale and a higher risk of large vessel occlusion on admission. For patients on DOAC, plasma levels were available in 75.6% and found to be low in 49 (27.7%), intermediate in 41 (23.2%), and high in 87 patients (49.2%). Low plasma levels were associated with higher National Institutes of Health Stroke Scale scores on admission (low: 8 [interquartile range, 3-15] versus intermediate: 4 [1-11] versus high: 3 [0-8]; P<0.001) and higher risk of persisting neurological deficits or cerebral infarction on imaging (85.7% versus 75.6% versus 54.0%; P<0.001). Low DOAC plasma levels were an independent predictor of large vessel occlusion (odds ratio, 3.84 [95% CI, 1.80-8.20]; P=0.001). Conclusions- The activity of anticoagulation measured by specific DOAC plasma levels on admission is associated with stroke severity and presence of large vessel occlusion.
CRIS-Team Scopus Importer:2019-07-19
Keywords: anticoagulants; atrial fibrillation; direct oral anticoagulants; ischemic stroke; plasma level

Cerebral lesion correlates of sympathetic cardiovascular activation in multiple sclerosis - Winder, Klemens; Linker, Ralf A.; Seifert, Frank; Wang, Ruihao; Lee, De Hyung; Engelhorn, Tobias; Dörfler, Arnd; Fröhlich, Katharina; Hilz, Max-Josef (Human Brain Mapping, 2019)
Cardiovascular autonomic dysfunction is common in multiple sclerosis (MS) and contributes significantly to disability. We hypothesized that cerebral MS-lesions in specific areas of the central autonomic network might account for imbalance of the sympathetic and parasympathetic cardiovascular modulation. Therefore, we used voxel-based lesion symptom mapping (VLSM) to determine associations between cardiovascular autonomic dysfunction and cerebral MS-related lesion sites. In 74 MS-patients (mean age 37.0 ± 10.5 years), we recorded electrocardiographic RR-intervals and systolic and diastolic blood pressure. Using trigonometric regressive spectral analysis, we assessed low (0.04–0.15 Hz) and high (0.15–0.5 Hz) frequency RR-interval-and blood pressure-oscillations and determined parasympathetically mediated RR-interval–high-frequency modulation, mainly sympathetically mediated RR-interval–low-frequency modulation, sympathetically mediated blood pressure-low-frequency modulation, and the ratios of sympathetic and parasympathetic RR-interval-modulation as an index of sympathetic-parasympathetic balance. Cerebral MS-lesions were analyzed on imaging scans. We performed a VLSM-analysis correlating parameters of autonomic dysfunction with cerebral MS-lesion sites. The VLSM-analysis showed associations between increased RR-interval low-frequency/high-frequency ratios and lesions most prominently in the left insular, hippocampal, and right frontal inferior opercular region, and a smaller lesion cluster in the right middle cerebellar peduncle. Increased blood pressure-low-frequency powers were associated with lesions primarily in the right posterior parietal white matter and again left insular region. Our data indicate associations between a shift of cardiovascular sympathetic-parasympathetic balance toward increased sympathetic modulation and left insular and hippocampal lesions, areas of the central autonomic network. The VLSM-analysis further distinguished between right inferior fronto-opercular lesions disinhibiting cardiac sympathetic activation and right posterior parietal lesions increasing sympathetic blood pressure modulation.
CRIS-Team Scopus Importer:2019-08-23
Keywords: autonomic dysfunction; insular lesion; multiple sclerosis; visceral arousal; voxel-based lesion symptom mapping

Cerebral lipogranuloma: A penetrating traumatic brain injury - Hagen, Manuel; Coras, Roland; Engelhorn, Tobias; Schwab, Stefan; Seifert, Frank (Neurology, 2020)
CRIS-Team Scopus Importer:2020-12-11

Cerebral Microinfarcts in Primary Open-Angle Glaucoma Correlated With DTI-Derived Integrity of Optic Radiation - Schoemann, Johannes; Engelhorn, Tobias; Wärntges, Simone; Dörfler, Arnd; El-Rafei, Ahmed Mohamed Ibrahim; Michelson, Georg (Investigative Ophthalmology & Visual Science, 2014)
To evaluate the correlation between the extent of cerebral white matter lesions (WMLs) and the integrity of the visual pathway represented by fractional anisotropy (FA) in patients with primary open-angle glaucoma (POAG).This case-control study included a total of 61 German patients (39 POAG patients, 22 controls) matched for age and sex. Fractional anisotropy of the optic radiation was determined by 3-Tesla diffusion tensor imaging. White matter lesions and brain volumes were manually measured by using a T2-weighted, 3-D fluid-attenuated inversion recovery sequence.In POAG patients WML volumes were significantly (P = 0.04) increased in the subcortical area. This applied for both absolute and relative units to the specific patient's brain volume, compared to controls. The WML volumes were significantly (P = 0.003) greater in middle-aged (40-59 years) POAG patients than control patients. In controls there was a significant age correlation of WML volumes in the total brain, subcortical, and optic radiation regions of interest. There was a significant correlation between FA and WML in POAG regarding the total brain, the periventricular region, and the optic radiation in both hemispheres. In POAG, FA left and right optic radiation correlated significantly with age (P = 0.002).We were able to demonstrate that (1) POAG patients aged 40 to 60 years had higher volumes of cerebral microinfarcts and (2) POAG patients showed a significant correlation between cerebral microinfarcts and degeneration of the optic radiation. This indicates that cerebral microinfarcts might be an intracerebral risk factor for glaucomatous optic nerve atrophy.
EVALuna2:21212

CEREBROSPINAL FLUID BIOMARKERS FOR CEREBRAL AMYLOID ANGIOPATHY - Sembill, Jochen; Lusse, C.; Linnerbauer, Mathias; Sprügel, Maximilian; Mrochen, Anne; Knott, Michael; Hölter, Philip; Engelhorn, Tobias; Schmidt, M.; Dörfler, Arnd; Oberstein, Timo; Maler, Juan Manuel; et al. (INTERNATIONAL JOURNAL OF STROKE, 2022)
CRIS-Team WoS Importer:2022-11-18

Cerebrospinal fluid biomarkers for cerebral amyloid angiopathy - Sembill, Jochen; Lusse, Christoph; Linnerbauer, Mathias; Sprügel, Maximilian; Mrochen, Anne; Knott, Michael; Engelhorn, Tobias; Schmidt, Manuel; Dörfler, Arnd; Oberstein, Timo; Maler, Juan Manuel; Kornhuber, Johannes; et al. (Brain Communications, 2023)
Integrating cerebrospinal fluid-biomarkers into diagnostic workup of patients with sporadic cerebral amyloid angiopathy may support early and correct identification. We aimed to identify and validate clinical- and cerebrospinal fluid-biomarkers for in vivo diagnosis of cerebral amyloid angiopathy. This observational cohort study screened 2795 consecutive patients admitted for cognitive complaints to the academic departments of neurology and psychiatry over a 10-year period (2009–2018). We included 372 patients with available hemosiderin-sensitive MR imaging and cerebrospinal fluid-based neurochemical dementia diagnostics, i.e. Aβ40, Aβ42, t-tau, p-tau. We investigated the association of clinical- and cerebrospinal fluid-biomarkers with the MRI-based diagnosis of cerebral amyloid angiopathy, applying confounder-adjusted modelling, receiver operating characteristic and unsupervised cluster analyses. We identified 67 patients with cerebral amyloid angiopathy, 76 patients with Alzheimer’s disease, 75 patients with mild cognitive impairment due to Alzheimer’s disease, 76 patients with mild cognitive impairment with unlikely Alzheimer’s disease and 78 healthy controls. Patients with cerebral amyloid angiopathy showed a specific cerebrospinal fluid pattern: average concentration of Aß40 [13 792 pg/ml (10 081–18 063)] was decreased compared to all controls (P < 0.05); Aß42 [634 pg/ml (492–834)] was comparable to Alzheimer’s disease and mild cognitive impairment due to Alzheimer’s disease (P = 0.10, P = 0.93) but decreased compared to mild cognitive impairment and healthy controls (both P < 0.001); p-tau [67.3 pg/ml (42.9–91.9)] and t-tau [468 pg/ml (275–698)] were decreased compared to Alzheimer’s disease (P < 0.001, P = 0.001) and mild cognitive impairment due to Alzheimer’s disease (P = 0.001, P = 0.07), but elevated compared to mild cognitive impairment and healthy controls (both P < 0.001). Multivariate modelling validated independent clinical association of cerebral amyloid angiopathy with older age [odds-ratio: 1.06, 95% confidence interval (1.02–1.10), P < 0.01], prior lobar intracerebral haemorrhage [14.00 (2.64–74.19), P < 0.01], prior ischaemic stroke [3.36 (1.58–7.11), P < 0.01], transient focal neurologic episodes (TFNEs) [4.19 (1.06–16.64), P = 0.04] and gait disturbance [2.82 (1.11–7.15), P = 0.03]. For cerebrospinal fluid-biomarkers per 1 pg/ml, both lower Aß40 [0.9999 (0.9998–1.0000), P < 0.01] and lower Aß42 levels [0.9989 (0.9980–0.9998), P = 0.01] provided an independent association with cerebral amyloid angiopathy controlled for all aforementioned clinical confounders. Both amyloid biomarkers showed good discrimination for diagnosis of cerebral amyloid angiopathy among adjusted receiver operating characteristic analyses (area under the receiver operating characteristic curves, Aß40: 0.80 (0.73–0.86), P < 0.001; Aß42: 0.81 (0.75–0.88), P < 0.001). Unsupervised Euclidian clustering of all cerebrospinal fluid-biomarker-profiles resulted in distinct segregation of cerebral amyloid angiopathy patients from all controls. Together, we demonstrate that a distinctive set of cerebrospinal fluid-biomarkers effectively differentiate cerebral amyloid angiopathy patients from patients with Alzheimer’s disease, mild cognitive impairment with or without underlying Alzheimer’s disease, and healthy controls. Integrating our findings into a multiparametric approach may facilitate diagnosing cerebral amyloid angiopathy, and may aid clinical decision-making, but warrants future prospective validation.
CRIS-Team Scopus Importer:2023-07-21
Keywords: biomarker; cerebral amyloid angiopathy; cerebrospinal fluid; dementia; small vessel disease

Characteristics in Non-Vitamin K Antagonist Oral Anticoagulant-Related Intracerebral Hemorrhage - Gerner, Stefan; Kuramatsu, Joji; Sembill, Jochen; Sprügel, Maximilian; Hagen, Manuel; Knappe, Ruben U.; Endres, Matthias; Haeusler, Karl Georg; Sobesky, Jan; Schurig, Johannes; Zweynert, Sarah; Bauer, Miriam; et al. (Stroke, 2019)
Background and Purpose Given inconclusive studies, it is debated whether clinical and imaging characteristics, as well as functional outcome, differ among patients with intracerebral hemorrhage (ICH) related to vitamin K antagonists (VKA) versus non-vitamin K antagonist (NOAC)-related ICH. Notably, clinical characteristics according to different NOAC agents and dosages are not established.
CRIS-Team WoS Importer:2019-06-18

Clinical and radiological outcome after mechanical thrombectomy in acute ischemic stroke: What matters? - Kaschka, Iris; Kloska, Stephan; Struffert, Tobias; Engelhorn, Tobias; Gölitz, Philipp; Kurka, Natalia; Köhrmann, Martin; Schwab, Stefan; Dörfler, Arnd (Neuroradiology Journal, 2016)
Recent studies have shown the efficacy of mechanical thrombectomy in acute ischemic stroke. We sought to identify prognostic parameters for clinical and radiological outcome after mechanical thrombectomy.In 34 patients (age 72 ± 13 years, 64.7% women) with acute occlusion of the distal ICA and/or M1 segment who were treated with mechanical thrombectomy, the Spearman correlation was performed to assess potential prognostic outcome parameters (age, NIHSS, ASPECT, thrombus length (TL), clot burden score (CBS), relative filling time delay (rFTD), time to recanalization (TTR) and TICI score). The modified Rankin scale (mRS) and the Alberta Stroke Program Early CT (ASPECT) score were used for clinical and radiological outcome, respectively. Receiver operating characteristic (ROC) analysis was performed to assess parameters predicting favorable clinical (?mRS <= 2) and radiological outcome (?ASPECT <= 2).Variables associated with favorable clinical outcome included NIHSS, TL, TTR and TICI score (p <= 0.01) with NIHSS <= 15 (p = 0.001, area under the curve (AUC) 0.87), TL <= 2 cm (p = 0.017, AUC 0.75), TTR <= 231 min (p = 0.001 AUC 0.88) and TICI >= 2b (p = 0.050, AUC 0.70). Shorter TTR and higher TICI scores were associated with favorable radiological outcome (p < 0.001) with TTR <= 224 min (p = 0.023, AUC 0.77) and TICI >= 2b (p = 0.000, AUC 0.86).Fast and complete recanalization is essential to achieve a favorable radiological and functional outcome after mechanical thrombectomy in acute ischemic stroke. Age, CBS and collateral supply play a subordinate role.
EVALuna2:22544

Clot Burden and Collaterals in Anterior Circulation Stroke: Differences Between Single-Phase CTA and Multi-phase 4D-CTA - Kaschka, Iris; Kloska, Stephan; Struffert, Tobias; Engelhorn, Tobias; Gölitz, Philipp; Kurka, Natalia; Köhrmann, Martin; Schwab, Siegfried; Dörfler, Arnd (Clinical Neuroradiology, 2014)
It has been reported that the extent of intravascular thrombi and the quality of collateral filling in computed tomography (CT) angiography are predictive for the clinical outcome in patients with acute stroke. We hypothesized that multi-phase four-dimensional CTA (4D-CTA) allows better assessment of clot burden and collateral flow compared with arterial single-phase CTA (CTA).In 49 patients (33 female; age: 77 ± 12 years) with acute anterior circulation stroke, CTA and 4D-CTA reconstructed from dynamic perfusion CT data were analyzed for absolute thrombus length (TL), clot burden score (CBS), and collateral score (CS). The length of the filling defect was also defined on thin-slice nonenhanced CT as corresponding hyperdense middle cerebral artery sign (HMCAS) when present.There was good correlation (r = 0.62, p < 0.01) between the length of HMCAS (1.29 ± 0.62 cm) and TL in 4D-CTA (1.22 ± 0.51 cm). 4D-CTA and CTA significantly varied (p < 0.01) in TL (1.42 ± 0.73 cm (CTA) versus 1.11 ± 0.62 cm (4D-CTA)), CBS (median: 5, interquartile range: 4-7 (CTA) versus median: 6, interquartile range: 5-8 (4D-CTA); p < 0.001), and CS (median: 2, interquartile range: 1-2 (CTA) versus median: 3, interquartile range: 2-3 (4D-CTA); p < 0.001). Accordingly, CTA significantly overrated clot burden and underestimated collateral flow.4D-CTA more closely defines clot burden and collateral supply in anterior circulation stroke than CTA, implicating an additional diagnostic benefit.
EVALuna2:22276

Cluster Analysis of Glaucoma Patients Using the Retinal Nerve Fiber Layer Thickness of the Optic Nerve and DTI Parameters of the Optic Radiation - Michelson, Georg; Wärntges, Simone; Engelhorn, Tobias; El-Rafei, Ahmed Mohamed Ibrahim; Hornegger, Joachim; Dörfler, Arnd (Clinical and Experimental Ophthalmology, 2011)

Comparison of ped and fred flow diverters for posterior circulation aneurysms: a propensity score matched cohort study - Griessenauer, Christoph J.; Enriquez-Marulanda, Alejandro; Xiang, Sissi; Hong, Tao; Zhang, Hongqi; Taussky, Philipp; Grandhi, Ramesh; Waqas, Muhammad; Tutino, Vincent M.; Siddiqui, Adnan H.; Levy, Elad I.; Ogilvy, Christopher S.; et al. (Journal of Neurointerventional Surgery, 2020)
Background: Flow diversion is a common endovascular treatment for cerebral aneurysms, but studies comparing different types of flow diverters are scarce. Objective: To perform a propensity score matched cohort study comparing the Pipeline Embolization Device (PED) and Flow Redirection Intraluminal Device (FRED) for posterior circulation aneurysms. Methods: Consecutive aneurysms of the posterior circulation treated at 25 neurovascular centers with either PED or FRED were collected. Propensity score matching was used to control for age, duration of follow-up imaging, adjunctive coiling, and aneurysm location, size, and morphology; previously ruptured aneurysms were excluded. The two devices were compared for the following outcomes: procedural complications, aneurysm occlusion, and functional outcome. Results: A total of 375 aneurysms of the posterior circulation were treated in 369 patients. The PED was used in 285 (77.2%) and FRED in 84 (22.8%) procedures. Aneurysms treated with the PED were more commonly fusiform and larger than those treated with FRED. To account for these important differences, propensity score matching was performed resulting in 33 PED and FRED unruptured aneurysm pairs. No differences were found in occlusion status and neurologic thromboembolic or hemorrhagic complications between the two devices. The proportion of patients with favorable functional outcome was higher with FRED (100% vs 87.9%, p=0.04). Conclusion: Comparative analysis of PED and FRED for the treatment of unruptured posterior circulation aneurysms did not identify significant differences in aneurysm occlusion or neurologic complications. Variations in functional outcomes warrant additional investigations.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Aneurysm; Embolic; Flow diverter; Intervention; Posterior fossa

Comparison of Pipeline Embolization Device and Flow Re-Direction Endoluminal Device Flow Diverters for Internal Carotid Artery Aneurysms: A Propensity Score-Matched Cohort Study - Griessenauer, Christoph J.; Thomas, Ajith J.; Enriquez-Marulanda, Alejandro; Deshmukh, Aviraj; Jain, Abhi; Ogilvy, Christopher S.; Kocer, Naci; Engelhorn, Tobias; Möhlenbruch, Markus; Holtmannspötter, Markus; Janssen, Hendrik; Finkenzeller, Thomas; et al. (Neurosurgery, 2019)
BACKGROUND: Flow diversion has become an accepted endovascular treatment modality for intracranial aneurysms. Studies comparing different types of flow diverters are currently lacking. OBJECTIVE: To perform a propensity score-matched cohort study comparing the Pipeline Embolization Device (PED; Medtronic, Dublin, Ireland) and Flow Redirection Endoluminal Device (FRED; MicroVention, Aliso Viejo, California). METHODS: Aneurysms of the internal carotid artery proximal to the communicating segment treated with PED at 2 neurovascular centers in the United States were matched with aneurysms treated in the European FRED study using propensity scoring. Aneurysms treated in the setting of subarachnoid hemorrhage were excluded from matching. Occlusion rates and complications were evaluated. RESULTS: Two hundred twenty-one internal carotid artery aneurysms were treated with PED and 282 with FRED. Propensity score matching controlling for age, sex, aneurysm size, location, number of flow diverters, and adjunctive coiling resulted in 55 matched pairs. Median angiographic follow-up was nonsignificantly longer for FRED compared to PED (12.2 vs 7.5 mo, P = .28). The rate of complete occlusion did not differ between flow diverters (80% vs 80%, P > .99). Functional outcome and complications were comparable for PED and FRED. CONCLUSION: Propensity score-matched analysis of PED and FRED for internal carotid artery aneurysms revealed comparable angiographic complete occlusion and complication rates. Whether FRED has an advantage in terms of near complete aneurysm occlusion warrants further investigation. Limitations include the retrospective design and lack of an independent assessment of radiographic outcome in a core-laboratory and functional outcomes, among others, and the results should be interpreted as such.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Aneurysm; Embolization; Flow diversion; Stent

Consecutive Lacunar Strokes Mimicking Brainstem Symptoms in a Patient With Pseudobulbar Palsy - Stocker, Alexander; Struffert, Tobias; Engelhorn, Tobias; Huttner, Hagen (Neurologist, 2015)
The pseudobulbar palsy affects both corticobulbar tracts leading to symptoms of the caudal brain nerves. These bulbar symptoms often may be misinterpreted and lead to a false localization of the ischemic lesion. Here we report on a patient with an acute small lacunar ischemic lesion who presented clinically with severe affection because of an identical old contralateral lesion.The patient presented with sudden onset of dysphagia, anarthria, and glossplegia. The clinical examination was suspicious of a brainstem lesion, however, stroke magnetic resonance imaging revealed a small ischemic lacuna within the right internal capsule. However, because of an old ischemic lesion within the left internal capsule, both corticobulbar tracts were involved and this pseudobulbar palsy was mimicking bulbar brainstem symptoms.Patients who suffer from a pseudobulbar palsy usually have–compared with the rather small lesions within the central nervous system–clinically dramatic presentations and due to bulbar symptoms severe medical secondary complications and social-economic consequences to deal with.
EVALuna2:22360

Correlation between clinical severity and extent of autonomic cardiovascular impairment in the acute phase of subarachnoid hemorrhage - Borutta, Matthias; Gerner, Stefan T.; Möser, Philip; Hölter, Philip; Engelhorn, Tobias; Dörfler, Arnd; Huttner, Hagen B.; Schwab, Stefan; Kuramatsu, Joji; Köhn, Julia (Journal of Neurology, 2022)
Background and aim: To assess associations between clinical severity and possible dysfunction of autonomic cardiovascular modulation within the acute phase after spontaneous subarachnoid hemorrhage (SAH). Methods: In this prospective observational study, in 51 patients with spontaneous SAH, Hunt-and-Hess scores (H&H) were assessed and cardiovascular autonomic modulation was monitored within 24 h after SAH-onset. From 5 min time-series of R–R-intervals (RRI) and blood-pressure (BP) recordings, we calculated autonomic parameters including time-domain [RRI-coefficient-of-variation (RRI-CV) and square-root-of-the-mean-squared-differences-of-successive-RRIs (RMSSD)] and frequency-domain parameters [low- and high-frequency-powers of RRI- and BP-modulation (RRI-LF-, RRI-HF-, SBP-LF-powers) and RRI-total-powers]. Data were compared to those of 20 healthy volunteers. Results: RRI- and BP-values did not differ between groups. Yet, parameters of sympathetic (RRI-LF-powers 141.0 (18.9–402.4) ms2 vs 442.3 (246.8–921.2) ms2, p = 0.001) and total autonomic modulation (RRI-CV 2.4 (1.2–3.7) ms2 vs 3.7 (3.1–5.3) ms2, p = 0.001) were significantly lower in patients than in controls. Subgroup analyses (patients with H&H < 3 vs H&H ≥ 3) and Spearman-rank-correlations revealed increasing loss of sympathetic (RRI-LF-powers 338.6 (179.7–710.4) ms2 vs 72.1 (10.1–175.9) ms2, p = 0.001, rho = − 0.524) and total autonomic modulation (RRI-CV 3.5 (2.3–5.4) ms2 vs 1.6 (1.0–2.8) ms2, p < 0.001, rho = − 0.519) with higher H&H-scores. Multiple-logistic-regression underlined the significant influence of H&H-scores on sympathetic (RRI-LF-powers, p = 0.033) and total autonomic modulation (RRI-CV, p = 0.040) compared to possible confounders (e.g., age, intubation). Conclusion: Within the acute phase, spontaneous SAH induces a decrease in sympathetic and total autonomic cardiovascular modulation. Higher H&H-scores were associated with increasing autonomic dysfunction and may therefore augment the risk of cardiovascular complications and poor clinical outcome.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Autonomic nervous system; Heart rate variability; Hunt and Hess; Subarachnoid hemorrhage

Definition of K(trans) and FA Thresholds for Better Assessment of Experimental Glioma Using High-field MRI: A Feasibility Study - Engelhorn, Tobias; Schwarz, Martin; Heß, Andreas; Budinsky, Lubos; Pitann, Patrick; Eyüpoglu, Ilker Yasin; Dörfler, Arnd (Clinical Neuroradiology, 2014)
To define K(trans) and fractional anisotropy (FA) thresholds in correlation to histology for improved magnetic resonance imaging (MRI) tumor assessment in an animal model of brain glioma.Twelve rats underwent 4.7 T MRI at day 10 after tumor implantation. Anatomical scans (T2, T1 at 8 min after double dose contrast application) as well as dynamic contrast-enhanced (DCE) imaging with calculation of K(trans) and diffusion tensor imaging (DTI) with calculation of FA were performed. T2- and T1-derived tumor volumes were calculated and thresholds for K(trans) and FA were defined for best MRI tumor assessment correlated to histology.Tumor volumes were 159 ± 14 mm(3) (histology), 126 ± 26 mm(3) (T1 with contrast, r = 0.76), and 153 ± 12 mm(3) (T2, r = 0.84), respectively. K(trans)- and FA-derived tumor volumes were 160 ± 16 mm(3) (for K(trans) ³ 0.04 min(-1), r = 0.94), and 159 ± 14 mm(3) (for FA £ 0.14, r = 0.96), respectively.DCE-MRI and DTI with calculation of K(trans) and FA maps allow very precise brain glioma assessment comparable to histology if established thresholds for the given tumor model are used.
EVALuna2:8504

Detection of brain lesions after catheter ablation depends on imaging criteria: insights from AXAFA-AFNET 5 trial - Haeusler, Karl Georg; Eichner, Felizitas A.; Heuschmann, Peter U.; Fiebach, Jochen B.; Engelhorn, Tobias; Callans, David; De Potter, Tom; Debruyne, Philippe; Scherr, Daniel; Hindricks, Gerhard; Al-Khalidi, Hussein R.; Mont, Lluis; et al. (Europace, 2023)
Aims Left atrial catheter ablation is well established in patients with symptomatic atrial fibrillation (AF) but associated with risk of embolism to the brain. The present analysis aims to assess the impact of diffusion-weighted imaging (DWI) slice thickness on the rate of magnetic resonance imaging (MRI)–detected ischaemic brain lesions after ablation. Methods AXAFA-AFNET 5 trial (NCT02227550) participants underwent MRI using high-resolution (hr) DWI (slice thickness: and results 2.5–3 mm) and standard DWI (slice thickness: 5–6 mm) within 3–48 h after ablation. In 321 patients with analysable brain MRI (mean age 64 years, 33% female, median CHA2DS2-VASc 2), hrDWI detected at least one acute brain lesion in 84 (26.2%) patients and standard DWI in 60 (18.7%; P < 0.01) patients. High-resolution diffusion-weighted imaging detected more lesions compared to standard DWI (165 vs. 104; P < 0.01). The degree of agreement for lesion confirmation using hrDWI vs. standard DWI was substantial (κ = 0769). Comparing the proportion of DWI-detected lesions, lesion distribution, and total lesion volume per patient, there was no difference in the cohort of participants undergoing MRI at 1.5 T (n = 52) vs. 3 T (n = 269). Conclusion The pre-specified AXAFA-AFNET 5 sub-analysis revealed significantly increased rates of MRI-detected acute brain lesions using hrDWI instead of standard DWI in AF patients undergoing ablation. In comparison to DWI slice thickness, MRI field strength had a no significant impact in the trial. Comparing the varying rates of ablation-related MRI-detected brain lesions across previous studies has to consider these technical parameters. Future studies should use hrDWI, as feasibility was demonstrated in the multicentre AXAFA-AFNET 5 trial.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Ablation; Brain MRI; Diffusion-weighted imaging; Field strengths; Slice thickness

Development of pre-syrinx state and syringomyelia following a minor injury: a case report - Kleindienst, Andrea; Engelhorn, Tobias; Röckelein, Verena; Buchfelder, Michael (Journal of Medical Case Reports, 2020)
Background: A generally accepted rule is that posttraumatic syringomyelia (PTS) results from spinal cord injury (SCI). Case presentation: Here, we report the development of syringomyelia without SCI in a 54-year-old Caucasian man following a mild motor vehicle accident. The computed tomography on admission excluded an injury of the spine. Because of neck and back pain, magnetic resonance imaging was performed on day 3 post-injury and demonstrated minimal changes from a ligamentous strain at the cervicothoracic transition. Any traumatic affection of the bone, vertebral discs, intraspinal compartment, or spinal cord were excluded. Some limb weakness and neurogenic bladder dysfunction started manifesting within the following weeks. Repeated MRIs following the accident demonstrated arachnoid adhesions at the C1–2 level and spinal cord edema equivalent to a pre-syrinx state at 12 months and syrinx formation at 24 months. Because of further deterioration, decompression was performed at 36 months. Conclusions: We conclude that even after a minor trauma PTS can occur and that medullary edema (pre-syrinx state) may precede syrinx formation.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Pre-syrinx; Spinal cord injury; Syringomyelia; Trauma; Treatment

Diagnostic imaging in cancer therapy with magnetic nanoparticles - Lyer, Stefan; Tietze, Rainer; Dürr, Stephan; Struffert, Tobias; Engelhorn, Tobias Martin; Schwarz, Marc; Dörfler, Arnd; Budinsky, Lubos; Heß, Andreas; Schmidt, Wolfgang; Jurgons, Roland; Alexiou, Christoph (Springer Proceedings in Physics, 2012)
The unfavorable application-to-tumor-dose-ratio is a drawback of conventional systemic chemotherapy, implying an often insufficient drug dose in the tumor being associated with severe side effects for the patient. The use of chemotherapeutics bound to magnetic nanoparticles offers several advantages. On the one hand it is possible to concentrate the chemotherapeutics in the tumor region by the use of magnetic fields, like it is done in Magnetic Drug Targeting (MDT). On the other hand magnetic particles can serve as contrast agent for magnetic resonance imaging (MRI) that is bound to the therapeutics. Hence, the particles possibly are opening an insight into drug distribution in the tumor region directly after administration. Another important factor for a successful MDT-application is detailed knowledge about tumor vascularization. In this pilot study we investigated vascularization and size of an tumor in an experimental in vivo tumor model via flat-panel angiography and DYNA-CT before MDT and the particle distribution with MRI after MDT. We could show that the tumor could be displayed by MRI and DYNA-CT before and after MDT. Flat panel angiography revealed clearly the pathological tumor vascularization before MDT, while MRI imaging afterwards displayed the tumor as well as the particle distribution in the tumor.
CRIS-Team Scopus Importer:2022-06-27
Keywords: Magnetic Nanoparticles; Tumor Region; Magnetic Resonance Imaging Imaging; Signal Extinction; Left Hind Limb

Diffusion tensor imaging of the visual pathway in glaucomatous optic nerve atrophy - Engelhorn, Tobias; A. Schmidt, M.; Dörfler, Arnd; Michelson, Georg (Ophthalmologe, 2017)
In Germany more than one million inhabitants suffer from glaucoma, more than 100,000 are threatened with blindness because glaucoma is often diagnosed too late or not at all. Diagnosis and monitoring is usually carried out "only" by examination of the retina and not the whole visual pathway. However, the eye is just "the tip of the iceberg" of the actual visual pathway, which extends through the brain to the visual cortex. The interdisciplinary holistic assessment of the whole visual pathway in glaucoma is of crucial importance because glaucoma is a complex neurodegenerative disease. Subtypes, such as normal tension glaucoma (NTG), seem to originate from primary damage to the intracranial visual pathway with secondary retrograde retinal degeneration. Recent studies including glaucoma patients and healthy controls could show that diffusion tensor imaging with calculation of diffusion coefficients, i.e. fractional anisotropy (FA), mean and radial diffusivity (MD and RD) as markers of axonal integrity, provide the potential to assess the intracranial visual pathway with a high correlation to established ophthalmological examinations. In particular, calculation of FA maps of the visual pathway and accompanying voxel-based approaches, can be integrated into clinical routine. Thus, detection of glaucoma-related intracranial alterations, even in early stages of the disease, as well as differentiation of different glaucoma subtypes, is made possible. Furthermore, the diagnosis of normal tension glaucoma seems to be possible much earlier with these new imaging techniques compared to established ophthalmological work-up. Moreover, holistic imaging provides new insights into the pathophysiology of this form of glaucoma. This review article gives an overview of these novel magnetic resonance imaging techniques for assessment of the visual pathway in glaucomatous optic nerve atrophy and reveals the potential of an interdisciplinary approach.
EVALuna2:21333

Direct Oral Anticoagulant Plasma Levels for the Management of Acute Ischemic Stroke - Marsch, Armin; Macha, Kosmas; Siedler, Gabriela; Breuer, Lorenz; Strasser, Erwin; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Kallmünzer, Bernd (Cerebrovascular Diseases, 2019)
Introduction: The management of acute ischemic stroke in patients on direct oral anticoagulants (DOACs) is challenging. However, the substance-specific plasma level could guide treatment decisions on recanalization therapies. We present a plasma-level-based protocol for emergency treatment of stroke patients on oral anticoagulants. Bleeding complications and clinical outcome for patients on DOACs are reported and compared to patients on vitamin K antagonists (VKAs). Methods: In patients with acute ischemic stroke and suspected use of DOACs within 48 h prior to hospital admission, plasma levels were measured using the calibrated Xa-activity (apixaban, edoxaban, rivaroxaban) or the Hemoclot®-assay (dabigatran). Levels <50 ng/mL were supportive for thrombolysis, while high values >100 ng/mL excluded patients from recombinant tissue plasminogen activator use. For patients on VKAs, the cutoff was set at international normalized ratio of 1.7. Endovascular thrombectomy of a large vessel occlusion was performed independently from coagulation testing. Consecutive patients were included in an observational registry. Results: Five hundred and twenty-two patients (261 on VKAs and 261 on DOACs) were included. Thirty patients (11.5%) on VKAs and 24 (9.2%) on DOACs received thrombolysis, followed by mechanical thrombectomy in 10 and 14 patients, respectively. Seventeen patients in each group received thrombectomy only. Symptomatic intracranial hemorrhage associated with thrombolysis occurred in 1 patient on VKA (3.3%) and 1 on DOAC (4.2%; p = 0.872). The turnaround time of specific assays did not show a significant delay in comparison to standard coagulation parameters. Conclusion: DOAC plasma levels could support decisions on emergency treatment of ischemic stroke. Systemic thrombolysis below suggested thresholds appears preliminary feasible and safe without an excess in bleeding complications.
CRIS-Team Scopus Importer:2019-09-24

Disability-Adjusted Life-Years Associated with Intracerebral Hemorrhage and Secondary Injury - Haupenthal, David; Kuramatsu, Joji; Volbers, Bastian; Sembill, Jochen; Mrochen, Anne; Balk, Stefanie; Hölter, Philip; Lücking, Hannes; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen; et al. (JAMA Network Open, 2021)
Importance: Intracerebral hemorrhage (ICH) contributes significantly to the global burden of disease. Objective: To examine the association of ICH and secondary injury with disability-adjusted life-years (DALYs) for the individual patient. Design, Setting, and Participants: This cohort study was conducted using data from the Universitätsklinikum Erlangen Cohort of Patients With Spontaneous Intracerebral Hemorrhage study. Consecutive patients admitted to a single tertiary care center from January 1, 2006, to December 31, 2015, were included. The sample comprised patients with oral anticoagulation-associated ICH (OAC-ICH) or primary spontaneous ICH (non-OAC-ICH). Statistical analysis was conducted from October 1 to December 31, 2020. Exposures: ICH occurrence and secondary injury. Main Outcomes and Measures: DALYs, years of life lost (YLL), and years lived with disability (YLD) were analyzed by hematoma location, ICH volume, and secondary injury (ie, hematoma expansion [HE], intraventricular hemorrhage [IVH], and perihemorrhagic edema [PHE]). Results: Among 1322 patients with ICH, 615 (46.5%) were women and the mean (SD) age at hospital admission was 71 (13) years; ICH was associated with a mean (SD) of 9.46 (8.08) DALYs, 5.72 (8.29) YLL, and 3.74 (5.95) YLD. There were statistically significant differences in mean (SD) DALYs by extent of hematoma volume (< 10 mL ICH: 7.05 [6.79] DALYs; 10-30 mL ICH: 9.91 [8.35] DALYs; >30 mL ICH: 12.42 [8.47] DALYs; P <.001) and ICH location (deep location: 10.60 [8.35] DALYs; lobar location: 8.18 [7.63] DALYs; cerebellum: 8.14 [6.80] DALYs; brainstem: 12.63 [9.21] DALYs; P <.001). Regarding population-level disease burden of secondary injuries after ICH, there was a statistically significant difference in mean (SD) by injury type, with 0.94 (3.19) DALYs for HE, 2.45 (4.16) DALYs for IVH, and 1.96 (2.66) DALYs for PHE (P <.001) among the entire ICH cohort. Regarding individual-level exposure to secondary injuries after ICH, there were a mean (SD) 7.14 (6.62) DALYs for HE, 4.58 (4.75) DALYs for IVH, and 3.35 (3.28) DALYs for PHE among patients with ICH affected by secondary injuries. Conclusions and Relevance: These findings suggest that there is a high burden of disability associated with ICH and secondary injuries, and the findings may guide public health strategies. The study findings further suggest that IVH and PHE may be relevant for the overall outcome of patients with ICH, that DALYs may represent a viable outcome parameter for studies to evaluate treatment outcomes in ICH research, and that IVH and PHE may represent potential treatment targets..
CRIS-Team Scopus Importer:2021-07-30

DSC Brain Perfusion Using Advanced Deconvolution Models in the Diagnostic Work-Up of Dementia and Mild Cognitive Impairment: A Semiquantitative Comparison with HMPAO-SPECT-Brain Perfusion - Schmidt, Manuel; Engelhorn, Tobias; Lang, Stefan; Lücking, Hannes; Hölter, Philip; Fröhlich, Kilian; Ritt, Philipp; Maler, Juan Manuel; Kuwert, Torsten; Kornhuber, Johannes; Dörfler, Arnd (Journal of Clinical Medicine, 2020)
Background: SPECT (single-photon emission-computed tomography) is used for the detection of hypoperfusion in cognitive impairment and dementia but is not widely available and related to radiation dose exposure. We compared the performance of DSC (dynamic susceptibility contrast) perfusion using semi- and fully adaptive deconvolution models to HMPAO-SPECT (99mTc-hexamethylpropyleneamine oxime-SPECT). Material and Methods: Twenty-seven patients with dementia of different subtypes including frontotemporal dementia (FTD) and mild cognitive impairment (MCI) received a multimodal diagnostic work-up including DSC perfusion at a clinical 3T high-field scanner and HMPAO-SPECT. Nineteen healthy control individuals received DSC perfusion. For calculation of the hemodynamic parameter maps, oscillation-index standard truncated singular value decomposition (oSVD, semi-adaptive) as well as Bayesian parameter estimation (BAY, fully adaptive) were performed. Results: Patients showed decreased cortical perfusion in the left frontal lobe compared to controls (relative cerebral blood volume corrected, rBVc: 0.37 vs. 0.27,p= 0.048, adjusted for age and sex). Performance of rBVc (corrected for T1 effects) was highest compared to SPECT for detection of frontal hypoperfusion (sensitivity 83%, specificity 80% for oSVD and BAY, area under curve (AUC) = 0.833 respectively,p< 0.05) in FTD and MCI. For nonleakage-corrected rBV and for rBF (relative cerebral blood flow), sensitivity of frontal hypoperfusion was above 80% for oSVD and for BAY (rBV: sensitivity 83%, specificity 75%, AUC = 0.908 for oSVD and 0.917 for BAY,p< 0.05 respectively; rBF: sensitivity 83%, specificity 65%, AUC = 0.825,p< 0.05 for oSVD). Conclusion: Advanced deconvolution DSC can reliably detect pathological perfusion alterations in FTD and MCI. Hence, this widely accessible technique has the potential to improve the diagnosis of dementia and MCI as part of an interdisciplinary multimodal imaging work-up. Advances in knowledge: Advanced DSC perfusion has a high potential in the work-up of suspected dementia and correlates with SPECT brain perfusion results in dementia and MCI.
CRIS-Team WoS Importer:2020-07-31

DTI analysis in patients with primary open-angle glaucoma: impact of registration on Voxel-Wise statistics - Schmidt, Manuel; Mennecke, Angelika; Michelson, Georg; Dörfler, Arnd; Engelhorn, Tobias (PLoS ONE, 2014)
Tract-based spatial statistics (TBSS) has been used to assess the integrity of the visual pathway in glaucoma patients. TBSS uses the subjects' FA data to create a mean FA skeleton of white matter tracts before running voxel-wise cross-subject statistics. We compared four different approaches of registration of FA maps to create the skeleton and evaluated alignment and subsequently the impact of the chosen registration on voxel-wise statistics.Our study comprised 69 subjects, i.e. 46 patients with primary open angle glaucoma (POAG) and a healthy, age-matched control group of 23 subjects. Mean FA skeletons were created using the following registration approaches: registration to a standard template (T), registration to the group mean (GM), registration to a group-wise atlas (GW) and registration to the most typical subject (N). Subsequently, maps of standard deviation of the 4D images were created to assess the alignment. Voxel-wise statistics for each registration approach were performed.We found distinct differences in voxel-wise statistics depending on the chosen registration approach. Best alignment results were achieved by registration to a study specific template, i.e. to the group mean (GM) or to a group-wise atlas (GW). Overall alignment did not differ between these two approaches. However, voxel-wise statistics showed clusters of significantly decreased FA values in the T and GM approach, which were not significant after GW registration. These voxels of significantly decreased FA values after T and GM registration did not represent white matter tracts and correlated with higher standard deviation in FA maps across subjects, thus implying registration errors, especially in the optic radiation.Registration to a study-specific template, i.e. to the group mean or a group-wise atlas seems to be the method of choice in TBSS-analysis of glaucoma patients as it shows better alignment of the optic radiation and helps to rule out registration errors due to misalignment.
EVALuna2:21168

DTI parameters of axonal integrity and demyelination of the optic radiation correlate with glaucoma indices - Michelson, Georg; Engelhorn, Tobias; Wärntges, Simone; El-Rafei, Ahmed Mohamed Ibrahim; Hornegger, Joachim; Dörfler, Arnd (Graefes Archive For Clinical and Experimental Ophthalmology, 2013)
EVALuna2:21070

Dynamic Angiography and Perfusion Imaging Using Flat Detector CT in the Angiography Suite: A Pilot Study in Patients with Acute Middle Cerebral Artery Occlusions - Struffert, Tobias; Deuerling-Zheng, Y.; Kloska, Stephan; Engelhorn, Tobias; Lang, Sabine; Mennecke, Angelika; Manhart, M.; Strother, C. M.; Schwab, Sibylle; Dörfler, Arnd (American Journal of Neuroradiology, 2015)
Perfusion and angiographic imaging using intravenous contrast application to evaluate stroke patients is now technically feasible by flat detector CT performed by the angiographic system. The aim of this pilot study was to show the feasibility and qualitative comparability of a novel flat detector CT dynamic perfusion and angiographic imaging protocol in comparison with a multimodal stroke MR imaging protocol.In 12 patients with acute stroke, MR imaging and the novel flat detector CT protocol were performed before endovascular treatment. Perfusion parameter maps (MTT, TTP, CBV, CBF) and MIP/volume-rendering technique images obtained by using both modalities (MR imaging and flat detector CT) were compared.Comparison of MIP/volume-rendering technique images demonstrated equivalent visibility of the occlusion site. Qualitative comparison of perfusion parameter maps by using ASPECTS revealed high Pearson correlation coefficients for parameters CBF, MTT, and TTP (0.95-0.98), while for CBV, the coefficient was lower (0.49).We have shown the feasibility of a novel dynamic flat detector CT perfusion and angiographic protocol for the diagnosis and triage of patients with acute ischemic stroke. In a qualitative comparison, the parameter maps and MIP/volume-rendering technique images compared well with MR imaging. In our opinion, this flat detector CT application may substitute for multisection CT imaging in selected patients with acute stroke so that in the future, patients with acute stroke may be directly referred to the angiography suite, thereby avoiding transportation and saving time.
EVALuna2:22353

Early Mortality of Brain Cancer Patients and its Connection to Cytomegalovirus Reactivation During Radiochemotherapy - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Rühle, Paul-Friedrich; Putz, Florian; Semrau, Sabine; et al. (Clinical Cancer Research, 2020)
PURPOSE: If routine diagnostics are inconclusive, neurologic deterioration and death of patients with brain cancer are attributed to tumor or therapy. Therefore, diagnosing symptoms of encephalopathy caused by human cytomegalovirus (HCMV) reactivation remains uncommon. We investigated the role of HCMV reactivation in neurologic decline and clinical outcome after the start of radiochemotherapy. EXPERIMENTAL DESIGN: HCMV analyses and extended MRI studies including additional independent retrospective neuroradiologic evaluation were performed at predetermined intervals and in case of sudden neurologic decline for 118 adult patients: 63 histologically proven high-grade gliomas, 55 with brain metastases. Immunophenotyping from simultaneously taken whole-blood samples was carried out to detect immune cells serving as prognostic marker for HCMV-associated complications. Symptomatic viremia and overall survival (OS) were the endpoints. RESULTS: Twenty-four percent (28/118) of all patients (12/44 glioblastoma, 3/13 anaplastic astrocytoma; 8/31 non-small cell lung cancer (NSCLC), 13/24 other brain metastases) developed HCMV-viremia during or within 4 weeks after radiotherapy; 21 of 28 patients experienced concurrent major neurologic decline, reversible by antiviral treatment. Identified by immunophenotyping, pretherapeutically low basophil counts predicted a high-risk for HCMV-associated encephalopathy (glioblastoma: P = 0.002, NSCLC: P = 0.02). Median OS was substantially reduced after HCMV-associated encephalopathy without MRI signs of tumor progression [glioblastoma: 99 vs. 570 days (calculated 1-year OS: 22% vs. 69%; P = 0.01) and NSCLC: 47 vs. 219 days (calculated 1-year OS: 0% vs. 32%; P = 0.02)]. CONCLUSIONS: For patients with brain cancer, HCMV reactivation after the start of radiochemotherapy is a frequent risk for cognitively detrimental but treatable encephalopathy and premature death. Routinely performed HCMV diagnostics, assessing basophil counts and study-based anti-viral regimens, are necessary to combat this hidden threat.See related commentary by Lawler et al., p. 3077.
CRIS-Team Scopus Importer:2020-07-17

Efficient drug-delivery using magnetic nanoparticles–biodistribution and therapeutic effects in tumour bearing rabbits. - Peukert, Wolfgang; Tietze, Rainer; Lyer, Stefan; Dürr, Stephan; Struffert, Tobias; Engelhorn, Tobias; Schwarz, Marc; Eckert, Elisabeth; Göen, Thomas; Vasylyev, Serhiy; Trahms, Lutz; Dörfler, Arnd; et al. (Nanomedicine : nanotechnology, biology, and medicine, 2013)
To treat tumours efficiently and spare normal tissues, targeted drug delivery is a promising alternative to conventional, systemic administered chemotherapy. Drug-carrying magnetic nanoparticles can be concentrated in tumours by external magnetic fields, preventing the nanomaterial from being cleared by metabolic burden before reaching the tumour. Therefore in Magnetic Drug Targeting (MDT) the favoured mode of application is believed to be intra-arterial. Here, we show that a simple yet versatile magnetic carrier-system (hydrodynamic particles diameter <200nm) accumulates the chemotherapeutic drug mitoxantrone efficiently in tumours. With MDT we observed the following drug accumulations relative to the recovery from all investigated tissues: tumour region: 57.2%, liver: 14.4%, kidneys: 15.2%. Systemic intra-venous application revealed different results: tumour region: 0.7%, liver: 14.4 % and kidneys: 77.8%. The therapeutic outcome was demonstrated by complete tumour remissions and a survival probability of 26.7% (P=0.0075). These results are confirming former pilot experiments and implying a milestone towards clinical studies. FROM THE CLINICAL EDITOR This team of investigators studied drug carrying nanoparticles for magnetic drug targeting (MDT), demonstrating the importance of intra-arterial administration resulting in improved clinical outcomes in the studied animal model compared with intra-venous.
Keywords: treatment; drug; delievery; magnetic; nanoparticles

Endovascular therapy of isolated posterior cerebral artery occlusion stroke with and without general anesthesia - Berberich, Anne; Herweh, Christian; Qureshi, Muhammad M.; Strambo, Davide; Michel, Patrik; Räty, Silja; Abdalkader, Mohamad; Virtanen, Pekka; Olive Gadea, Marta; Ribo, Marc; Psychogios, Marios Nikos; Nguyen, Anh; et al. (Journal of Neurointerventional Surgery, 2024)
Background: The optimal anesthetic strategy for endovascular therapy (EVT) in acute ischemic stroke is still under debate. The aim of this study was to compare the clinical outcomes of patients with isolated posterior cerebral artery (PCA) occlusion stroke undergoing EVT by anesthesia modality with conscious sedation (non-GA) versus general anesthesia (GA). Methods: Patients from the Posterior CerebraL Artery Occlusion (PLATO) study were analyzed with regard to anesthetic strategy. GA was compared with non-GA using multivariable logistic regression and inverse probability of weighting treatment (IPTW) methods. The primary endpoint was the 90-day distribution of the modified Rankin Scale (mRS) score. Secondary outcomes included functional independence or return to Rankin at day 90, and successful reperfusion, defined as expanded Thrombolysis in Cerebral Infarction (eTICI) 2b to 3. Safety endpoints were symptomatic intracranial hemorrhage and mortality. Results: Among 376 patients with isolated PCA occlusion stroke treated with EVT, 183 (49%) had GA. The treatment groups were comparable, although the GA group contained more patients with severe stroke and lower posterior circulation Alberta Stroke Program Early CT Score (pc-ASPECTS). On IPTW analysis, there was no difference between groups with regard to ordinal mRS shift analysis (common OR 0.89, 95% CI 0.53 to 1.51, P=0.67) or functional independence (OR 0.84, 95% CI 0.50 to 1.39, P=0.49). There were greater odds for successful reperfusion with GA (OR 1.70, 95% CI 1.17 to 2.47, P=0.01). Safety outcomes were comparable between groups. Conclusion: In patients with isolated PCA occlusion undergoing EVT, patients treated with GA had higher reperfusion rates compared with non-GA. Both GA and non-GA strategies were safe and functional outcomes were similar.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Intervention; Stroke; Thrombectomy

Endovascular treatment in patients with large vessel occlusion: reduced mortality despite minimal penumbra - Schmidt, Manuel; Breuer, Lorenz; Kallmünzer, Bernd; Schwab, Stefan; Dörfler, Arnd; Engelhorn, Tobias; Hölter, Philip (Neuroradiology, 2019)
Purpose: In patients with acute ischemic stroke (AIS) caused by large vessel occlusion (LVO), endovascular treatment (EVT) is highly effective for emergency revascularization. However, data on functional outcome are lacking for patients, which show no or minimal mismatch between ischemic core and penumbra. Methods: Forty-five patients with AIS due to LVO of the anterior circulation were retrospectively analyzed within 6 h since onset when administered to our department. In all patients, there was no relevant penumbra according to CT perfusion (CTP). Functional outcome, defined by the modified Rankin Scale (mRS) at 30 and 90 days, was analyzed according to LVO treatment (EVT versus non-EVT). Confounding was addressed by multivariable regression analyses. Results: mRS values at 30 days (p = 0.002) and 90 days (p = 0.005) after AIS occurrence were significantly lower in patients who had received EVT. There was no significant difference regarding good functional outcome, as measured by mRS of 0–2 at 30 (p = 0.432) and 90 days, respectively (p = 0.186). Mortality was significantly reduced in patients undergoing EVT at 30-day (p < 0.001) and at 90-day follow-up (p = 0.003), respectively. Multivariable regression analyses revealed that EVT was associated with reduced mortality at 30 (OR 0.091; CI (0.013–0.612); p = 0.014) and 90 days (OR 0.134; CI (0.021–0.857); p = 0.034) after AIS. Conclusions: Despite a small and highly selected patient collective, our study indicates that AIS patients with minimal penumbra in CTP might benefit from EVT in terms of reduced mortality at 30 and 90 days after AIS. However, in this group of patients, we could not prove favorable functional outcome at 30 and 90 days, despite receiving EVT.
CRIS-Team Scopus Importer:2019-09-17
Keywords: CTP; Endovascular treatment; Mortality; Penumbra; Stroke

Endovascular treatment of patient with multiple extracranial large vessel stenosis and coexistent unruptured wide-neck intracranial aneurysm using a WEB device and Szabo-technique - Cherednychenko, Yurii; Engelhorn, Tobias; Miroshnychenko, Andrii; Zorin, Mikola; Dzyak, Liudmila; Tsurkalenko, Olena; Cherednychenko, Natalia (Radiology Case Reports, 2020)
The coexistence of severe extracranial large vessel stenosis and unruptured intracranial aneurysms is not rare. There are different treatment approaches for these conditions, such as initial treatment of the aneurysm before revascularization of the stenosis; single-stage endovascular treatment of both lesions; stenosis eliminating followed by treatment of the aneurysm, or without treating the aneurysm. But, taking into account the risk of aneurysm rupture on the one hand and the risk of ischemic stroke on the other, it is sometimes difficult to choose the right management strategy. Despite this fact, there are still no guidelines or consensus on the management of these coexistent lesions. The article describes a clinical case of endovascular treatment of multiple extracranial stenosis and coexistent unruptured wide-neck aneurysm of the middle cerebral artery. The endovascular treatment of the carotid stenosis and aneurysm using a woven endobridge device was performed in one session; endovascular treatment of vertebral artery stenosis with Szabo technique was performed in another session.
CRIS-Team Scopus Importer:2020-10-16
Keywords: Cerebral aneurysm; Endovascular treatment; Stenosis of extracranial vessel; Szabo-technique; WEB device

Endovascular Versus Medical Management of Posterior Cerebral Artery Occlusion Stroke: The PLATO Study. - Nguyen, Thanh N.; Qureshi, Muhammad M.; Strambo, Davide; Strbian, Daniel; Räty, Silja; Herweh, Christian; Abdalkader, Mohamad; Olive-Gadea, Marta; Ribo, Marc; Psychogios, Marios; Fischer, Urs; Nguyen, Anh; et al. (Stroke, 2023)
BACKGROUND: The optimal management of patients with isolated posterior cerebral artery occlusion is uncertain. We compared clinical outcomes for endovascular therapy (EVT) versus medical management (MM) in patients with isolated posterior cerebral artery occlusion. METHODS: This multinational case-control study conducted at 27 sites in Europe and North America included consecutive patients with isolated posterior cerebral artery occlusion presenting within 24 hours of time last well from January 2015 to August 2022. Patients treated with EVT or MM were compared with multivariable logistic regression and inverse probability of treatment weighting. The coprimary outcomes were the 90-day modified Rankin Scale ordinal shift and ≥2-point decrease in the National Institutes of Health Stroke Scale. RESULTS: Of 1023 patients, 589 (57.6%) were male with median (interquartile range) age of 74 (64-82) years. The median (interquartile range) National Institutes of Health Stroke Scale was 6 (3-10). The occlusion segments were P1 (41.2%), P2 (49.2%), and P3 (7.1%). Overall, intravenous thrombolysis was administered in 43% and EVT in 37%. There was no difference between the EVT and MM groups in the 90-day modified Rankin Scale shift (aOR, 1.13 [95% CI, 0.85-1.50]; P=0.41). There were higher odds of a decrease in the National Institutes of Health Stroke Scale by ≥2 points with EVT (aOR, 1.84 [95% CI, 1.35-2.52]; P=0.0001). Compared with MM, EVT was associated with a higher likelihood of excellent outcome (aOR, 1.50 [95% CI, 1.07-2.09]; P=0.018), complete vision recovery, and similar rates of functional independence (modified Rankin Scale score, 0-2), despite a higher rate of SICH and mortality (symptomatic intracranial hemorrhage, 6.2% versus 1.7%; P=0.0001; mortality, 10.1% versus 5.0%; P=0.002). CONCLUSIONS: In patients with isolated posterior cerebral artery occlusion, EVT was associated with similar odds of disability by ordinal modified Rankin Scale, higher odds of early National Institutes of Health stroke scale improvement, and complete vision recovery compared with MM. There was a higher likelihood of excellent outcome in the EVT group despite a higher rate of symptomatic intracranial hemorrhage and mortality. Continued enrollment into ongoing distal vessel occlusion randomized trials is warranted.
EVALuna2:536990

European Multicenter Study for the Evaluation of a Dual-Layer Flow-Diverting Stent for Treatment of Wide-Neck Intracranial Aneurysms: The European Flow-Redirection Intraluminal Device Study - Killer-Oberpfalzer, Monika; Kocer, N.; Griessenauer, C. J.; Janssen, H.; Engelhorn, Tobias; Holtmannspotter, Markus; Buhk, J. H.; Finkenzeller, Thomas; Fesl, G.; Trenkler, J.; Reith, W.; Berlis, A.; et al. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Endoluminal reconstruction with flow-diverting stents represents a widely accepted technique for the treatment of complex intracranial aneurysms. This European registry study analyzed the initial experience of 15 neurovascular centers with the Flow-Redirection Intraluminal Device (FRED) system. MATERIALS AND METHODS: Consecutive patients with intracranial aneurysms treated with the FRED between February 2012 and March 2015 were retrospectively reviewed. Complications and adverse events, transient and permanent morbidity, mortality, and occlusion rates were evaluated. RESULTS: During the defined study period, 579 aneurysms in 531 patients (median age, 54 years; range, 13-86 years) were treated with the FRED. Seven percent of patients were treated in the acute phase (≤3 days) of aneurysm rupture. The median aneurysm size was 7.6 mm (range, 1-36.6 mm), and the median neck size 4.5 mm (range, 1-30 mm). Angiographic follow-up of >3 months was available for 516 (89.1%) aneurysms. There was progressive occlusion witnessed with time, with complete occlusion in 18 (20%) aneurysms followed for up to 90 ± 14 days, 141 (82.5%) for 180 ± 20 days, 116 (91.3%) for 1 year ± 24 days, and 122 (95.3%) aneurysms followed for >1 year. Transient and permanent morbidity occurred in 3.2% and 0.8% of procedures, respectively. The overall mortality rate was 1.5%. CONCLUSIONS: This retrospective study in real-world patients demonstrated the safety and efficacy of the FRED for the treatment of intracranial aneurysms. In most cases, treatment with a single FRED resulted in complete angiographic occlusion at 1 year.
EVALuna2:34271

Evaluation of Functional Recovery Following Thrombectomy in Patients With Large Vessel Occlusion and Prestroke Disability - Sprügel, Maximilian; Sembill, Jochen; Kremer, Svenja; Gerner, Stefan; Knott, Michael; Hock, Stefan; Engelhorn, Tobias; Dörfler, Arnd; Huttner, Hagen; Schwab, Stefan (JAMA Network Open, 2022)
IMPORTANCE It is uncertain whether thrombectomy is associated with benefits in patients with prestroke disability.
CRIS-Team WoS Importer:2022-09-02

Feasibility of cerebral blood volume mapping by flat panel detector CT in the angiography suite: First experience in patients with acute middle cerebral artery occlusions - Struffert, Tobias; Deuerling-Zheng, Y.; Engelhorn, Tobias; Kloska, Stephan; Gölitz, Philipp; Koehrmann, M.; Schwab, S.; Strother, C. M.; Dörfler, Arnd (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: A new FPCT application offers the possibility of perfusion (FPCT CBV) and parenchymal (FPCT) imaging within the angiography suite. We tested the hypothesis that findings in FPCT CBV and FPCT would correlate with those obtained using MSCT and PCT. MATERIALS AND METHODS: In 16 patients with acute MCA occlusion, FPCT CBV was performed immediately posttreatment. The volume of tissue having abnormal CBV values was determined by FPCT CBV and PCT images. Stroke volume on follow-up MSCT was determined, CBV values in the effected parenchyma were measured, and FPCT images were reviewed. RESULTS: In 6 cases, we found a FPCT CBV value identical or higher (hyperemia) in comparison with the contralateral side. In 10 cases, we found CBV lesions with values lower (oligemia) than the contralateral brain tissue. We found a high correlation of CBV lesion volume on FPCT CBV images to stroke volume on follow-up MSCT (r = 0.9, P < .05) in the oligemia group. Absolute FPCT CBV and PCT CBV values were comparable and showed good correlation (r = 0.9, P < .05). In 8 patients, contrast medium extravasation was visible. CONCLUSIONS: The new FPCT application allows assessment of CBV in acute stroke patients. Our initial results indicate that these measurements may predict final infarct volume. The ability to assess this key parameter of cerebral perfusion within the angiographic suite may improve the management of these patients.
CRIS-Team Scopus Importer:2022-08-05

FLAIRfusion Processing with Contrast Inversion : Improving Detection and Reading Time of New Cerebral MS Lesions - Schmidt, Manuel; Linker, Ralf; Lang, S.; Lücking, Hannes; Engelhorn, Tobias; Kloska, Stephan; Uder, Michael; Dörfler, Arnd; Dankerl, Peter; Cavallaro, Alexander Josef (Clinical Neuroradiology, 2017)
To evaluate the performance of an innovative image processing approach for detection of T2-weighted hyperintense multiple sclerosis (MS) lesions.In this study 20 consecutive patients with inflammatory demyelinating lesions were retrospectively evaluated of whom 10 patients featured progressive disease and 10 a stable lesion load. 3 mm transversal FLAIRfusion imaging was processed and archived. Image processing was performed through landmark-based 3D co-registration of the previous and current isotropic FLAIR examination followed by inversion of image contrast. Thereby, the hyperintense signals of the unchanged MS plaques extinguish each other, while newly developed lesions appear bright on FLAIRfusion. Diagnostic performance was evaluated by 4 experienced readers. Consensus reading supplied the reference standard. Sensitivity, specificity, NPV (negative predictive value), PPV (positive predictive value), interreader agreement and reading time were the outcome measures analyzed.Combined sensitivity was 100% at a specificity of 88.2%, with PPV ranging from 83.3% to 90.1% and NPV at 100%. Reading time was nearly 5-fold faster than conventional side by side comparison (35.6 s vs. 163.7 s, p < 0.001). Cohen's kappa was excellent (>0.75; p < 0.001) and Cronbach's alpha was 0.994.FLAIRfusion provides reliable detection of newly developed MS lesions along with strong interreader agreement across all levels of expertise in 35 s of reading time.
EVALuna2:14615

Flat-Panel Computed Tomography (DYNA-CT) in Neuroradiology. From High-Resolution Imaging of Implants to One-Stop-Shopping for Acute Stroke - Dörfler, Arnd; Gölitz, Philipp; Engelhorn, Tobias; Kloska, Stephan; Struffert, Tobias (Clinical Neuroradiology, 2015)
Originally aimed at improving standard radiography by providing higher absorption efficiency and a wider dynamic range, flat-panel detector technology has meanwhile got widely accepted in the neuroradiological community. Especially flat-panel detector computed tomography (FD-CT) using rotational C-arm mounted flat-panel detector technology is capable of volumetric imaging with a high spatial resolution. By providing CT-like images of the brain within the angio suite, FD-CT is able to rapidly visualize hemorrhage and may thus improve complication management without the need of patient transfer. As "Angiographic CT" FD-CT may be helpful during many diagnostic and neurointerventional procedures and for noninvasive monitoring and follow-up. In addition, spinal interventions and high-resolution imaging of the temporal bone might also benefit from FD-CT. Finally, using novel dynamic perfusion and angiographic protocols, FD-CT may provide functional information on brain perfusion and vasculature with the potential to replace standard imaging in selected acute stroke patients.
EVALuna2:22997

Flat panel detector angiographic CT for stent-assisted coil embolization of broad-based cerebral aneurysms - Richter, Gregor; Engelhorn, Tobias; Struffert, Tobias; Dölken, Marc; Ganslandt, Oliver; Hornegger, Joachim; Kalender, Willi Alfred; Dörfler, Arnd (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: The purpose of this work was to evaluate angiographic CT (ACT) in the combined application of a self-expanding neurovascular stent and detachable platinum coils in the management of broad-based and fusiform intracranial aneurysms. MATERIALS AND METHODS: Eleven patients harboring wide-necked intracranial aneurysms were treated with a flexible self-expanding neurovascular stent and subsequent aneurysm embolization with platinum microcoils. ACT was performed after the interventional procedure to analyze stent position and the relationship of coils to the stent. Postprocessing included multiplanar reconstructions (MPRs) and maximum intensity projections (MIPs). ACT volume datasets were postprocessed for soft tissue visualization. RESULTS: Accurate stent placement with subsequent coil occlusion of the aneurysms was feasible in all of the patients. Similar to nonsubtracted digital subtraction angiography (DSA) images, radiopaque platinum stent markers showed excellent visibility in ACT as well. The stent struts themselves, hardly visible in nonsubtracted DSA, were visible in MPRs and MIPs of ACT in all of the patients. In aneurysms larger than 10 mm in diameter, accurate stent assessment at the level of the coils was limited due to beam hardening artifacts. Postprocedural ACT in all of the patients did not reveal any evidence of procedure-related intracranial hemorrhage. CONCLUSION: ACT provides cross-sectional, 3D visualization of endovascular stents otherwise hardly visible with plain fluoroscopy. ACT enables us to accurately determine stent position, which may be helpful in complex stent-assisted aneurysm coiling procedures. However, in aneurysms larger than 10 mm in diameter, beam hardening artifacts caused by the endoaneurysmal coil package impair visibility of the stent. Further data are necessary to evaluate the usefulness of ACT in stent-assisted aneurysm coiling.

FRED Flow Diverter: A Study on Safety and Efficacy in a Consecutive Group of 50 Patients - Lücking, Hannes; Engelhorn, Tobias; Lang, Stefan; Gölitz, Philipp; Kloska, Stephan; Roessler, Karl; Dörfler, Arnd (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: Endovascular flow diverters are increasingly used for the treatment of cerebral aneurysms. We assessed the safety and efficacy of the Flow-Redirection Endoluminal Device (FRED) in a consecutive series of 50 patients. MATERIALS AND METHODS: Inclusion criteria were wide-neck, blister-like, or fusiform/dissecting aneurysms independent of size, treated with the FRED between February 2014 and May 2015. Assessment criteria were aneurysm occlusion, manifest ischemic stroke, bleeding, or death. The occlusion rate was assessed at 3 months with flat panel CT and at 6 months with DSA by using the Raymond classification and the O'Kelly-Marotta grading scale. RESULTS: Fifty patients with 52 aneurysms were treated with 54 FREDs; 20 patients were treated with the FRED and coils. Aneurysm size ranged from 2.0 to 18.5 mm. Deployment of the FRED was successful in all cases. There were no device-associated complications. One patient developed mild stroke symptoms that fully receded within days. There have been no late-term complications so far and no treatment-related mortality. Initial follow-up at 3 months showed complete occlusion in 72.3% of the overall study group, Six-month follow-up showed total and remnant-neck occlusion in 87.2% of patients, distributed over 81.5% of the FRED-only cases and 95.0% of the cases with combined treatment. CONCLUSIONS: The FRED flow diverter is a safe device for the treatment of cerebral aneurysms of various types. Our data reveal high occlusion rates at 3 and 6 months, comparable with those in other flow diverters. Long-term occlusion rates are expected.
EVALuna2:33142

Frequent occurrence of therapeutically reversible CMV-associated encephalopathy during radiotherapy of the brain - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Ruehle, Paul F.; Putz, Florian; Semrau, Sabine; et al. (Neuro-Oncology, 2016)
Neurological decline during radio(chemo)therapy of the brain is often attributed to disease progression or side effects of radiotherapy. Diagnosis of opportunistic neurotropic infections such as cytomegalovirus (CMV) infections is uncommon, even though high-grade gliomas and some brain metastases are known to contain CMV particles. We prospectively examined the frequency of CMV encephalopathy during radiotherapy of the brain.Fifty patients requiring whole-brain radiotherapy for brain metastases (n = 27) or local radio(chemo)therapy of the brain for high-grade gliomas (n = 23) were observed in the prospective observational GLIO-CMV-01 study. MRIs and blood samples were obtained before, halfway through, and at the end of radiotherapy. MRIs were screened for disease progression or increased intracranial pressure. Blood was tested for anti-CMV immunoglobulin (Ig)M, anti-CMV IgG, and CMV DNA.Thirty-two of 50 (64%) patients were positive for anti-CMV IgG before radio(chemo)therapy. Fifteen of those 32 (48%) developed viremia during or up to 28 days after treatment. Thirteen of those 15 (87%) required treatment for CMV-associated encephalopathy. MRIs were negative for disease progression, edema, or bleeding. None of the patients negative for anti-CMV IgG developed viremia, suggesting a reactivation rather than a primary infection.In the group at risk consisting of anti-CMV IgG+ patients, age >65 (P = .004) and the amount of dexamethasone taken during radio(chemo)therapy (P = .004) were associated with an increased risk for CMV-associated encephalopathy. One hundred and fifty days after the start of radio(chemo)therapy, survival was 74% (14/19) (no encephalopathy) versus 54% (7/13) (encephalopathy) (odds ratio, 0.42; 95% CI, 0.03-1.86; P = .25).CMV reactivation frequently causes encephalopathy during radio(chemo)therapy of the brain. The unexpected high incidence of this infection makes it highly clinically relevant for every treating physician.
EVALuna2:8306

Glaucoma classification based on histogram analysis of diffusion tensor imaging measures in the optic radiation - El-Rafei, Ahmed Mohamed Ibrahim; Engelhorn, Tobias; Wärntges, Simone; Dörfler, Arnd; Hornegger, Joachim; Michelson, Georg (Springer-verlag, 2011)
Glaucoma is associated with axonal degeneration of the optic nerve leading to visual impairment. This impairment can progress to a complete vision loss. The transsynaptic disease spread in glaucoma extends the degeneration process to different parts of the visual pathway. Most of glaucoma diagnosis focuses on the eye analysis, especially in the retina. In this work, we propose a system to classify glaucoma based on visual pathway analysis. The system utilizes diffusion tensor imaging to identify the optic radiation. Diffusion tensor-derived indices describing the underlying fiber structure as well as the main diffusion direction are used to characterize the optic radiation. Features are extracted from the histograms of these parameters in regions of interest defined on the optic radiation. A support vector machine classifier is used to rank the extracted features according to their discrimination ability between glaucoma patients and healthy subjects. The seven highest ranked features are used as inputs to a logistic regression classifier. The system is applied to two age-matched groups of 39 glaucoma subjects and 27 normal controls. The evaluation is performed using a 10-fold cross validation scheme. A classification accuracy of 81.8% is achieved with an area under the ROC curve of 0.85. The performance of the system is competitive to retina based classification systems. However, this work presents a new direction in detecting glaucoma using visual pathway analysis. This analysis is complementary to eye examinations and can result in improvements in glaucoma diagnosis, detection, and treatment. © 2011 Springer-Verlag.

Glaucoma classification based on visual pathway analysis using diffusion tensor imaging - El-Rafei, Ahmed Mohamed Ibrahim; Engelhorn, Tobias; Wärntges, Simone; Dörfler, Arnd; Hornegger, Joachim; Michelson, Georg (Magnetic Resonance Imaging, 2013)
Most of the existing methods for diagnosing glaucoma analyze the eye with a main focus on the retina, despite the transsynaptic nature of the fiber degeneration caused by glaucoma. Thus, they ignore a significant part of the visual system represented by the visual pathway in the brain. The advances in neuroimaging, especially diffusion tensor imaging (DTI), enable the identification and characterization of white matter fibers. In this work, we propose a system based on DTI analysis of the visual pathway fibers in the optic radiation for detecting and discriminating different glaucoma entities. The optic radiation is identified semi-automatically. DTI provides information about the fiber orientation as well as a set of derived parameters describing the degree of diffusion anisotropy and diffusivity. Features for each DTI derived measure are extracted from a specified region of interest on the optic radiation. The features are grouped into three sets: Histogram, co-occurrence matrices, and Laws features. For feature selection, the features are ranked using a support vector machine classifier. The highest ranked features are used for classification. A support vector machine classifier is used for classification in a 10-fold cross validation setup. The system is applied to three age-matched subjects' categories containing 27 healthy, 39 primary open angle glaucoma (POAG), and 18 normal tension glaucoma (NTG) subjects. The discrimination accuracy between healthy and glaucoma (POAG and NTG) subjects is 94.1% with an area under the ROC of 0.97. Classification accuracy of 92.4% is obtained for the normal and the POAG groups while it increased to 100% in case of healthy and NTG groups. In addition, the system could differentiate between glaucoma types (POAG and NTG) with an accuracy of 98.3%. A complementary analysis was performed to estimate the selection bias in the obtained accuracy. The bias ranged from 10% to 20% depending on the group pair under consideration. The classification results indicate the high performance of the system compared to retina-based glaucoma detection systems. The proposed approach utilizes visual pathway analysis rather than the conventional eye analysis which presents a new trend in glaucoma detection. Analyzing the entire visual system could provide significant information that can improve the glaucoma examination flow and treatment. (c) 2013 Elsevier Inc. All rights reserved.
Keywords: Diffusion tensor imaging; Glaucoma; Optic radiation; Visual pathway; Classification; Texture features

Heart Failure in Ischemic Stroke: Relevance for Acute Care and Outcome - Siedler, Gabriela; Sommer, Kim; Macha, Kosmas; Marsch, Armin; Breuer, Lorenz; Stoll, Svenja; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Kallmünzer, Bernd; Arnold, Martin (Stroke, 2019)
Background and Purpose- Heart failure (HF) in patients with acute ischemic stroke constitutes the source of various detrimental pathophysiologic mechanisms including prothrombotic and proinflammatory states, worsening of cerebral tissue oxygenation, and hemodynamic impairment. In addition, HF might affect the safety and efficacy of the acute recanalization stroke therapies. Methods- Patients treated with intravenous recombinant tissue-type plasminogen activator or mechanical recanalization at a universitary stroke center were included into a prospective registry. Patients received cardiological evaluation, including echocardiography, during acute care. Functional outcome was assessed after 90 days by structured telephone interviews. Safety and efficacy of intravenous thrombolysis and mechanical thrombectomy were investigated among patients with HF and compared with patients with normal cardiac function after propensity score matching. Results- One thousand two hundred nine patients were included. HF was present in 378 patients (31%) and an independent predictor of unfavorable functional outcome. Recanalization rates were equal among patients with HF after intravenous thrombolysis and after mechanical recanalization or combined treatment. The rate of secondary intracranial hemorrhage was not different (7% versus 8%; P=0.909 after thrombolysis and 15% versus 20%, P=0.364 after mechanical recanalization or combined therapy). Early mortality within 48 hours after admission was equal (<1.5% in both groups). Conclusions- In this real-world cohort of patients with stroke, HF was an independent predictor of unfavorable functional long-term outcome, while the safety and efficacy of intravenous thrombolysis and mechanical recanalization appeared unaffected.
EVALuna2:204477

High-resolution diffusion tensor-imaging indicates asymmetric microstructural disorganization within substantia nigra in early Parkinson's disease - Knossalla, Frauke; Kohl, Zacharias; Winkler, Jürgen; Schwab, Stefan; Schenk, Thomas; Engelhorn, Tobias; Dörfler, Arnd; Gölitz, Philipp (Journal of Clinical Neuroscience, 2018)
BACKGROUND AND PURPOSE: Parkinson's disease (PD) is characterised by neuropathological degenerative changes in the substantia nigra (SN). Our study aimed to evaluate whether high-resolution diffusion tensor-imaging (DTI) can detect anatomical biomarkers in early-stage PD, and has the potential to visualize asymmetry effects comparable to the 123I-FP-CIT SPECT (DaTSCAN). METHODS: Ten early-stage PD patients with mild disease severity and ten age- and gender-matched healthy controls were examined with a high-resolution DTI protocol at a 3 Tesla MRI scanner to assess fractional anisotropy (FA) values in the ventral, middle and dorsal region of SN. In addition, a subgroup of 5 PD patients underwent a DaTSCAN. RESULTS: PD subjects showed reduced FA values in all SN regions compared to controls, but post hoc analysis revealed a significant reduction (p = .032) in the dorsal region. There was no significant correlation between clinical data and FA values. Subgroup analysis of PD patients with asymmetric radioligand uptake in the DaTSCAN demonstrated also significant asymmetric FA values (p = .027) in the dorsal region of SN. CONCLUSIONS: Our results provide preliminary evidence that high-resolution DTI can detect in early-stage PD patients with mild disease severity an anatomical biomarker in the dorsal region of SN, indicating microstructural disorganization. This biomarker, discriminating potentially in vivo between patients and healthy people, could be valuable for early PD diagnosis. If asymmetric radioligand uptake in the DaTSCAN was present, also asymmetry effects in the dorsal region of SN were obtained by DTI. These findings might contribute to improve effectiveness in diagnosing and monitoring PD.
EVALuna2:34272

Imaging modalities using magnetic nanoparticles - overview of the developments in recent years - Schwarz, Marc; Dörfler, Arnd; Engelhorn, Tobias; Struffert, Tobias; Tietze, Rainer; Janko, Christina; Tripal, Philipp; Cicha, Iwona; Dürr, Stephan; Alexiou, Christoph; Lyer, Stefan (Nanotechnology Reviews, 2013)
The use of nanoparticles in tumor imaging, molecular imaging, and drug delivery has significantly expanded in the last few years. The relatively new field of "theranostics" combines their capacity for drug delivery with their potential as contrast agents. Depending on the imaging modality used, several types of nanoparticles are available, such as gold for optical imaging or superparamagnetic iron oxide for magnetic resonance imaging. This review will give a short overview of the different types of nanoparticles as well as their development and potential application in recent years. Furthermore, it describes the research on classic imaging modalities as well as on new techniques to image nanoparticles in vivo and focuses on magnetic-based imaging modalities.
EVALuna2:19967

Impairment of the Visual System in Glaucoma - Schmidt, Manuel; Engelhorn, Tobias; Dörfler, Arnd; Michelson, Georg (Klinische Monatsblätter für Augenheilkunde, 2019)
MR Diffusion Tensor Imaging (DTI) enables visualisation of the visual system in glaucoma; it has been shown that the atrophy of the optic radiation is more pronounced in glaucoma than in age-matched controls. The atrophy of the optic radiation thereby correlates with OCT and visual field measures. Diffusion tensor imaging permits quantification of the axonal integrity of the optic radiation by calculation of fractional anisotropy (FA) and radial diffusivity (RD). Both within and also outside the visual system, there are substantial changes in FA and RD, changes suggesting a complex neurodegenerative disease. Metabolic MRI by specific Na+-coils and by the CEST-technique (CEST: chemical exchange saturation transfer) will enable visualisation of neuronal cell death and pathological protein accumulation in the visual system. It is proposed that glaucomatous atrophy of the visual system may be induced by antero- and retrograde axonal degeneration. In normal tension glaucoma and PEX glaucoma, retrograde degeneration is induced by ischemic lesions or pathological protein accumulation within the cerebral portion of the visual system. Magnetic resonance imaging of the visual system with DTI and metabolic imaging will potentially improve therapeutic monitoring and diagnosis of glaucoma.
CRIS-Team WoS Importer:2019-03-06

Influence of bundled care treatment on functional outcome in patients with intracerebral hemorrhage - Mrochen, Anne; Song, Yu; Harders, Verena; Sembill, Jochen; Sprügel, Maximilian; Hock, Stefan; Lang, Stefan; Engelhorn, Tobias; Kallmünzer, Bernd; Volbers, Bastian; Kuramatsu, Joji (Frontiers in Neurology, 2024)
Background and aims: General guideline recommendations in patients with intracerebral hemorrhage (ICH) include blood pressure-, temperature- and glucose management. The therapeutic effect of such a “care bundle” (blood pressure lowering, glycemic control, and treatment of pyrexia) on clinical outcomes becomes increasingly established. For the present study, we aimed to investigate associations of strict bundled care treatment (BCT) with clinical outcomes and characterize associations with key outcome effectors such as hematoma enlargement (HE) and peak perihemorrhagic edema (PHE). Methods: We screened consecutive ICH patients (n = 1,322) from the prospective UKER-ICH cohort study. BCT was defined as achieving and maintaining therapeutic ranges for systolic blood pressure (110–160 mmHg), glucose (80–180 mg/dL), and body temperature (35.5–37.5°C) over the first 72 h. The primary outcome was the functional outcome at 12 months (modified Rankin Scale (mRS) 0–3). Secondary outcomes included mortality at 12 months, the occurrence of hematoma enlargement, and the development of peak perihemorrhagic edema. Confounding was addressed by a doubly robust methodology to calculate the absolute treatment effect (ATE) and by calculating e-values. Results: A total of 681 patients remained for analysis, and 182 patients fulfilled all three BCT criteria and were compared to 499 controls. The ATE of BCT to achieve the primary outcome was 9.3%, 95% CI (1.7 to 16.9), p < 0.001; e-value: 3.1, CI (1.8). Mortality at 12 months was significantly reduced by BCT [ATE: −12.8%, 95% CI (−19.8 to −5.7), p < 0.001; e-value: 3.8, CI (2.2)], and no association was observed for HE or peak PHE. Significant drivers of BCT effect on the primary outcome were systolic blood pressure control (ATE: 15.9%) and maintenance of normothermia (ATE: 10.9%). Conclusion: Strict adherence to this “care bundle” over the first 72 h during acute hospital care in patients with ICH was independently associated with improved functional long-term outcome, driven by systolic blood pressure control and maintenance of normothermia. Our findings strongly warrant prospective validation to determine the generalizability especially in Western countries. Clinical trial registration:ClinicalTrials.gov, identifier [ID: NCT03183167].
CRIS-Team Scopus Importer:2024-08-30
Keywords: bundle; HE; ICH; PHE; treatment

Influence of Early Enteral Nutrition on Clinical Outcomes in Neurocritical Care Patients With Intracerebral Hemorrhage - Peng, Jianhua; Volbers, Bastian; Sprugel, Maximilian I.; Hölter, Philip; Engelhorn, Tobias; Jiang, Yong; Kuramatsu, Joji; Huttner, Hagen; Dörfler, Arnd; Schwab, Stefan; Gerner, Stefan (Frontiers in Neurology, 2021)
Objective: Early enteral nutrition (EEN) represents the current standard of care for patients treated in general intensive care units (ICU). Specific nutritional recommendations for patients receiving dedicated neurocritical care are not established. This study investigated associations of EEN with clinical outcomes for patients suffering from intracerebral hemorrhage treated at a neurological ICU (NICU).
CRIS-Team WoS Importer:2021-05-14

Influence on Outcome and Treatment of Intracerebral Hematoma in Patients with Atraumatic Subarachnoid Hemorrhage - Gerner, Stefan; Kuramatsu, Joji; Reichl, Jonathan; Eyüpoglu, Ilker Yasin; Dörfler, Arnd; Engelhorn, Tobias; Schwab, Stefan; Huttner, Hagen (CEREBROVASCULAR DISEASES, 2019)
CRIS-Team WoS Importer:2020-02-21

Insular multiple sclerosis lesions are associated with erectile dysfunction - Winder, Klemens; Linker, Ralf; Seifert, Frank; Deutsch, Martina; Engelhorn, Tobias; Dörfler, Arnd; Lee, De-Hyung; Hoesl, Katharina M.; Hilz, Max-Josef (Journal of Neurology, 2018)
Erectile function (EF) is frequently compromised in men with multiple sclerosis (MS). Functional neuroimaging in healthy men identified a network of brain areas, such as the insula, visual and somatosensory association areas, cingulate gyrus, prefrontal cortex, as well as subcortical regions, contributing to EF. This study intended to determine associations between EF deterioration during MS and cerebral MS-associated lesion sites. In 31 men with MS (mean age 38.2 ± 11.2 years), we evaluated MS-related EF deterioration by comparing scores of the 5-item International Index of Erectile Function-5 questionnaire (IIEF5) at the time of study and retrospectively, 3 months prior to MS diagnosis, by calculating score differences as DeltaIIEF5 (DeltaIIEF5 score < 0 indicated EF deterioration). To assess the impact of confounding factors of EF, patient age, disease duration, disease severity, depressiveness, bladder and bowel symptoms, and total cerebral MS lesion volume were correlated with DeltaIIEF5 scores (Spearman rank correlation) and compared between patients with and without EF deterioration (t tests or Mann-Whitney U test). MS lesions were assessed on T2-weighted magnetic resonance imaging (MRI; 1.5 or 3 T). We determined the lesion overlap (prevalence of identical lesion sites among patients), subtracted lesion overlaps in patients without EF deterioration from overlaps in patients with EF deterioration, and compared DeltaIIEF5 scores voxel-wise between patients with and without lesions in a given voxel (t test; significance: p < 0.05). In 14 patients (45.2%), DeltaIIEF5 scores indicated EF deterioration. DeltaIIEF5 scores were not associated with age (ρ = 0.06; p = 0.74), disease duration (ρ = 0.26; p = 0.15), disease severity (ρ = - 0.19; p = 0.31), depressiveness (ρ = 0.07; p = 0.72), bladder symptoms (ρ = - 0.11; p = 0.57), bowel symptoms (ρ = 0.17; p = 0.37), and total lesion volume (ρ = - 0.13; p = 0.47). The voxel-wise analysis showed associations between EF deterioration and MS lesions primarily in the bilateral, and predominantly left juxtacortical insular region. In conclusion, MS lesions particularly in the left insular region, which is activated with sexual arousal, contribute to erectile dysfunction.
EVALuna2:34021

Integrity/Demyelination of the optic radiation, morphology of the papilla, and contrast sensitivity in glaucoma patients - Michelson, Georg; Wärntges, Simone; Engelhorn, Tobias; El-Rafei, Ahmed Mohamed Ibrahim; Hornegger, Joachim; Dörfler, Arnd (Klinische Monatsblätter für Augenheilkunde, 2012)
Background: In primary open angle glaucoma (POAG) and its non-barotraumatic subgroup, normal tension glaucoma (NTG), the pathophysiological differences are not clear. A participation of the 4th neuron of the visual pathway (optic radiation) appears possible on the basis of related experimental studies. The goal of the present study was the evaluation of the optic radiation by diffusion tensor imaging (DTI), which is based on the magnetic resonance imaging. The diffusion and anisotropy parameters of the optic radiation as a marker of axonal integrity and demyelination/damage of glial cells, respectively, were used to investigate the relation between the morphology of the papilla (BLDF, linear discriminant function of Burk) and the contrast sensitivity (FDT, frequency doubling test). Patients and Methods: In this prospective observational study 13 POAG patients, 13 NTG patients, and 7 control patients of the same mean age were included. For segmentation of the optic radiation a semi-automated algorithm was applied and the diffusion and anisotropy parameters were calculated. The importance of the covariates age, BLDF, and FDT for the DTI parameters was determined using partial correlation analysis. Results: Analysis of the covariates partially showed a clear autocorrelation. The correlations between the DTI parameters and BLDF were significant in all groups after correction of the measurement values for the covariates. FDT correlated with DTI parameters in controls and POAG. The NTG group did not show this correlation due to a strong spreading of the FDT values. Conclusion: After statistical elimination of the autocorrelation of the covariates age, BLDF, and FDT the morphology of the papilla correlated with the axonal integrity and demyelination/glia cell impairment of the optic radiation in controls and glaucoma. In NTG the impaired contrast sensitivity is highly variable and is not associated with the condition of the 3rd or 4th neuron, respectively, as compared to POAG. The autocorrelation between individual covariates represents an important element for the judgement of the visual pathway. © Georg Thieme Verlag KG · Stuttgart · New York.

Investigation of lateral geniculate nucleus volume and diffusion tensor imaging in patients with normal tension glaucoma using 7 tesla magnetic resonance imaging - Schmidt, Manuel; Knott, Michael; Heidemann, Robin; Michelson, Georg; Kober, Tobias; Dörfler, Arnd; Engelhorn, Tobias (PLoS ONE, 2018)
BACKGROUND: There is evidence that glaucoma is a neurodegenerative disease involving the whole visual pathway. We prospectively examined potential benefits of volumetry of the lateral geniculate nucleus (LGN) and diffusion tensor imaging (DTI) using a new 7T scanner. METHODS: 20 patients with normal tension glaucoma and 16 control individuals were examined. LGN volume and fractional anisotropy (FA) of the optic tract (OT) and the optic radiation (OR) and their correlation with RNFL (retinal nerve fiber layer) thickness were analyzed. RESULTS: LGN volume was significantly reduced in NTG (60.9 vs 88.3; p < 0.05). FA of the OT (right: 0.35 vs 0.66, left: 0.36 vs 0.67; p < 0.05) and of the OR (right: 0.41 vs 0.70, left: 0.41 vs 0.69; p < 0.05) was also significantly reduced. Nasal RNFL thickness correlated with the volume of the contralateral LGN (r = 0.471, p = 0.05). Temporal RNFL thickness correlated with the volume of the ipsilateral LGN (r = 0.603, p = 0.015). CONCLUSION: NTG leads to significant atrophy of the LGN compared to controls. FA of the optic tract and the optic radiation is reduced in NTG as sign of axonal degeneration. RNFL thickness but not FA correlates with LGN volume.
EVALuna2:34502

Isolated meningomyeloradiculitis following infection with tick borne encephalitis virus - Racz, Attila; Schaller, Gerd; Lunkenheimer, Jens; Engelhorn, Tobias; Dörfler, Arnd; Sperling, Wolfgang; Schwab, Stefan; Maihöfner, Christian (Clinical Neurology and Neurosurgery, 2012)
CRIS-Team Scopus Importer:2022-08-05
Keywords: Meningomyeloradiculitis; Myelitis; Polyradiculitis; Tick borne encephalitis virus

Isolated Unilateral Strabismus Sursoadductorius (Congenital Trochlear Palsy) with and without Hypotrophia of the Superior Oblique Muscle-Orthoptic Differences in Adulthood - Gusek-Schneider, Gabriele-Charlotte; Kaestle, Nicola; Reil, Franziska; Schuerhoff, Sabine; Engelhorn, Tobias (Klinische Monatsblätter für Augenheilkunde, 2018)
PURPOSE: The clinical feature of unilateral decompensating strabismus sursoadductorius (dSSA; often called congenital superior oblique palsy, CSOP) is not an etiologically uniform entity. Hypotrophy of the superior oblique muscle (HMOS) is a frequent and immediate cause of dSSA/CSOP. In this study, clinical characteristics of dSSA/CSOP with and without HMOS are compared. PATIENTS AND METHODS: Twenty-five consecutive patients (age 14 - 69 years; median 43 years) were included in this study, 14 with 3T MRI-proven HMOS (group 1) and 11 without HMOS (group 2). HMOS was defined as a reduction of the medio-lateral (ML) as well as based on ML and cranio-caudal (CC) diameter calculated area = (ML · CC/4) · π of the affected superior oblique muscle (SOM) < 80% in comparison to the contralateral SOM (measured on the single coronal image on which the muscle has its greatest extent). The two groups were compared in terms of head tilt, cyclo- and vertical deviation and the Bielschowsky head tilt test. Patients were classified according the Knapp's classification. RESULTS: Both the incidence of head tilt with 14/14 vs. 5/11 (χ2 = 0.003) and its degree: 11.1 ± 4.5° vs. 3.2 ± 4.1° (p < 0.001) was higher in group 1 than in group 2, as well as the Bielschowsky head tilt test: 9.3 ± 4.3° vs. 3.8 ± 4.9° (p = 0.008). The average amount of hypertropia was larger in group 1 than in group 2 during adduction: 16.7 ± 5.3° vs. 9.3 ± 3.4° (p < 0.001) as well as during adduction and downgaze of the affected eye: 14.6 ± 7.1 vs. 7.2 ± 3.7° (p = 0.03). In the sagittal plane, the increase of vertical deviation was larger in group 1 than in group 2: 2.8 ± 7.8 vs. - 2.4 ± 4.2 (p = 0.04); the excyclodeviation was larger in group 1 in all three planes (sagittal plane, adduction and abduction) in comparison to group 2: 1.3 ± 4.1 vs. - 2.9 ± 2.8 (p = 0.006), 2.4 ± 5.2 vs. - 2.2 ± 2.9 (p = 0.01), 0.5 ± 3.8 vs. - 2.7 ± 3.9 (p = 0.05). Knapp's class II was found in 6 of 15 patients in group 1 and only in this patient group (χ2 = 0.03). CONCLUSIONS: In both groups, the vertical deviation showed a great dispersion. In patients without HMOS (group 2), vertical deviation in adduction did not exceed 15°. Patients with HMOS (group 1) do not show the typical features of a later acquired trochlear palsy due to an early developed compensating innervation. A vertical deviation in adduction of more than 15°, increasing excyclodeviation towards downgaze in all three planes (sagittal plane, adduction and abduction) and Knapp's class II are relatively reliable predictors of a hypoplasia of the SOM. An internationally uniform term for this group of patients, such as superior oblique weakness or superior oblique hypotrophy, would be desirable.
EVALuna2:34915

IV Thrombolysis for Acute Ischemic Stroke with Unknown Onset in Patients on Oral Anticoagulation - Macha, Kosmas; Sembill, Jochen; Mühlen, Iris; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Kallmünzer, Bernd (Cerebrovascular Diseases, 2024)
Introduction: IV thrombolysis (IVT) is established in the unknown or extended time window based on multimodal imaging. Further, increasing evidence exists regarding IVT in patients on oral anticoagulation including direct oral anticoagulants (DOACs). However, data on IVT in ischemic stroke patients on oral anticoagulation with unknown time of stroke onset are sparse. Methods: This study bases on the longitudinal cohort study Stroke Research Consortium in Northern Bavaria (STAMINA; ClinicalTrials.gov Identifier: NCT04357899). Acute ischemic stroke patients treated with IVT in the unknown or extended time window from January 2015 to December 2019 were included. Patient selection was based on multimodal CT or MRI. Patients on oral anticoagulation (vitamin-K antagonist [VKA] or DOAC within 48 h) were eligible for IVT based on INR measurement (VKA) or plasma levels (DOAC) according to an institutional protocol. Primary outcomes were the incidence of any and symptomatic intracranial hemorrhage. Results: Of 170 ischemic stroke patients treated with IVT in the unknown or extended time window, 151 had no oral anticoagulation at stroke onset and 19 were on oral anticoagulation (6 on VKA and 13 on DOAC). The risk of symptomatic ICH according to ECASS II criteria was similar between the patients with and without oral anticoagulation (1 [5.3%] vs. 4 [2.7%], p = 0.453). After adjustment for confounding factors, pre-medication with oral anticoagulation was not associated with symptomatic ICH (aOR 1.02 [0.09-11.02], p = 0.988). Conclusion: IVT for ischemic stroke with unknown onset appeared safe in selected patients on oral anticoagulation with both DOAC and VKA.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Direct oral anticoagulant; Ischemic stroke; IV thrombolysis; Unknown onset; Vitamin-K antagonist

IV-Thrombolysis in Ischemic Stroke With Unknown Time of Onset—Safety and Outcomes in Posterior vs. Anterior Circulation Stroke - Macha, Kosmas; Hölter, Philip; Siedler, Gabriela; Wang, Ruihao; Knott, Michael; Stoll, Svenja; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Mühlen, Iris; Kallmünzer, Bernd (Frontiers in Neurology, 2021)
Background: rt-PA for ischemic stroke in the unknown or extended time window beyond the first 4. 5 h after symptom onset is safe and effective for certain patients after selection by multimodal neuroimaging. However, the evidence for this approach comes mainly from patients with anterior circulation stroke (ACS), while the data on posterior circulation stroke (PCS) are scarce. Methods: Ischemic stroke patients treated with IV-thrombolysis in the unknown or extended time window between January 2011 and May 2019 were identified from an institutional registry. The patients were categorized into PCS or ACS based on clinico-radiological findings. We analyzed the hemorrhagic complications, clinical and imaging efficacy outcomes, and mortality rates by comparing the PCS and ACS patient groups. Adjusted outcome analyses were performed after propensity score matching for the relevant factors. Results: Of the 182 patients included, 38 (20.9%) had PCS and 144 (79.1%) had ACS. Symptomatic acute large vessel occlusion (LVO) was present in 123 patients on admission [27 (22.0%) PCS and 96 (78.0%) ACS]. The score on the National Institutes of Health Stroke Scale (NIHSS), the time from last seen normal, and the door-to-needle times were similar in PCS and ACS. In patients with LVO, the NIHSS score was lower [8 (5–15) vs. 14 (9–18), p = 0.005], and infarction visible on follow-up imaging was less common [70.4 vs. 87.5%; aRD, −18.9% (−39.8 to −2.2%)] in the PCS patient group. There was a trend toward a lower risk for intracranial hemorrhage (ICH) following intravenous thrombolysis in PCS vs. ACS, without reaching a statistical significance [5.3 vs. 16.9%; aRD, −10.4% (−20.4 to 4.0%)]. The incidence of symptomatic ICH [according to the ECASS III criteria: 2.6 vs. 3.5%; aRD, −2.9% (−10.3 to 9.2%)], efficacy outcomes, and mortality rates were similar in PCS and ACS patients. Conclusions: In this real-world clinical cohort, the safety and the efficacy of rt-PA for ischemic stroke in the unknown or extended time window did not show relevant differences between PCS and ACS, with a trend toward less hemorrhagic complications in PCS. The findings reconfirm the clinician in the usage of rt-PA beyond the first 4.5 h also in selected patients with PCS.
CRIS-Team Scopus Importer:2021-10-01
Keywords: anterior circulation stroke; extended time window; IV-thrombolysis; posterior circulation stroke; wake-up stroke

Janus-faced spatacsin (SPG11): involvement in neurodevelopment and multisystem neurodegeneration - Pozner, Tatyana; Regensburger, Martin; Engelhorn, Tobias; Winkler, Jürgen; Winner, Beate (Brain, 2020)
Hereditary spastic paraplegia (HSP) is a heterogeneous group of rare motor neuron disorders characterized by progressive weakness and spasticity of the lower limbs. HSP type 11 (SPG11-HSP) is linked to pathogenic variants in the SPG11 gene and it represents the most frequent form of complex autosomal recessive HSP. The majority of SPG11-HSP patients exhibit additional neurological symptoms such as cognitive decline, thin corpus callosum, and peripheral neuropathy. Yet, the mechanisms of SPG11-linked spectrum diseases are largely unknown. Recent findings indicate that spatacsin, the 280 kDa protein encoded by SPG11, may impact the autophagy-lysosomal machinery. In this update, we summarize the current knowledge of SPG11-HSP. In addition to clinical symptoms and differential diagnosis, our work aims to link the different clinical manifestations with the respective structural abnormalities and cellular in vitro phenotypes. Moreover, we describe the impact of localization and function of spatacsin in different neuronal systems. Ultimately, we propose a model in which spatacsin bridges between neurodevelopmental and neurodegenerative phenotypes of SPG11-linked disorders.
CRIS-Team Scopus Importer:2020-09-04
Keywords: autophagy; hereditary spastic paraplegia; neurodegeneration; neurodevelopment; SPG11

Klinische und echographische Untersuchungsbefunde bei Patienten mit Carotis-Sinus-cavernosus-Fisteln - Huebner, L.; Struffert, T.; Mardin, Christian; Engelhorn, Tobias; Holbach, L.; Weller, J.; Hohberger, Bettina; Gusek-Schneider, Gabriele (Ophthalmologe, 2021)
Background: Symptoms and clinical findings in patients with carotid-cavernous fistulas are specific. Nevertheless, they can be very mildly expressed. This study aims to point out the potential diagnostic value of ultrasound of the orbit. Methods: A total of 25 patients with a reliable angiographic diagnosis of a fistula were reviewed retrospectively. We analyzed the symptoms, clinical findings and demonstrability in ultrasound of the orbit. Results: The most common clinical findings were nerve palsy, dilation of episcleral vessels and exophthalmos. If an ultrasound had been part of the examination a dilation of the superior ophthalmic vein could be demonstrated in all cases. Conclusion: The expeditious ultrasound investigation provides valuable information for the diagnosis of red eyes which are resistant to treatment. The examiner has to consider a fistula and perform an ultrasound especially when diplopia has newly occurred. Finally, the expedient neuroimaging can be arranged.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Diplopia; Echography; Exophthalmos; Red eye; Superior ophthalmic vein

Learning Curve for Flow Diversion of Posterior Circulation Aneurysms: A Long-Term International Multicenter Cohort Study - Adeeb, N.; Dibas, Mahmoud; Griessenauer, C. J.; Cuellar, H. H.; Salem, M. M.; Xiang, S.; Enriquez-Marulanda, A.; Hong, T.; Zhang, H.; Taussky, P.; Grandhi, R.; Waqas, M.; et al. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Flow diversion has gradually become a standard treatment for intracranial aneurysms of the anterior circulation. Recently, the off-label use of the flow diverters to treat posterior circulation aneurysms has also increased despite initial concerns of rupture and the suboptimal results. This study aimed to explore the change in complication rates and treatment outcomes across time for posterior circulation aneurysms treated using flow diversion and to further evaluate the mechanisms and variables that could potentially explain the change and outcomes. MATERIALS AND METHODS: A retrospective review using a standardized data set at multiple international academic institutions was performed to identify patients with ruptured and unruptured posterior circulation aneurysms treated with flow diversion during a decade spanning January 2011 to January 2020. This period was then categorized into 4 intervals. RESULTS: A total of 378 procedures were performed during the study period. Across time, there was an increasing tendency to treat more vertebral artery and fewer large vertebrobasilar aneurysms (P = .05). Moreover, interventionalists have been increasingly using fewer overlapping flow diverters per aneurysm (P = .07). There was a trend toward a decrease in the rate of thromboembolic complications from 15.8% in 2011?13 to 8.9% in 2018?19 (P = .34).CONCLUSIONS: This multicenter experience revealed a trend toward treating fewer basilar aneurysms, smaller aneurysms, and increased usage of a single flow diverter, leading to a decrease in the rate of thromboembolic and hemorrhagic complications.
CRIS-Team WoS Importer:2022-10-28

Lesion correlates of secondary paroxysmal dyskinesia in multiple sclerosis - Fröhlich, Katharina; Winder, Klemens; Linker, Ralf; Huhn, Konstantin; Engelhorn, Tobias; Dörfler, Arnd; Lee, De-Hyung; Schwab, Stefan; Seifert, Frank (Journal of Neurology, 2018)
Secondary paroxysmal dyskinesia is a rare but life-quality-compromising symptom in multiple sclerosis (MS) and might be associated with particular MS lesions. The present study intended to determine associations between paroxysmal dyskinesia and the MS-associated lesion site using a voxelwise lesion analysis. We conducted a retrospective study and sought MS patients with documented paroxysmal dyskinesia and controls without paroxysmal dyskinesia matched for age, disease severity, and disease duration in a local database. The MS lesions were analysed on T2-weighted magnetic resonance imaging scans (1.5 or 3 T), manually outlined, and transformed into stereotaxic space. We determined the lesion overlap and compared the absence or presence of paroxysmal dyskinesia voxelwise between patients with and without lesions in a given voxel using the Liebermeister test with 4000 permutations. From 15,869 MS patient records screened, we identified 25 patients with paroxysmal dyskinesia. The voxelwise analysis in 22 subjects yielded associations between paroxysmal dyskinesia and MS lesions in the internal capsule, the basal ganglia, and another prominent lesion cluster in the posterior periventricular white matter. Our voxelwise analysis shows associations between paroxysmal dyskinesia and MS lesions in the internal capsule and basal ganglia, areas contributing to motor sequence programming. This association in another lesion site located in the posterior thalamic radiation suggests that lesions in subcortical sensory pathways may also contribute to paroxysmal dyskinesia in MS.
EVALuna2:34912

Limited versus Whole-Brain Perfusion for the Indication of Thrombolysis in the Extended Time Window of Acute Cerebral Ischemia - Breuer, Lorenz; Knott, Michael; Struffert, Tobias; Kloska, Stephan; Kurka, Natalia; Schwab, Stefan; Dörfler, Arnd; Köhrmann, Martin; Engelhorn, Tobias (Journal of Stroke and Cerebrovascular Diseases, 2015)
Perfusion computed tomography (PCT) has emerged as alternative to magnetic resonance imaging (MRI) for assessment of patients clinically qualifying for off-label thrombolysis within 4.5 to 9 hours after onset of ischemic stroke. However, disadvantage of PCT is its often limited anatomic coverage with only 2 or 3 slices when using a 4- to 64-section scanner. Our purpose was therefore to evaluate the value of 2- and 3-slice perfusion compared to whole-brain perfusion.One hundred twenty-five patients undergoing MRI beyond 4.5 hours after symptom onset with supratentorial perfusion deficit were selected retrospectively. Accordingly to PCT slice positioning, 2 or 3 slices of the whole-brain perfusion weighted imaging data set were depicted. Volumes of infarct (using cerebral blood volume) and penumbra (using time-to-peak and cerebral blood volume) were calculated, and results were compared with 2- and 3-slice-derived volumes, respectively.Whole-brain imaging revealed a mismatch of more than 20% in 68.8% of patients (defined as 100%). Two-slice imaging detected a perfusion deficit in 72% and a mismatch in 48.8% (sensitivity = 70.9%). Three-slice imaging detected a perfusion deficit in 76% and a mismatch in 50.4% (sensitivity = 73.3%). Although there was no significant difference between 2- and 3-slice imaging (P > .23), both techniques revealed significantly less patients with mismatch compared to whole-brain coverage (P < .01).Two- and 3-slice imaging like obtained with PCT on most installed CT systems to assess perfusion deficits with subsequent mismatch calculation in acute stroke outside the 4.5-hour time window is significantly inferior to whole-brain coverage and, hence, has to be considered as a less-than-ideal solution.
EVALuna2:22358

Longitudinal Sodium MRI of Multiple Sclerosis Lesions: Is there Added Value of Sodium Inversion Recovery MRI - Mennecke, Angelika; Nagel, Armin Michael; Huhn, Konstantin; Linker, Ralf; Schmidt, Manuel; Rothhammer, Veit; Wilferth, Tobias; Linz, Peter; Wegmann, Julius; Eisenhut, Felix; Engelhorn, Tobias; Dörfler, Arnd (Journal of Magnetic Resonance Imaging, 2021)
Background Sodium enhancement has been demonstrated in multiple sclerosis (MS) lesions. Purpose To investigate sodium MRI with and without an inversion recovery pulse in acute MS lesions in an MS relapse and during recovery. Study Type Prospective. Subjects Twenty-nine relapsing-remitting MS patients with an acute relapse were included. Field Strength/Sequence A 3D density-adapted radial sodium sequence at 3 T using a dual-tuned (Na-23/H-1) head coil. Assessment Full-brain images of the tissue sodium concentration (TSC1, n = 29) and a sodium inversion recovery sequence (SIR1, n = 20) at the beginning of the anti-inflammatory therapy and on medium-term follow-up visits (days 27-99, n = 12 [TSC], n = 5 [SIR]) were measured. Regions of interest (RoIs) with contrast enhancement (T1CE+) and without change in T1-weighted imaging (FL + T1n) were normalized (nTSC and nSIR). To gain insight on the origin of the TSC enhancement at time point 1, it is investigated whether the nTSC enhancement of the lesions is accompanied by a change of the respective nSIR. Potential prognostic value of nSIR1 is examined referring to the nTSC progression. Statistical Tests nTSC and nSIR were compared regarding the type of lesion and the time point using a one-way ANOVA. Pearson's correlation coefficient was calculated for nTSC over nSIR and for nTSC1-nTSC2 over nSIR1. A P-value At the first measurement, all lesion types showed increased nTSC, while nSIR was decreased in the FL + T(1)n and the T1CE+ lesions in comparison to the normal-appearing white matter. For acute lesions, the difference between nTSC at baseline and nTSC at time point 2 showed a significant correlation with the baseline nSIR. Data Conclusion At time point 1, nTSC is increased, while nSIR is unchanged or decreased in the lesions. The mean sodium IR signal at baseline correlates with recovery or progression of an acute lesion. Evidence Level 2 Technical Efficacy Stage 4
CRIS-Team WoS Importer:2021-07-23

Measurement of quantifiable parameters by time-density curves in the elastase-induced aneurysm model: first results in the comparison of a flow diverter and a conventional aneurysm stent - Struffert, Tobias; Ott, Sabine; Kowarschik, Markus; Bender, Frederik; Adamek, Edyta; Engelhorn, Tobias; Gölitz, Philipp; Lang, Stefan; Strother, Charles M.; Dörfler, Arnd (European Radiology, 2013)
Quantifiable parameters to evaluate the effectiveness of flow diverters (FDs) are desirable. We measured time-density curves (TDCs) and calculated quantifiable parameters in the rabbit elastase-induced aneurysm model after stent (Neuroform [NF]) and FD (Pipeline embolisation device [PED]) treatment.Sixteen rabbit elastase-induced aneurysms were treated with FD (n = 9) or NF (n = 5). Angiography was performed before and after treatment and TDCs were created. The time to peak (TTP), the full width at half maximum (FWHM) and the average slope of the curve which represent the inflow (IF) and outflow (OF) were calculated.Mean values before treatment were TTP = 0.8 s, FWHM = 1.2 s, IF = 153.5 and OF = -54.9. After PED treatment, the TTP of 1.8 s and FWHM of 47.8 s were extended. The IF was 31.2 and the OF was -11.5 and therefore delayed. The values after NF treatment (TTP = 1.1 s, FWHM = 1.8 s, IF = 152.9, OF = -33.2) changed only slightly.It was feasible to create TDCs in the rabbit aneurysm model. Parameters describing the haemodynamic effect of PED and NF were calculated and were different according to the type of device used. These parameters could possibly serve as predictive markers for aneurysm occlusion.
EVALuna2:22984

Mechanical Thrombectomy Using the new Solitaire™ Platinum Stent-retriever: Reperfusion Results, Complication Rates and Early Neurological Outcome - Pfaff, Johannes; Rohde, Stefan; Engelhorn, Tobias; Dörfler, Arnd; Bendszus, Martin; Möhlenbruch, Markus Alfred (Clinical Neuroradiology, 2019)
Background and Purpose: The application of radiopaque markers to the Solitaire™ stent-retriever for better visibility during mechanical thrombectomy (MT) has the potential to alter the well-known characteristics of the device; however, it is uncertain whether this adjustment influences efficacy or safety of the enhanced stent-retriever. Methods: Retrospective analysis of stroke databases of three comprehensive stroke centers. Our investigation was focused on technical and angiographic parameters, including procedure times, reperfusion results (thrombolysis in cerebral infarction, TICI), periprocedural complications and favorable early neurological recovery at discharge (modified Rankin scale ≤2 or National Institutes of Health Stroke Scale, NIHSS = 0 or ∆NIHSS ≥ 10), from consecutive patients with acute anterior circulation ischemic stroke treated with a Solitaire™ Platinum stent-retriever between October 2016 and March 2017. Results: A total of 75 patients (male: n = 27, 36%, age in years: mean (SD): 75 (±12), median baseline NIHSS: 17 (interquartile range IQR: 11–21), n = 41, 54.7% received additional i. v. thrombolytics) were treated with a median number of 2 device passes (range: 1–5). The median time from groin puncture to final TICI was 56 min (IQR: 41–79). In 69 patients (92%) TICI 2b-3 was achieved. Early neurological recovery was seen in 47 (62.7%) patients. The following periprocedural complications occurred: vasospasms (n = 7, 9.3%), emboli into a new territory (n = 4, 5.3%), symptomatic intracranial hemorrhage (n = 3, 4%), difficulties during device delivery/deployment (n = 1, 1.3%). Conclusion: The usage of the Solitaire™ Platinum stent-retriever for MT in acute ischemic stroke patients was highly effective and was not accompanied by an increased periprocedural complication rate.
CRIS-Team Scopus Importer:2019-06-25
Keywords: Acute ischemic stroke; Mechanical thrombectomy; Solitaire™ Platinum; Stent-retriever; Visibility

Microstructural abnormalities of the posterior thalamic radiation and the mediodorsal thalamic nuclei in females with anorexia nervosa - A voxel based diffusion tensor imaging (DTI) study - Frieling, Helge; Fischer, Julia; Wilhelm, Julia; Engelhorn, Tobias; Bleich, Stefan; Hillemacher, Thomas; Dörfler, Arnd; Kornhuber, Johannes; De Zwaan, Martina; Peschel, Thomas (Journal of Psychiatric Research, 2012)
Gray matter abnormalities have been found in anorexia nervosa (AN) in several brain regions. However, little is known about white matter abnormalities under the condition of AN. To comprehensively assess the microstructural integrity of white matter pathways in women with anorexia nervosa, we performed voxel-based Diffusion Tensor Imaging (DTI). 21 women with AN according to DSM-IV criteria (9 of them recovered) and 20 female age-matched healthy control subjects were enrolled in the study. The patients had a mean body mass index of 17.2 kg/m2 (controls: 19.6 kg/m2). High resolution T1 images (MP-RAGE) and DTI were performed on a 3 T Siemens-scanner. Images were pre-processed and analyzed using a modified protocol for DTI in SPM2. Fractional anisotropy (FA) maps were compared using t-tests (p < 0.05, corrected). Compared with controls, AN patients showed bilateral reductions of FA maps in the posterior thalamic radiation which includes the optic radiation, and the left mediodorsal thalamus. Our study is limited by the small sample size and its cross-sectional design. A longitudinal design with the same individuals assessed when acutely ill and recovered is warranted for future studies. For the first time, the findings of our DTI study identified disturbances of associational and commissural fibers in the bilateral occipitotemporal white matter. The results help narrowing the prevailing biological models of AN by suggesting that body image distortion is related to microstructural alterations of white matter tracts connecting the extrastriate visual cortex with other brain regions involved in body perception. © 2012 Elsevier Ltd.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Anorexia nervosa; Extrastriate body area; Voxel-based apparent diffusivity coefficient mapping; Voxel-based diffusion tensor imaging

MIF-CD74 signaling impedes microglial M1 polarization and facilitates brain tumorigenesis - Ghoochani, Ali; Schwarz, Martin; Yakubov, Eduard; Engelhorn, Tobias; Dörfler, Arnd; Buchfelder, Michael; Bucala, R.; Savaskan, N. E.; Eyupoglu, I. Y. (Oncogene, 2016)
Microglial cells in the brain tumor microenvironment are associated with enhanced glioma malignancy. They persist in an immunosuppressive M2 state at the peritumoral site and promote the growth of gliomas. Here, we investigated the underlying factors contributing to the abolished immune surveillance. We show that brain tumors escape pro-inflammatory M1 conversion of microglia via CD74 activation through the secretion of the cytokine macrophage migration inhibitory factor (MIF), which results in a M2 shift of microglial cells. Interruption of this glioma-microglial interaction through an antibody-neutralizing approach or small interfering RNA (siRNA)-mediated inhibition prolongs survival time in glioma-implanted mice by reinstating the microglial pro-inflammatory M1 function. We show that MIF-CD74 signaling inhibits interferon (IFN)-γ secretion in microglia through phosphorylation of microglial ERK1/2 (extracellular signal-regulated protein kinases 1 and 2). The inhibition of MIF signaling or its receptor CD74 promotes IFN-γ release and amplifies tumor death either through pharmacological inhibition or through siRNA-mediated knockdown. The reinstated IFN-γ secretion leads both to direct inhibition of glioma growth as well as inducing a M2 to M1 shift in glioma-associated microglia. Our data reveal that interference with the MIF signaling pathway represents a viable therapeutic option for the restoration of IFN-γ-driven immune surveillance.
EVALuna2:33151

Monitoring of balloon test occlusion of the internal carotid artery by parametric color coding and perfusion imaging within the angio suite: first results - Struffert, Tobias; Deuerling-Zheng, Y.; Engelhorn, Tobias; Kloska, Stephan; Gölitz, Philipp; Bozzato, A.; Kapsreiter, M.; Strother, C. M.; Dörfler, Arnd (Clinical Neuroradiology, 2013)
Temporary balloon test occlusion (BTO) might be performed prior to procedures in which occlusion of the internal carotid artery (ICA) might be necessary. We tested the hypothesis that parametric color coding (PCC) of angiographic series (digital subtraction angiography (DSA)) along with the assessment of cerebral blood volume (CBV) in the angiography suite would simplify and enhance the identification of candidates who are most likely to tolerate occlusion.Fifteen patients underwent angiographic series (DSA) and perfusion imaging before and during BTO. Pre- and postocclusion DSA acquisitions were evaluated for venous delay by conventional methods ("eye balling") and by PCC measurements. Comparison of CBV values between the left and right hemisphere in 6 defined regions was performed.Values of venous delay by eye balling and PCC showed a high correlation (r = 0.87, p < 0.01). Bland-Altman plot indicated slightly lower values (-0.05 s) by the PCC method. One of the 15 patients developed an asymmetrical CBV map with an increase in CBV of more than one standard deviation in 3 of the 6 regions of interest (ROIs). Acquisition of angiographic series and perfusion imaging did not prolong the test occlusion time.PCC and CBV mapping are feasible during BTO. The use of PCC seems to simplify the ability to measure changes in venous filling delay. Perfusion imaging may show an increase in CBV in patients reaching the limits of cerebral autoregulation. These patients may be at risk for delayed infarction, even though they seem to tolerate temporary occlusion, and could be unsuitable candidates for permanent ICA occlusion.
EVALuna2:22981

MRI assessment of experimental gliomas using 17.6 T - Schwarz, Marc A.; Pham, Mirko; Helluy, Xavier; Dörfler, Arnd; Engelhorn, Tobias (Neuroradiology, 2013)
Introduction: Using ultra-high-field contrast-enhanced magnetic resonance imaging (MRI), an increase of field strength is associated with a decrease of T 1 relaxivity. Yet, the impact of this effect on signal characteristics and contrast-enhanced pathology remains unclear. Hence, we evaluated the potential of a 17.6-T MRI to assess contrast-enhancing parts of experimentally induced rat gliomas compared to 3 T. Methods: A total of eight tumor-bearing rats were used for MRI assessments either at 17.6 T (four rats) or at 3 T (four rats) at 11 days after stereotactic implantation of F98 glioma cells into the right frontal lobe. T 1-weighted sequences were used to investigate signal-to-noise-ratios, contrast-to-noise-ratios, and relative contrast enhancement up to 16 min after double-dose contrast application. In addition, tumor volumes were calculated and compared to histology. Results: The 17.6-T-derived contrast-enhancing volumes were 31.5 ± 15.4 mm3 at 4 min, 38.8 ± 12.7 mm3 at 8 min, 51.1 ± 12.6 mm3 at 12 min, and 61.5 ± 10.8 mm3 at 16 min after gadobutrol injection. Corresponding histology-derived volumes were clearly higher (138.8 ± 8.4 mm3; P < 0.01). At 3 T, contrast-enhancing volumes were 85.2 ± 11.7 mm3 at 4 min, 107.3 ± 11.0 mm3 at 8 min, 117.0 ± 10.5 mm3 at 12 min, and 129.1 ± 10.0 mm3 at 16 min after contrast agent application. Averaged histology-derived volumes (139.1 ± 13.4 mm 3) in this group were comparable to the 16-min volume (P â† 16 min = 0.38). Compared to ultra-high-field MRI, all 3-T-derived volumes were significantly higher (P < 0.02). Conclusion: Compared to 3-T-derived images and histology, tumor volumes were underestimated by approximately 50 % at 17.6 T. Hence, contrast-enhanced 17.6-T MRI provided no further benefits in tumor measurement compared to 3 T. © 2013 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2022-08-05
Keywords: 17.6 T; 3 T; MRI; Rat brain; Tumor

MRI-Detected Brain Lesions and Cognitive Function in Patients With Atrial Fibrillation Undergoing Left Atrial Catheter Ablation in the Randomized AXAFA-AFNET 5 Trial - Hausler, Karl Georg; Eichner, Felizitas A.; Heuschmann, Peter U.; Fiebach, Jochen B.; Engelhorn, Tobias; Blank, Benjamin; Callans, David; Elvan, Arif; Grimaldi, Massimo; Hansen, Jim; Hindricks, Gerhard; Al-Khalidi, Hussein R.; et al. (Circulation, 2022)
BACKGROUND: We aimed to assess the prevalence of ischemic brain lesions detected by magnetic resonance imaging and their association with cognitive function 3 months after first-time ablation using continuous oral anticoagulation in patients with paroxysmal atrial fibrillation (AF).
CRIS-Team WoS Importer:2022-04-01

Multimodal CT or MRI for IV thrombolysis in ischemic stroke with unknown time of onset - Macha, Kosmas; Hölter, Philip; Siedler, Gabriela; Knott, Michael; Schwab, Stefan; Dörfler, Arnd; Kallmünzer, Bernd; Engelhorn, Tobias (Neurology, 2020)
OBJECTIVE: To investigate differences in procedure times, safety, and efficacy outcomes comparing 2 different protocols to enable thrombolysis in the extended or unknown time window after stroke onset with either multimodal CT or MRI. METHODS: Patients with ischemic stroke in the extended or unknown time window who received IV thrombolysis between January 2011 and May 2019 were identified from an institutional registry. Imaging-based selection was done by multimodal CT or MRI according to institutional treatment algorithms. RESULTS: IV thrombolysis was performed in 100 patients (54.3%) based on multimodal CT imaging and in 84 patients (45.7%) based on MRI. Baseline clinical data, including stroke severity and time from last seen normal to hospital admission, were similar in patients with CT and MRI. Door-to-needle times were shorter in patients with CT-based selection (median [interquartile range] 45 [37-62] minutes vs 75 [59-90] minutes; mean difference [95% confidence interval (CI)] -28 minutes [-35 to -21]). No differences were detected regarding the incidence of symptomatic intracranial hemorrhage (2 [2.0%] vs 4 [4.8%]; adjusted odds ratio [aOR] [95% CI] 0.47 [0.08-2.83]) and favorable outcome at day 90 (25 [33.8%] vs 33 [42.9%]; aOR 0.95 [0.45-2.02]). CONCLUSION: IV thrombolysis in ischemic stroke in the unknown or extended time window appeared safe in CT- and MRI-selected patients, while the use of CT imaging led to faster door-to-needle times. CLASSIFICATION OF EVIDENCE: This study provides Class IV evidence that for patients with ischemic stroke in the extended or unknown time window, imaging-based selection for IV thrombolysis by multimodal CT compared to MRI led to shorter door-to-needle times.
CRIS-Team Scopus Importer:2020-12-11

Neuroanatomic Correlates of Female Sexual Dysfunction in Multiple Sclerosis - Winder, Klemens; Linker, Ralf; Seifert, Frank; Deutsch, Martina; Engelhorn, Tobias; Dörfler, Arnd; Lee, De-Hyung; Hoesl, Katharina M.; Hilz, Max-Josef (Annals of Neurology, 2016)
This study intended to determine associations between alterations of female sexual arousal as well as vaginal lubrication and the site of cerebral multiple sclerosis (MS) lesions.In 44 women with MS (mean age: 36.5 ± 9.9 years), we assessed their medical history and evaluated sexual function using the Female Sexual Function Index scores for arousal and vaginal lubrication. We determined potential confounding factors of sexual dysfunction: age; disease duration; physical disability; depression; bladder or urinary dysfunction; and total volume of cerebral lesions. Arousal and lubrication scores were correlated with one another and with potential confounding factors. Cerebral MS lesions were recorded on imaging scans. A voxel-based lesion symptom mapping (VLSM) analysis adjusted for confounding variables was performed correlating cerebral sites of MS lesions with arousal and lubrication scores.Decreased arousal scores correlated with decreased lubrication scores; decreased lubrication scores were associated with bladder or urinary symptoms. Arousal and lubrication scores were not associated with any other variables. Multivariate VLSM analysis, including arousal and lubrication scores as covariables of interest, showed right occipital lesions associated with impaired arousal and left insular lesions associated with decreased lubrication. Impaired lubrication remained associated with left insular lesions after adjustment for bladder or urinary dysfunction.Our data indicate that impaired female sexual arousal is associated with MS lesions in the occipital region, integrating visual information and modulating attention toward visual input. Impaired lubrication correlated with lesions in the left insular region, contributing to mapping and generating visceral arousal states. Ann Neurol 2016;80:490-498.
EVALuna2:22501

One year survival of brain tumor patients is closely linked to symptomatic CMV-encephalopathy - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Merkel, Andreas; Rühle, Paul-Friedrich; Putz, Florian; et al. (2017)
EVALuna2:32882

On PTV definition for glioblastoma based on fiber tracking of diffusion tensor imaging data - Witulla, Barbara; Goerig, Nicole; Putz, Florian; Frey, Benjamin; Engelhorn, Tobias; Dörfler, Arnd; Uder, Michael; Fietkau, Rainer; Bert, Christoph; Laun, Frederik Bernd (PLoS ONE, 2020)
Radiotherapy (RT) is commonly applied for the treatment of glioblastoma multiforme (GBM). Following the planning target volume (PTV) definition procedure standardized in guidelines, a 20% risk of missing non-local recurrences is present. Purpose of this study was to evaluate whether diffusion tensor imaging (DTI)-based fiber tracking may be beneficial for PTV definition taking into account the prediction of distant recurrences. 56 GBM patients were examined with magnetic resonance imaging (MRI) including DTI performed before RT after resection of the primary tumor. Follow-up MRIs were acquired in three month intervals. For the seven patients with a distant recurrence, fiber tracking was performed with three algorithms and it was evaluated whether connections existed from the primary tumor region to the distant recurrence. It depended strongly on the used tracking algorithm and the used tracking parameters whether a connection was observed. Most of the connections were weak and thus not usable for PTV definition. Only in one of the seven patients with a recurring tumor, a clear connection was present. It seems unlikely that DTI-based fiber tracking can be beneficial for predicting distant recurrences in the planning of PTVs for glioblastoma multiforme.
CRIS-Team Scopus Importer:2020-01-21

Parenchymatous hematoma in patients with atraumatic subarachnoid hemorrhage: Characteristics, treatment, and clinical outcomes - Gerner, Stefan; Hülsbrink, Robert; Reichl, Jonathan; Mrochen, Anne; Eyüpoglu, Ilker Yasin; Brandner, Sebastian; Dörfler, Arnd; Engelhorn, Tobias; Kuramatsu, Joji; Schwab, Stefan; Huttner, Hagen (International Journal of Stroke, 2020)
Background: Data regarding the influence of concomitant parenchymatous hematoma (PH) on long-term outcomes in patients with atraumatic subarachnoid hemorrhage (SAH) are scarce. Further, it is not established if these patients benefit from surgical intervention. Aim: The aim of this study was to determine the influence of concomitant PH in SAH patients on functional long-term outcome, and whether these patients may benefit from surgical hematoma evacuation. Methods: Over a 5-year period, all consecutive patients with SAH treated at the Departments of Neurology, Neuroradiology, and Neurosurgery, at the University Hospital Erlangen (Germany) were recorded. In addition to the clinical and imaging characteristics of SAH, we documented the presence, location, and volume of PH as well as treatment parameters. Outcome assessment at 12 months included functional outcome (modified Rankin scale (mRS), favorable = 0–2), health-related quality of life, and long-term complications. For outcome analysis, a propensity score matching (ratio 1:1, caliper 0.1) was performed to compare SAH patients with and without PH. Sub-analyses were performed regarding PH treatment (surgical evacuation vs. conservative). Results: A total of 494 patients with atraumatic SAH were available. Eighty-five (17.2%) had PH on initial imaging. SAH patients with PH had a worse clinical condition on admission and had a greater extent of subarachnoid/intraventricular hemorrhage. Median PH volume was 11.0 ml (5.4–31.8) with largest volumes observed in patients with ruptured middle cerebral artery (MCA)-aneurysm (31.7 ml (16.3–43.2)). After propensity-score matching (PSM), patients with PH had worse functional outcomes at 12 months (modified Rankin scale (mRS) 0–2: PH 31.8% vs. ØPH57.7% p < 0.001), and a lower rate of self-reported health compared to patients without PH (EQ-5D VAS: PH 50(30–70) vs. ØPH 80(65–95); p < 0.001). In PH patients, surgical evacuation was associated with a higher rate of favorable outcome at 12 months compared to those treated conservatively (surgery 14/28 (50.0%) vs. conservative 14/57 (24.6%); adjusted odds-ratio (OR; 95%CI): 1.34 (1.08–1.66); p = 0.001), irrespective of aneurysm location. Subgroup-analysis revealed positive associations of surgical hematoma evacuation with outcome in subgroups with larger PH volumes (>10 ml; OR (95%CI): 1.39 (1.09–1.79)), frontal PH location (OR 1.59 (1.14–2.23)), and early surgery (within 600 min after onset; OR 1.42 (1.03–1.94)). Conclusions: Concomitant PH occurs frequently in patients with SAH and is associated with functional impairment after 1 year. Surgical evacuation of PH may improve outcomes in these patients, irrespective of aneurysm-location.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Cerebral hemorrhage; complications; intracerebral hemorrahage; subarachnoid hemorrhage; surgery; treatment

Pearls & Oy-sters: Moyamoya Vasculopathy and Its Association With Congenital Heart Disease - Osterloh, Justus; Heim, Christian; Siedler, Gabriela; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Kallmünzer, Bernd (Neurology, 2021)
CRIS-Team Scopus Importer:2021-06-25

Pearls & Oy-sters: SARS-CoV-2 Infection of the CNS in a Patient With Meningeosis Carcinomatosa - Steininger, Philipp; Seifert, Frank; Balk, Stefanie; Kuramatsu, Joji; Kremer, Andreas; Coras, Roland; Engelhorn, Tobias; Maier, Clara; Tenbusch, Matthias; Korn, Klaus; Enßer, Armin (Neurology, 2021)
CRIS-Team Scopus Importer:2021-03-26

Potential of Sodium MRI as a Biomarker for Neurodegeneration and Neuroinflammation in Multiple Sclerosis - Huhn, Konstantin; Engelhorn, Tobias; Linker, Ralf A.; Nagel, Armin Michael (Frontiers in Neurology, 2019)
In multiple sclerosis (MS), experimental and ex vivo studies indicate that pathologic intra-and extracellular sodium accumulation may play a pivotal role in inflammatory as well as neurodegenerative processes. Yet, in vivo assessment of sodium in the microenvironment is hard to achieve. Here, sodium magnetic resonance imaging ((NaMRI)-Na-23) with its non-invasive properties offers a unique opportunity to further elucidate the effects of sodium disequilibrium in MS pathology in vivo in addition to regular proton based MRI. However, unfavorable physical properties and low in vivo concentrations of sodium ions resulting in low signal-to-noise-ratio (SNR) as well as low spatial resolution resulting in partial volume effects limited the application of (NaMRI)-Na-23. With the recent advent of high-field MRI scanners and more sophisticated sodium MRI acquisition techniques enabling better resolution and higher SNR, (NaMRI)-Na-23 revived. These studies revealed pathologic total sodium concentrations in MS brains now even allowing for the (partial) differentiation of intra-and extracellular sodium accumulation. Within this review we (1) demonstrate the physical basis and imaging techniques of (NaMRI)-Na-23 and (2) analyze the present and future clinical application of (NaMRI)-Na-23 focusing on the field of MS thus highlighting its potential as biomarker for neuroinflammation and -degeneration.
CRIS-Team WoS Importer:2019-02-22

PRG3 induces Ras-dependent oncogenic cooperation in gliomas - Fan, Zheng; Bittermann-Rummel, Philipp; Yakubov, Eduard; Chen, Daishi; Broggini, Thomas; Sehm, Tina; Hatipoglu Majernik, Gökce; Hock, Stefan; Schwarz, Marc; Engelhorn, Tobias; Dörfler, Arnd; Buchfelder, Michael; et al. (Oncotarget, 2016)
Malignant gliomas are one of the most devastating cancers in humans. One characteristic hallmark of malignant gliomas is their cellular heterogeneity with frequent genetic lesions and disturbed gene expression levels conferring selective growth advantage. Here, we report on the neuronal-associated growth promoting gene PRG3 executing oncogenic cooperation in gliomas. We have identified perturbed PRG3 levels in human malignant brain tumors displaying either elevated or down-regulated PRG3 levels compared to non-transformed specimens. Further, imbalanced PRG3 levels in gliomas foster Ras-driven oncogenic amplification with increased proliferation and cell migration although angiogenesis was unaffected. Hence, PRG3 interacts with RasGEF1 (RasGRF1/CDC25), undergoes Ras-induced challenges, whereas deletion of the C-terminal domain of PRG3 (PRG3ΔCT) inhibits Ras. Moreover PRG3 silencing makes gliomas resistant to Ras inhibition. In vivo disequilibrated PRG3 gliomas show aggravated proliferation, invasion, and deteriorate clinical outcome. Thus, our data show that the interference with PRG3 homeostasis amplifies oncogenic properties and foster the malignancy potential in gliomas.
EVALuna2:23011

Prognostic Accuracy of CTP Summary Maps in Patients with Large Vessel Occlusive Stroke and Poor Revascularization after Mechanical Thrombectomy-Comparison of Three Automated Perfusion Software Applications - Mühlen, Iris; Borutta, Matthias; Siedler, Gabriela; Engelhorn, Tobias; Hock, Stefan; Knott, Michael; Hölter, Philip; Volbers, Bastian; Schwab, Stefan; Dörfler, Arnd (Tomography, 2022)
Background: Innovative automated perfusion software solutions offer support in the management of acute stroke by providing information about the infarct core and penumbra. While the performance of different software solutions has mainly been investigated in patients with successful recanalization, the prognostic accuracy of the hypoperfusion maps in cases of futile recanalization has hardly been validated. Methods: In 39 patients with acute ischemic stroke (AIS) due to large vessel occlusion (LVO) in the anterior circulation and poor revascularization (thrombolysis in cerebral infarction (TICI) 0-2a) after mechanical thrombectomy (MT), hypoperfusion analysis was performed using three different automated perfusion software solutions (A: RAPID, B: Brainomix e-CTP, C: Syngo.via). The hypoperfusion volumes (HV) as Tmax > 6 s were compared with the final infarct volumes (FIV) on follow-up CT 36-48 h after futile recanalization. Bland-Altman analysis was applied to display the levels of agreement and to evaluate systematic differences. Based on the median hypoperfusion intensity ratio (HIR, volumetric ratio of tissue with a Tmax > 10 s and Tmax > 6 s) patients were dichotomized into high- and low-HIR groups. Subgroup analysis with favorable (<0.6) and unfavorable (>= 0.6) HIR was performed with respect to the FIV. HIR was correlated to clinical baseline and outcome parameters using Pearson's correlation. Results: Overall, there was good correlation without significant differences between the HVs and the FIVs with package A (r = 0.78, p < 0.001) being slightly superior to B and C. However, levels of agreement were very wide for all software applications in Bland-Altman analysis. In cases of large infarcts exceeding 150 mL the performance of the automated software solutions generally decreased. Subgroup analysis revealed the FIV to be generally underestimated in patients with HIR >= 0.6 (p < 0.05). In the subgroup with favorable HIR, however, there was a trend towards an overestimation of the FIV. Nevertheless, packages A and B showed good correlation between the HVs and FIVs without significant differences (p > 0.2), while only package C significantly overestimated the FIV (-54.6 +/- 56.0 mL, p = 0.001). The rate of modified Rankin Scale (mRS) 0-3 after 3 months was significantly higher in favorable vs. unfavorable HIR (42.1% vs. 13.3%, p = 0.02). Lower HIR was associated with higher Alberta Stroke Program Early CT Score (ASPECTS) at presentation and on follow-up imaging, lower risk of malignant edema, and better outcome (p < 0.05). Conclusion: Overall, the performance of the automated perfusion software solutions to predict the FIV after futile recanalization is good, with decreasing accuracy in large infarcts exceeding 150 mL. However, depending on the HIR, FIV can be significantly over- and underestimated, with Syngo showing the widest range. Our results indicate that the HIR can serve as valuable parameter for outcome predictions and facilitate the decision whether or not to perform MT in delicate cases.
CRIS-Team WoS Importer:2022-07-08

Prophylactic nimodipine treatment and improvement in hearing outcome after vestibular schwannoma surgery: a combined analysis of a randomized, multicenter, Phase III trial and its pilot study - Scheller, Christian; Wienke, Andreas; Tatagiba, Marcos; Gharabaghi, Alireza; Ramina, Kristofer F.; Ganslandt, Oliver Thomas; Bischoff, Barbara; Zenk, Johannes; Engelhorn, Tobias; Matthies, Cordula; Westermaier, Thomas; Antoniadis, Gregor; et al. (Journal of Neurosurgery, 2017)
OBJECTIVE In clinical routines, neuroprotective strategies in neurosurgical interventions are still missing. A pilot study (n = 30) and an analogously performed Phase III trial (n = 112) pointed to a beneficial effect of prophylactic nimodipine and hydroxyethyl starch (HES) in vestibular schwannoma (VS) surgery. Considering the small sample size, the data from both studies were pooled. METHODS The patients in both investigator-initiated studies were assigned to 2 groups. The treatment group (n = 70) received parenteral nimodipine (1-2 mg/hour) and HES (hematocrit 30%-35%) from the day before surgery until the 7th postoperative day. The control group (n = 72) was not treated prophylactically. Facial and cochlear nerve functions were documented preoperatively, during the inpatient care, and 1 year after surgery. RESULTS Pooled raw data were analyzed retrospectively. Intent-to-treat analysis revealed a significantly lower risk for hearing loss (Class D) 12 months after surgery in the treatment group compared with the control group (OR 0.46, 95% CI 0.22-0.97; p = 0.04). After exclusion of patients with preoperative Class D hearing, this effect was more pronounced (OR 0.38, 95% CI 0.17-0.83; p = 0.016). Logistic regression analysis adjusted for tumor size showed a 4 times lower risk for hearing loss in the treatment group compared with the control group (OR 0.25, 95% CI 0.09-0.63; p = 0.003). Facial nerve function was not significantly improved with treatment. Apart from dose-dependent hypotension (p < 0.001), the study medication was well tolerated. CONCLUSIONS Prophylactic nimodipine is safe and may be recommended in VS surgery to preserve hearing. Prophylactic neuroprotective treatment in surgeries in which nerves are at risk seems to be a novel and promising concept. Clinical trial registration no.: DRKS 00000328 ( https://drks-neu.uniklinik-freiburg.de/drks_web/ ).
EVALuna2:33133

Prophylactic nimodipine treatment for cochlear and facial nerve preservation after vestibular schwannoma surgery: a randomized multicenter Phase III trial - Scheller, Christian; Wienke, Andreas; Tatagiba, Marcos; Gharabaghi, Alireza; Ramina, Kristofer F.; Ganslandt, Oliver Thomas; Bischoff, Barbara; Zenk, Johannes; Engelhorn, Tobias; Matthies, Cordula; Westermaier, Thomas; Antoniadis, Gregor; et al. (Journal of Neurosurgery, 2016)
OBJECT A pilot study of prophylactic nimodipine and hydroxyethyl starch treatment showed a beneficial effect on facial and cochlear nerve preservation following vestibular schwannoma (VS) surgery. A prospective Phase III trial was undertaken to confirm these results. METHODS An open-label, 2-arm, randomized parallel group and multicenter Phase III trial with blinded expert review was performed and included 112 patients who underwent VS surgery between January 2010 and February 2013 at 7 departments of neurosurgery to investigate the efficacy and safety of the prophylaxis. The surgery was performed after the patients were randomly assigned to one of 2 groups using online randomization. The treatment group (n = 56) received parenteral nimodipine (1-2 mg/hr) and hydroxyethyl starch (hematocrit 30%-35%) from the day before surgery until the 7th postoperative day. The control group (n = 56) was not treated prophylactically. RESULTS Intent-to-treat analysis showed no statistically significant effects of the treatment on either preservation of facial nerve function (35 [67.3%] of 52 [treatment group] compared with 34 [72.3%] of 47 [control group]) (p = 0.745) or hearing preservation (11 [23.4%] of 47 [treatment group] compared with 15 [31.2%] of 48 [control group]) (p = 0.530) 12 months after surgery. Since tumor sizes were significantly larger in the treatment group than in the control group, logistic regression analysis was required. The risk for deterioration of facial nerve function was adjusted nearly the same in both groups (OR 1.07 [95% CI 0.34-3.43], p = 0.91). In contrast, the risk for postoperative hearing loss was adjusted 2 times lower in the treatment group compared with the control group (OR 0.49 [95% CI 0.18-1.30], p = 0.15). Apart from dose-dependent hypotension (p < 0.001), no clinically relevant adverse reactions were observed. CONCLUSIONS There were no statistically significant effects of the treatment. Despite the width of the confidence intervals, the odds ratios may suggest but do not prove a clinically relevant effect of the safe study medication on the preservation of cochlear nerve function after VS surgery. Further study is needed before prophylactic nimodipine can be recommended in VS surgery.
EVALuna2:22832

Prospective intraindividual comparison of gadoterate and gadobutrol for cervical and intracranial contrast-enhanced magnetic resonance angiography - Lang, Stefan; Weibart, Marina; Schmidt, Manuel; Knott, Michael; Engelhorn, Tobias; Essig, Marco; Kloska, Stephan; Dörfler, Arnd; Hölter, Philip (Neuroradiology, 2017)
PURPOSE: Gadobutrol (GB) is reported to provide improved relaxivity and concentration compared to gadoterate (GT). This study was designed to intraindividually compare quantitative and qualitative enhancement characteristics of GB to GT in cervicocranial magnetic resonance angiography (MRA) of patients with cerebrovascular disease (CVD). METHODS: Patients (n = 54) with CVD underwent two identical contrast-enhanced magnetic resonance angiography (CE-MRA) examinations of the cervical and intracranial vasculature in randomized order, using GB and GT in equimolar dose. Signal-to-noise ratios (SNR) and contrast-to-noise ratios (CNR) were obtained by two independent neuroradiologists, blinded to the applied contrast agents. Qualitative assessment was performed using a three-point scale with a focus on M1/M2 segments. RESULTS: One thousand and twenty-six vessel segments were analyzed. GB revealed a significantly higher SNR (p = 0.032) and CNR (p = 0.031) in all vessel segments. GB featured a significantly higher SNR and CNR in thoracic (p = 0.022; p = 0.016) and cervical vessels (p = 0.03; p = 0.038), as well as in the posterior circulation (p = 0.012; p = 0.005). In blinded qualitative assessment, overall preference was given to GB (p = 0.02), showing a significant better delineation of the M1/M2 segments (p = 0.041). CONCLUSION: Compared to GT, the use of GB results in a significantly higher SNR and CNR in cervical and cerebral CE-MRA, leading to a better delineation of the intracranial vasculature. Present results underline the potential of GB for improved CE-MRA assessment of vasculature in CVD patients.
EVALuna2:33134

Pupillometry in the follow-up of patients undergoing EVT - prediction of space-occupying hemispheric infarction - Kossel, Clara-Sophie; Kobus, Franca; Borutta, Matthias; Kärtner, Maximilian; Kuramatsu, Joji; Engelhorn, Tobias; Schwab, Stefan; Köhn, Julia (Journal of Neurology, 2023)
Background: Despite benefits of endovascular treatment (EVT) for large vessel occlusion (LVO) ischemic stroke, space-occupying brain edema (BE) represents a detrimental complication. In critical-care settings, CT-imaging is needed for monitoring these patients. Yet, bed-side techniques with the potential to predict whether patients develop BE or not would facilitate a time- and cost-efficient patient care. We assessed clinical significance of automated pupillometry in the follow-up of patients undergoing EVT. Methods: From 10/2018 to 10/2021, neurocritical-care-unit patients were retrospectively enrolled after EVT of anterior circulation LVO. We monitored parameters of pupillary reactivity [light-reflex-latency (Lat), constriction- and redilation-velocities (CV, DV), percentage-change-of-apertures (per-change); NeurOptics-pupilometer®] up to every hour on day 1–3 of ICU stay. BE was defined as midline shift ≥ 5 mm on follow-up imaging 3–5 days after EVT. We calculated mean values of intra-individual differences between successive pairs of parameters (mean-deltas), determined best discriminative cut-off values for BE development (ROC-analyses), and evaluated prognostic performance of pupillometry for BE development (sensitivity/specificity/positive-/negative-predictive-values). Results: 3241 pupillary assessments of 122 patients [67 women, 73 years (61.0–85.0)] were included. 13/122 patients developed BE. Patients with BE had significantly lower CVs, DVs, and smaller per-changes than patients without BE. On day 1 after EVT mean-deltas of CV, DV, and per-changes were significantly lower in patients with than without BE. Positive-predictive-values of calculated thresholds to discriminate both groups were considerably low, yet, we found high negative-predictive-values for CV, DV, per-changes, and mean-deltas (max.: 98.4%). Conclusion: Our data suggest associations between noninvasively detected changes in pupillary reactivity and BE early after LVO-EVT. Pupillometry may identify patients who are unlikely to develop BE and may not need repetitive follow-up-imaging or rescue-therapy.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Automated pupillometry; Endovascular treatment; Ischemic stroke; Large vessel occlusion; Pupillary reactivity

Quantitative Corticospinal Tract Assessment in Acute Intracerebral Hemorrhage - Volbers, Bastian; Mennecke, Angelika; Kästle, Nicola; Huttner, Hagen; Schwab, Stefan; Schmidt, Manuel; Engelhorn, Tobias Martin; Dörfler, Arnd (Translational Stroke Research, 2020)
Intracerebral hemorrhage (ICH) prognostication during the acute phase is often subjective among physicians and often affects treatment decisions. The present study explores objective imaging parameters using quantitative corticospinal tract (CST) fiber reconstruction during the acute phase of ICH and correlates these parameters with functional outcome and patient recovery. We prospectively enrolled nonsurgical spontaneous supratentorial ICH patients and obtained an MRI scan on day 5 ± 1. Q-space diffeomorphic reconstruction was performed using DSI Studio, and quantitative anisotropy (QA) was calculated. The CST was reconstructed based on QA. The dichotomized modified Rankin Scale score on day 90 (favorable outcome = 0–2) and Barthel Index (favorable recovery = 100 on day 90 or improvement between discharge and day 90 > 60%) were assessed. Thirty-three patients, median age 72 years (interquartile range (IQR) 64–83), 21 female (64%), 21 (64%) with lobar hemorrhage, median ICH volume on admission 15.0 (IQR 7.0–27.4) mL, were included. Sixteen patients (48%) had a favorable outcome and 24 (73%) had a favorable recovery. The mean number of ipsilesional reconstructed CST fiber pathways was higher in patients with favorable outcomes (153 (standard deviation (SD) 103) vs. 60 (SD 39), p = 0.003) and predicted outcome after adjustment (Exp(B) = 1.016 (95% CI = 1.002–1.030)). QA in the ipsilesional posterior limb of the internal capsule showed a trend towards an association with favorable outcome (Exp(B) = 1.194 (95% CI = 0.991–1.439 (adjusted))). The total (ipsilesional + contralesional) number of reconstructed fiber pathways was associated with favorable recovery (Exp(B) = 1.025 (95% CI = 1.003–1.047 (adjusted))). Quantitative tractography parameters assessed in the acute phase of ICH may represent a promising predictor of long-term outcome and recovery. This might facilitate prognostic evaluation and organization of rehabilitation.
CRIS-Team Scopus Importer:2020-10-02
Keywords: All rehabilitation; DWI; Intracerebral hemorrhage; MRI; Outcome research

Quiet diffusion-weighted head scanning: Initial clinical evaluation in ischemic stroke patients at 1.5T - Rösch, Julie; Ott, Martin; Heismann, Bjoern; Dörfler, Arnd; Engelhorn, Tobias; Sembritzki, Klaus; Grodzki, David M. (Journal of Magnetic Resonance Imaging, 2016)
PURPOSE: To compare the quality and diagnostic value of routine single-shot, echo-planar imaging, diffusion-weighted imaging (ss-EPI-DWI) to those of quiet readout segmented EPI-DWI (q-DWI) in magnetic resonance imaging (MRI) of acute stroke. MATERIALS AND METHODS: Twenty-six patients with acute stroke underwent a 1.5T MRI including diffusion-weighted ss-EPI and q-DWI. The two sequences were protocolled to have identical spatial resolution and spatial coverage. q-DWI was tested with (regular q-DWI) and without (fast q-DWI) averaging in 13 patients each. The acoustic noise generated by each sequence was measured. Quantitative and qualitative assessments regarding signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR), lesion conspicuity, level of artifacts, overall image quality as well as diagnostic content were performed. RESULTS: SNR and CNR values of the q-DWI scans were considerably higher than those of ss-EPI DWI (P ≤ 0.0078). No statistical difference was found for lesion conspicuity (P ≥ 0.125). Statistical differences were found for level of artifacts (P ≥ 0.0078) and overall image quality (P ≥ 0.002). Both were evaluated better in the ss-EPI DWI than in the regular and fast q-DWI. Apart from one fast q-DWI patient, radiologists voted the images to have the same diagnostic content, with upper 90% confidence limits of 0.238 for regular q-DWI and 0.429 for fast q-DWI. CONCLUSION: If the acoustic burden is critical to the patient, q-DWI is an equivalent quiet alternative to ss-EPI DWI for use in stroke patients. J. Magn. Reson. Imaging 2016;44:1238-1243.
EVALuna2:33143

Radiologische Diagnostik zerebraler Metastasen - Engelhorn, Tobias; et al. (Onkologe, 2014)
Background. Imaging plays a key role in the diagnosis of central nervous system (CNS) metastases. Objective. In this review the role of magnetic resonance imaging (MRI) and computed tomography (CT) in the work-up of cerebral metastases is presented. In addition to characteristic imaging findings technical aspects for improved detection of CNS metastases and differential diagnoses are shown. Material and methods. This review is based on own experience and relevant recent publications. Results. In the diagnosis of CNS metastases contrast-enhanced MRI is the radiological method of choice. The sensitivity can be further increased by increasing contrast medium dose as well as the use of various magnetization transfer techniques. Functional MRI techniques, such as magnetic resonance spectroscopy, perfusion and diffusion-weighted imaging, diffusion tensor imaging and dynamic contrast-enhanced imaging can further improve the differential diagnosis and detection of recurrent disease. If CT is used for diagnostics of cerebral metastases it should be performed with increased contrast combined with a scan delay. Conclusions. Contrast-enhanced MRI ideally using a multimodal protocol is the most sensitive method for the detection of CNS metastases and should therefore be preferred to CT. © 2013 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Brain; Computed tomography; Contrast medium; Magnetic resonance imaging; Metastasis

Reactivation of HCMV during RT of the brain results in critical illness and early mortality - Frey, Benjamin; Goerig, Nicole; Becker, Ina; Donaubauer, Anna-Jasmina; Korn, Klaus; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Putz, Florian; Semrau, Sabine; et al. (RADIOTHERAPY AND ONCOLOGY, 2020)
CRIS-Team WoS Importer:2021-06-18

Real world application of ocrelizumab in multiple sclerosis: Single-center experience of 128 patients - Prockl, Victoria; Nickel, Franziska; Utz, Kathrin S.; Fröhlich, Kilian; Engelhorn, Tobias; Hilz, Max-Josef; Lee, De-Hyung; Linker, Ralf; Huhn, Konstantin (Journal of the Neurological Sciences, 2020)
Background: Pivotal trials showed good clinical efficiency of the monoclonal antibody ocrelizumab while being well tolerated and manageable in multiple sclerosis (MS). However, data on adverse events in everyday practice are scarce. Hence, our study aims at investigating short-term tolerability of ocrelizumab in a “real-world” setting. Methods: In this retrospective cohort study, data of 128 (86 relapsing-remitting, 42 progressive) MS patients at initiation of ocrelizumab were analyzed at the MS center of the University of Erlangen, Germany. Additionally, follow-up data of 68 patients at 6-months retreatment were analyzed. Structured phone interviews were applied after ocrelizumab initiation to report undocumented side effects. Results: Patients predominantly switched from monoclonal antibodies (46%), orals (20%), injectables (10%), steroids or immunosuppressants (each 8%), with a mean interval of 9.0 months after the last application of the previous immunotherapy. Applying a combined premedication with steroids, antihistamines and antipyretics for >90% of patients, ocrelizumab treatment was well tolerated and mainly comprised mild (n = 59/128 at initiation, n = 5/68 at 6 months retreatment) and rarely moderate (n = 7/128 at initiation, n = 2/68 at 6 months) side effects. Predominantly mild infusion related reactions (IRR) were reported with a declining percentage over the follow-up applications. Infections occurred rarely. No severe side effects were observed. Secondary, treatment appeared efficient when looking at clinical surrogates of stable disease. Discussion: Our study delineates good short-term tolerability of ocrelizumab in a miscellaneous “real-world” MS cohort. Additional studies are warranted to confirm these beneficial findings and to reveal safety concerns in the longer-term follow-up.
CRIS-Team Scopus Importer:2020-06-26
Keywords: B-cell depletion; CD 20; Immunomodulatory treatment; Monoclonal antibody; Multiple sclerosis; Ocrelizumab; Side effects

Reduction of cerebral infarct size by dronedarone - Engelhorn, Tobias; Schwarz, Marc A.; Heusch, Gerd; Dörfler, Arnd; Schulz, Rainer (Cardiovascular Drugs and Therapy, 2011)
In the ATHENA trial, dronedarone reduced the incidence of stroke in patients with atrial fibrillation. Since smaller cerebral infarcts are sometimes asymptomatic, the reduced incidence of stroke might reflect reduction of infarct size (IS) by dronedarone. However, no data on this effect of dronedarone are available.In 60 rats, the middle cerebral artery was occluded (MCAO) for 1 h followed by reperfusion. IS was assessed at day 7. Animals were examined using a neurological 5 points score. Twelve animals served as controls (group A), 12 animals received 30 mg/kg (group B) and 100 mg/kg (group C) dronedarone daily starting 3 days before MCAO; 12 animals received 30 mg/kg (group D) starting 2 h after MCAO. In all groups treatment was maintained until day 7. In 12 additional animals (6 controls, 6 pretreated animals) fractional anisotropy (FA) was assessed using magnetic resonance imaging (MRI).IS in group A was 151 ± 45 mm(3) versus 94 ± 42 mm(3) in group B, 79 ± 29 mm(3) in group C, and 127 ± 51 mm(3) in group D, respectively (B,C,D P < 0.05 vs. A). Neuroscores and weight loss (expressed as percent of initial weight) were less in treatment groups: 1.8 ± 0.6 and 91% in group B, 1.4 ± 0.5 and 93% in group C, and 2.1 ± 0.6 and 89% in group D compared to 2.4 ± 0.5 and 83% in controls (B,C,D P < 0.05 vs. A). FA in the ischemic penumbra was significantly higher in treated than in control animals (0.44 ± 0.2 vs. 0.35 ± 0.17; P < 0.05).Dronedarone administered before and after MCAO reduces IS and improves FA and neurological outcome in transient cerebral ischemia.
EVALuna2:22954

Retinal microangiopathy in arterial hypertension as an early marker of a cerebral macroangiopathy - Michelson, Georg; Engelhorn, Tobias; Dörfler, Arnd (Deutsche Medizinische Wochenschrift, 2011)
A 54-year-old man reported having had nonspecific attacks of dizziness. His BMI was 27.7. Since 11 years he had been treated for arterial hypertension and had received oral medication for type 2 diabetes for one year. The latest blood pressure value was 134/109 mm Hg during treatment with a combination of atenolol, chlortalidone und hydralazine-HCl; furthermore hr received simvastatin, metformin, glimepirid und ramipril. A standardized telemedical imaging of the retina ("talkingeyes (®) ") was undertaken, revealing focal and generalized arteriolar narrowing of the retinal vessels and a retinal microinfarction (cotton wool spot) in the right eye. The arterial/venous ratio was decreased to 0.74 in the right and 0.77 in the left eye.Optical coherence tomographie (OCT) revealed an ischemic microinfarction of the retina with marked axonal swelling. The digital subtraction angiography of the cerebral vessels revealed a 40 % stenosis of the right internal carotid artery and a proximal, highgrade stenosis of the basilary artery.Angioplasty with stent insertion of the basilary artery was performed. Long-term observation showed no restenosis and a reduction in the size of the the retinal microinfarct.Retinal microinfarctions denote localized retinal areas of hypoxia and underperfusion. They may act as markers of a generalized micro- and macroangiopathy. Patients with severe retinal microangiopathic changes should be examined thoroughly to detect early macroangiopathic changes. These can be treated by interventional procedures thus avoiding irreversible end-organ damages.
EVALuna2:21059

Rheumatoid vasculitis of the central nervous system - Lee, D. H.; Blinzler, C.; Stöckl, Thomas; Engelhorn, Tobias; Buslei, R.; Schwab, Sibylle; Linker, Ralf (Der Nervenarzt, 2015)
EVALuna2:7259

Simplified Edinburgh CT Criteria for Identification of Lobar Intracerebral Hemorrhage Associated With Cerebral Amyloid Angiopathy - Sembill, Jochen; Knott, Michael; Xu, Mingming; Röder, Sebastian; Hagen, Manuel; Sprügel, Maximilian; Mrochen, Anne; Borutta, Matthias; Hölter, Philip; Engelhorn, Tobias Martin; Rothhammer, Veit; Macha, Kosmas; et al. (Neurology, 2022)
BACKGROUND AND OBJECTIVES: In patients with lobar intracerebral hemorrhage (ICH), etiologic characterization represents a tradeoff between feasibility, resource allocation, and diagnostic certainty. This study investigated the accuracy and clinical utility of the simplified Edinburgh CT criteria to identify underlying cerebral amyloid angiopathy (CAA). METHODS: This external validation analyzed 210 consecutive patients with lobar ICH and available CT and MRI studies from a prospective single-center observational cohort study (2006-2015, Longitudinal Cohort Study on ICH Care [UKER-ICH,] NCT03183167). We investigated the interrater variability and diagnostic accuracy of the simplified Edinburgh CT-based criteria for identification of ICH associated with probable CAA according to MRI-based modified Boston criteria as a reference standard. We evaluated the utility of the simplified Edinburgh criteria by decision curve analysis, comparing the theoretical clinical net benefit (weighted benefit-harm at varying threshold probabilities) of the high-risk category (finger-like projections and subarachnoid hemorrhage) for ruling in and the low-risk category (neither finger-like projections nor subarachnoid hemorrhage) for ruling out with the assumptions of no or all patients having CAA (default strategies). RESULTS: Of 210 patients, 70 (33.3%) had high risk, 67 (31.9%) had medium risk, and 73 (34.8%) had low risk for CAA-associated ICH according to simplified Edinburgh CT criteria, showing moderate interrater variability. Discrimination was good (area under the receiver operating characteristics curve 0.74, 95% CI 0.67-0.81) without evidence of poor calibration (Hosmer-Lemeshow, p = 0.54) for validation of MRI-based diagnosis of probable CAA (n = 94 of 210, 44.8%). The rule-in criteria (high risk), had 87.1% (79.3%-92.3%) specificity, and the rule-out criteria (low risk), had 80.9% (71.1%-88.0%) sensitivity. Decision curve analysis suggested a theoretical clinical net benefit for ruling in but not for ruling out probable CAA compared to default strategies. DISCUSSION: Applying the simplified Edinburgh CT criteria during diagnostic workup seems clinically useful and may accurately identify CAA in patients with lobar ICH. TRIAL REGISTRATION INFORMATION: ClinicalTrials.gov Identifier: NCT03183167. CLASSIFICATION OF EVIDENCE: This study provides Class II evidence that in patients with lobar hemorrhages, the simplified Edinburgh criteria accurately identify those at high risk of CAA.
CRIS-Team Scopus Importer:2022-06-03

Siponimod (BAF-312) Attenuates Perihemorrhagic Edema And Improves Survival in Experimental Intracerebral Hemorrhage - Bobinger, Tobias; Manaenko, Anatol; Burkardt, Petra; Beuscher, Vanessa; Sprügel, Maximilian; Röder, Sebastian; Bäuerle, Tobias; Seyler, Lisa; Nagel, Armin Michael; Linker, Ralf; Engelhorn, Tobias; Dörfler, Arnd; et al. (Stroke, 2019)
Background and Purpose- Perihemorrhagic edema (PHE) is associated with poor outcome after intracerebral hemorrhage (ICH). Infiltration of immune cells is considered a major contributor of PHE. Recent studies suggest that immunomodulation via S1PR (sphingosine-1-phosphate receptor) modulators improve outcome in ICH. Siponimod, a selective modulator of sphingosine 1-phosphate receptors type 1 and type 5, demonstrated an excellent safety profile in a large study of patients with multiple sclerosis. Here, we investigated the impact of siponimod treatment on perihemorrhagic edema, neurological deficits, and survival in a mouse model of ICH. Methods- ICH was induced by intracranial injection of 0.075 U of bacterial collagenase in 123 mice. Mice were randomly assigned to different treatment groups: vehicle, siponimod given as a single dosage 30 minutes after the operation or given 3× for 3 consecutive days starting 30 minutes after operation. The primary outcome of our study was evolution of PHE measured by magnetic resonance-imaging on T2-maps 72 hours after ICH, secondary outcomes included evolution of PHE 24 hours after ICH, survival and neurological deficits, as well as effects on circulating blood cells and body weight. Results- Siponimod significantly reduced PHE measured by magnetic resonance imaging (P=0.021) as well as wet-dry method (P=0.04) 72 hours after ICH. Evaluation of PHE 24 hours after ICH showed a tendency toward attenuated brain edema in the low-dosage group (P=0.08). Multiple treatments with siponimod significantly improved neurological deficits measured by Garcia Score (P=0.03). Survival at day 10 was improved in mice treated with multiple dosages of siponimod (P=0.037). Mice treated with siponimod showed a reduced weight loss after ICH (P=0.036). Conclusions- Siponimod (BAF-312) attenuated PHE after ICH, increased survival, and reduced ICH-induced sensorimotor deficits in our experimental ICH-model. Findings encourage further investigation of inflammatory modulators as well as the translation of BAF-312 to a human study of ICH patients.
EVALuna2:204480

Siponimod reduces perihemorrhagic edema and improves neurological outcome in experimental intracerebral hemorrhage - Bobinger, Tobias; Manaenko, A.; Baeurele, T.; Seyler, L.; Nagel, Armin Michael; Engelhorn, Tobias; Dörfler, Arnd; Kuramatsu, J. B.; Schwab, Stefan; Huttner, Hagen (JOURNAL OF CEREBRAL BLOOD FLOW AND METABOLISM, 2019)
CRIS-Team WoS Importer:2019-07-19

Site and size of multiple sclerosis lesions predict enhanced or decreased female orgasmic function - Winder, Klemens; Seifert, Frank; Koehn, Julia; Deutsch, Martina; Engelhorn, Tobias; Dörfler, Arnd; Lee, De-Hyung; Linker, Ralf; Hilz, Max-Josef (Journal of Neurology, 2015)
Neuroimaging identified brain areas involved in female orgasm. In women with multiple sclerosis (MS), associations between orgasmic function and the site and size of MS-related magnetic resonance imaging (MRI) changes are undetermined. This study intended to correlate MS-associated cerebral lesion load and location with clinical scores of female orgasmic function. In 50 women with MS (mean age 37.0 ± 9.9 years), we assessed Female Sexual Function Index (FSFI) scores for orgasmic frequency, difficulty and satisfaction. We determined disease duration, Expanded Disability Status Scale (EDSS) scores, and cerebral MS-lesion load and location using T2-weighed 1.5 T MRIs. We correlated FSFI scores for orgasm with patient age, disease duration, EDSS scores, and cerebral MS-lesion load (Spearman rank correlation; significance: p < 0.05). FSFI scores for orgasm correlated inversely with MS-lesion load in the left temporal periventricular white matter and right middle-inferior occipital area, but directly with MS-lesion load in the right frontal primary motor cortex, left prefrontal/inferior frontal cortex, right amygdala, left temporal middle-inferior and fusiform areas, and midbrain. FSFI scores for orgasm did not correlate with patient age, disease duration and EDSS scores (p > 0.05). In conclusion, our results indicate that MS-lesions in left temporal periventricular and right visual association areas deteriorate orgasmic function. In contrast, direct correlations between frontotemporal or midbrain lesions and higher FSFI scores, indicating enhanced or disinhibited orgasmic function, suggest that these brain regions normally buffer orgasmic responses. Moreover, our results indicate that orgasmic dysfunction in women with MS evolves independently of disease duration and physical disability.
EVALuna2:22361

Specific cerebral multiple sclerosis lesions are associated with sympathetic cardiovascular activation - Winder, K.; Linker, R. A.; Seifert, F.; Wang, R.; Lee, D-H.; Engelhorn, Tobias; Dörfler, Arnd; Fröhlich, Katharina; Hilz, M. J. (EUROPEAN JOURNAL OF NEUROLOGY, 2019)
CRIS-Team WoS Importer:2019-07-30

Standardized acquisition and post-processing of dynamic susceptibility contrast perfusion in patients with brain tumors, cerebrovascular disease and dementia: comparability of post-processing software - Schmidt, Manuel; Knott, Michael; Engelhorn, Tobias; Larsson, Elna Marie; Nguyen, Than; Essig, Marco; Dörfler, Arnd; Hölter, Philip (British Journal of Radiology, 2020)
OBJECTIVE: MR-perfusion post-processing still lacks standardization. This study evaluates the results of perfusion analysis with two established software solutions in a large series of patients with different diseases when a highly standardized processing workflow is ensured. METHODS: Multicenter data of 260 patients (80 with brain tumors, 124 with cerebrovascular disease and 56 with dementia examined with the same MR protocol) were analyzed. Raw data sets were processed with two software suites: Olea sphere and NordicICE. Group differences were analyzed with paired t-tests and one-way ANOVA. RESULTS: Perfusion metrics were significantly different for all examined diseases in the unaffected brain for both software suites [ratio cortex/white matter left hemisphere: mean transit time (MTT) 0.991 vs 0.847, p < 0.05; relative cerebral bloodflow (rBF) 3.23 vs 4.418, p < 0.001; relative cerebral bloodvolume (rBVc) 2.813 vs 3.884, p < 0.001; right hemisphere: MTT 1.079 vs 0.854, p < 0.05; rBF 3.262 vs 4.378, p < 0.001; rBVc 2.762 vs 3.935, p < 0.001)]. Perfusion results were also significantly different in patients with stroke (ratio cortex/white matter affected hemisphere: MTT 1.058 vs 0.784; p < 0.001), dementia (ratio cortex/white matter left hemisphere: rBVc 1.152 vs 1.795, p < 0.001; right hemisphere: rBVc 1.396 vs 1.662, p < 0.05) and brain tumors (ratio cortex/whole tumor rBVc: 0.778 vs 0.919, p < 0.001 and ratio cortex/tumor hotspot rBVc: 0.529 vs 0.512, p < 0.05). CONCLUSION: Despite a highly standardized workflow, parametric perfusion maps are depended on the chosen software. Radiologists should consider software related variances when using dynamic susceptibility contrast perfusion for clinical imaging and research. ADVANCES IN KNOWLEDGE: This multicenter study compared perfusion parameters calculated by two commercial dynamic susceptibility contrast perfusion post-processing software solutions in different central nervous system disorders with a large sample size and a highly standardized processing workflow. Despite, parametric perfusion maps are depended on the chosen software which impacts clinical imaging and research.
CRIS-Team Scopus Importer:2019-12-24

Stent-Assisted Coiling Using Leo+ Baby Stent: Immediate and Mid-Term Results - Lücking, Hannes; Struffert, Tobias; Gölitz, Philipp; Engelhorn, Tobias; Brandner, Sebastian; Kuramatsu, Joji; Lang, Stefan; Schmidt, Manuel; Dörfler, Arnd (Clinical Neuroradiology, 2020)
Background: Stent-assisted coiling is well-established for treatment of cerebral aneurysms. The technique enables treatment of wide-neck, bifurcation and recurrent aneurysms with high packing rates. While described in extenso for laser cut stents, the results of patients treated with the Leo+ Baby (Balt, Montmorency, France) braided microstent are presented. Material and Methods: Patients were included if treated with a Leo+ Baby and with digital subtraction angiography (DSA) follow-up available of at least 6 months. Data were evaluated for successful deployment, aneurysm occlusion according to the modified Raymond-Roy classification (MRRC), stent patency and procedure-related morbidity and mortality. Results: A total of 81 patients were included and Leo+ Baby deployment was successful in all cases. Coils were used in 80 cases. In 1 case 2 stents were used stent-in-stent without additional coiling. Initial aneurysm occlusion rates were MRRCi1 51.9%, MRRCi2 11.1%, MRRCi3a 24.7% and MRRCi3b 12.3%. Occlusion rates after 6 months were MRRC6m1 78.9%, MRRC6m2 3.9%, MRRC6m3a 6.6% and MRRC6m3b 10.5%. Procedure-related morbidity was 1 case of acute stent thrombosis successfully treated with tirofiban and 1 case with transient hemiparesis due to stent thrombosis after 4 months. There was 1 case of coil-associated subarachnoid hemorrhage (SAH) which caused prolonged hospitalization. No procedure-related mortality was observed. Conclusion: The results confirm that stent-assisted coiling with the Leo+ Baby stent is safe and efficient for treatment of wide neck or recurrent cerebral aneurysms. Spontaneous progressive aneurysm occlusion over 6 months supports the theory of considerable flow-modulating effects of Leo+ Baby.
CRIS-Team Scopus Importer:2020-05-15
Keywords: Bifurcation aneurysm; Braided stent; Cerebral aneurysm; Coiling; Low profile stent

Study on the Impact of CMV-Encephalopathy on the Survival of Brain Cancer Patients Undergoing Radio(Chemo) therapy of the Brain - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, M. A.; Engelhorn, Tobias; Dörfler, Arnd; Eyüpoglu, Ilker Yasin; Merkel, Andreas; Rühle, Paul-Friedrich; Putz, F.; et al. (2017)
EVALuna2:32868

Sulfasalazine impacts on ferroptotic cell death and alleviates the tumor microenvironment and glioma-induced brain edema. - Sehm, Tina; Fan, Zheng; Ghoochani, Ali; Rauh, Manfred; Engelhorn, Tobias; Minakaki, Georgia; Dörfler, Arnd; Klucken, Jochen; Buchfelder, Michael; Eyüpoglu, Ilker Yasin; Savaskan, Nicolai (Oncotarget, 2016)
The glutamate transporter xCT (SCL7a11, system Xc-, SXC) is an emerging key player in glutamate/cysteine/glutathione homeostasis in the brain and in cancer. xCT expression correlates with the grade of malignancy. Here, we report on the use of the U.S. Food and Drug Administration and EMA-approved xCT inhibitor, sulfasalazine (SAS) in gliomas. SAS does not affect cell viability in gliomas at concentrations below 200 µM. At higher concentrations SAS becomes gliomatoxic. Mechanistically SAS inhibits xCT and induces ferroptotic cell death in glioma cells. There is no evidence for impact on autophagic flux following SAS application. However, SAS can potentiate the efficacy of the standard chemotherapeutic and autophagy-inducing agent temozolomide (Temcat, Temodal or Temodar®). We also investigated SAS in non-transformed cellular constituents of the brain. Neurons and brain tissue are almost non-responding to SAS whereas isolated astrocytes are less sensitive towards SAS toxicity compared to gliomas. In vivo SAS treatment does not affect experimental tumor growth and treated animals revealed comparable tumor volume as untreated controls. However, SAS treatment resulted in reduced glioma-derived edema and, hence, total tumor volume burden as revealed by T2-weighted magnetic resonance imaging. Altogether, we show that SAS can be utilized for targeting the glutamate antiporter xCT activity as a tumor microenvironment-normalizing drug, while crucial cytotoxic effects in brain tumors are minor.

Supratentorial lesions contribute to trigeminal neuralgia in multiple sclerosis - Fröhlich, Katharina; Winder, Klemens; Linker, Ralf; Engelhorn, Tobias; Dörfler, Arnd; Lee, De-Hyung; Hilz, Max-Josef; Schwab, Stefan; Seifert, Frank (Cephalalgia, 2018)
Background It has been proposed that multiple sclerosis lesions afflicting the pontine trigeminal afferents contribute to trigeminal neuralgia in multiple sclerosis. So far, there are no imaging studies that have evaluated interactions between supratentorial lesions and trigeminal neuralgia in multiple sclerosis patients. Methods We conducted a retrospective study and sought multiple sclerosis patients with trigeminal neuralgia and controls in a local database. Multiple sclerosis lesions were manually outlined and transformed into stereotaxic space. We determined the lesion overlap and performed a voxel-wise subtraction analysis. Secondly, we conducted a voxel-wise non-parametric analysis using the Liebermeister test. Results From 12,210 multiple sclerosis patient records screened, we identified 41 patients with trigeminal neuralgia. The voxel-wise subtraction analysis yielded associations between trigeminal neuralgia and multiple sclerosis lesions in the pontine trigeminal afferents, as well as larger supratentorial lesion clusters in the contralateral insula and hippocampus. The non-parametric statistical analysis using the Liebermeister test yielded similar areas to be associated with multiple sclerosis-related trigeminal neuralgia. Conclusions Our study confirms previous data on associations between multiple sclerosis-related trigeminal neuralgia and pontine lesions, and showed for the first time an association with lesions in the insular region, a region involved in pain processing and endogenous pain modulation.
EVALuna2:34503

T2-sequence with contrast inversion: diagnostic value in the investigation of gray matter heterotopias - Rösch, Julie; Mennecke, Angelika; Knott, Michael; Hamer, Hajo; Dörfler, Arnd; Engelhorn, Tobias Martin (NeuroReport, 2020)
To compare the diagnostic value of T1-inversion recovery sequence (T1 IR) to that of a T2-sequence with contrast inversion (T2 CI) in the investigation of heterotopias. In this study, we processed a contrast-inverted copy of our coronal T2-sequence of 21 patients with subependymal and subcortical heterotopias on an online picture archiving and communication system workstation. The diagnostic performance of these images was compared with the T1 IR of the same patients by quantitative and qualitative assessments regarding signal-to-noise ratio (SNR), lesion-to-white matter contrast-to-noise ratio (CNR), lesion conspicuity, level of artifacts, overall image quality as well as diagnostic content. SNR values of the T2 CI were significantly higher than those of the T1 IR. CNR values of both sequences were similar. No relevant difference was found for lesion conspicuity and level of artifacts. Overall image quality of the T2 CI was rated slightly better by one reader. Both readers voted the images to have the same diagnostic content. Beside the exact depiction of the hippocampus in the high resoluted T2-sequence, its contrast-inverted copy (T2 CI) is also useful in the detection of heterotopias. In conjunction with the MPRAGE or MP2RAGE as a three-dimensional sequence, it could offer an equivalent and time-saving alternative to the T1 IR in the investigation of this type of malformation of cortical development.
CRIS-Team Scopus Importer:2020-05-29

Technical feasibility of 2D-3D coregistration for visualization of self-expandable microstents to facilitate coil embolization of broad-based intracranial aneurysms: An in vitro study - Richter, Gregor; Pfister, Marcus; Struffert, Tobias; Engelhorn, Tobias; Dölken, Marc; Spiegel, Martin; Hornegger, Joachim; Dörfler, Arnd (Neuroradiology, 2009)
Introduction: The use of self-expandable microstents for treatment of broad-based intracranial aneurysms is widely spread. However, poor fluoroscopic visibility of the stents remains disadvantageous during the coiling procedure. Flat detector angiographic computed tomography (ACT) provides high resolution imaging of microstents even though integration of this imaging modality in the neurointerventional workflow has not been widely reported. Methods: An acrylic glass model was used to simulate the situation of a broad-based sidewall aneurysm. After insertion of a self-expandable microstent, ACT was performed. The resulting 3D dataset of the Microstent was subsequently projected into a conventional 2D fluoroscopic roadmap. This 3D visualization of the stent supported the coil embolization procedure of the in vitro aneurysm. Results: In vitro 2D-3D coregistration with integration of 3D ACT data of a self-expandable microstent in a conventional 2D roadmap is feasible. Conclusions: Unsatisfying stent visibility constrains clinical cases with complex parent vessel anatomy and challenging aneurysm geometry; hence, this technique potentially may be useful in such cases. In our opinion, the clinical feasibility and utility of this new technique should be verified in a clinical aneurysm embolization study series using 2D-3D coregistration. © 2009 Springer-Verlag.

The anesthetic approach for endovascular recanalization therapy depends on the lesion site in acute ischemic stroke - Fröhlich, Kilian; Siedler, Gabriela; Stoll, Svenja; Macha, Kosmas; Kinfe, Thomas Mehari; Dörfler, Arnd; Eisenhut, Felix; Engelhorn, Tobias; Hölter, Philip; Lang, Stefan; Mühlen, Iris; Schmidt, Manuel; et al. (Neuroradiology, 2021)
Purpose Endovascular therapy (EVT) of large-vessel occlusion in acute ischemic stroke (AIS) may be performed in general anesthesia (GA) or conscious sedation (CS). We intended to determine the contribution of ischemic cerebral lesion sites on the physician's decision between GA and CS using voxel-based lesion symptom mapping (VLSM). Methods In a prospective local database, we sought patients with documented AIS and EVT. Age, stroke severity, lesion volume, vigilance, and aphasia scores were compared between EVT patients with GA and CS. The ischemic lesions were analyzed on CT or MRI scans and transformed into stereotaxic space. We determined the lesion overlap and assessed whether GA or CS is associated with specific cerebral lesion sites using the voxel-wise Liebermeister test. Results One hundred seventy-nine patients with AIS and EVT were included in the analysis. The VLSM analysis yielded associations between GA and ischemic lesions in the left hemispheric middle cerebral artery territory and posterior circulation areas. Stroke severity and lesion volume were significantly higher in the GA group. The prevalence of aphasia and aphasia severity was significantly higher and parameters of vigilance lower in the GA group. Conclusions The VLSM analysis showed associations between GA and ischemic lesions in the left hemispheric middle cerebral artery territory and posterior circulation areas including the thalamus that are known to cause neurologic deficits, such as aphasia or compromised vigilance, in AIS-patients with EVT. Our data suggest that higher disability, clinical impairment due to neurological deficits like aphasia, or reduced alertness of affected patients may influence the physician's decision on using GA in EVT.
CRIS-Team WoS Importer:2021-07-23

The FRED for Cerebral Aneurysms of the Posterior Circulation: A Subgroup Analysis of the EuFRED Registry - Griessenauer, C. J.; Möhlenbruch, M. A.; Hendrix, P.; Ulfert, C.; Islak, C.; Sonnberger, M.; Engelhorn, Tobias; Müller-Thies-Broussalis, E.; Finkenzeller, T.; Holtmannspötter, M.; Buhk, J. H.; Reith, W.; et al. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: Flow diversion for the posterior circulation remains a promising treatment option for selected posterior circulation aneurysms. The Flow-Redirection Intraluminal Device (FRED) system has not been previously assessed in a large cohort of patients with posterior circulation aneurysms. The purpose of the present study was to assess safety and efficacy of FRED in this location. MATERIALS AND METHODS: Consecutive patients with posterior circulation aneurysms treated at 8 centers participating in the European FRED study (EuFRED) between April 2012 and January 2019 were retrospectively reviewed. Complication and radiographic and functional outcomes were evaluated. RESULTS: Eighty-four patients (median age, 54 years) with 84 posterior circulation aneurysms were treated with the FRED. A total of 25 aneurysms (29.8%) had previously ruptured, even though most aneurysms were diagnosed incidentally (45.2%). The intradural vertebral artery was the most common location (50%), and saccular, the most common morphology (40.5%). The median size was 7 mm. There were 8 (9.5%) symptomatic thromboembolic and no hemorrhagic complications. Thromboembolic complications occurred mostly (90.9%) in nonsaccular aneurysms. On last follow-up at a median of 24 months, 78.2% of aneurysms were completely occluded. Functional outcome at a median of 27 months was favorable in 94% of patients. All mortalities occurred in patients with acute subarachnoid hemorrhage and its sequelae. CONCLUSIONS: The largest cohort of posterior circulation aneurysms treated with the FRED to date demonstrated favorable safety and efficacy profiles of the device for this indication. Treatment in the setting of acute subarachnoid hemorrhage was strongly related to mortality, regardless of whether procedural complications occurred.
CRIS-Team Scopus Importer:2020-04-28

The Impact of Burst Motor Cortex Stimulation on Cardiovascular Autonomic Modulation in Chronic Pain: A Feasibility Study for a New Approach to Objectively Monitor Therapeutic Effects - Borutta, Matthias; Köhn, Julia; Souza de Oliveira, Daniela; Del Vecchio, Alessandro; Engelhorn, Tobias; Schwab, Stefan; Buchfelder, Michael; Kinfe, Thomas Mehari (Pain and Therapy, 2023)
Introduction: Chronic refractory pain of various origin occurs in 30–45% of pain patients, and a considerable proportion remains resistant to pharmacological and behavioral therapies, requiring adjunctive neurostimulation therapies. Chronic pain is known to stimulate sympathetic outflow, yet the impact of burst motor cortex stimulation (burstMCS) on objectifiable autonomic cardiovascular parameters in chronic pain remains largely unknown. Methods: In three patients with chronic pain (2 facial pain/1 post-stroke pain), we compared pain intensity using a visual analog scale (VAS 1–10) and parameters of autonomic cardiovascular modulation at supine rest, during parasympathetic challenge with six cycles per minute of metronomic deep breathing, and during sympathetic challenge (active standing) at baseline and after 4 months of burstMCS compared to age-/gender-matched healthy controls. Results: While two out of three patients were responsive after 4 months of adjunctive burstMCS (defined as pain reduction of > 30%), no differences were found in any of the three patients regarding the R-R intervals of adjacent QRS complexes (RRI, 642 vs. 676 ms) and blood pressure (BP, 139/88 vs. 141/90 mmHg). Under resting conditions, parameters of parasympathetic tone [normalized units of high-frequency oscillations of RRI (RRI-HFnu power) 0.24 vs. 0.38, root-mean-square differences of successive RRI (RRI-RMSSD) 7.7 vs. 14.7 ms], total autonomic cardiac modulation [RRI total power 129.3 vs. 406.2 ms2, standard deviation of RRI (RRI-SD) 11.6 vs. 18.5 ms, coefficient of variation of RRI (RRI-CV) 1.9 vs. 3.7%], and baroreceptor reflex sensitivity (BRS, 1.9 vs. 2.3 ms/mmHg) increased, and parameters of sympathetic tone [normalized units of low-frequency oscillations of RRI (RRI-LFnu power) 0.76 vs. 0.62] and sympatho-vagal balance [ratio of RR-LF to RRI-HF power (RRI-LF/HF ratio) 3.4 vs. 1.9] decreased after 4 months of burstMCS. Low-frequency oscillations of systolic blood pressure (SBP-LF power), a parameter of sympathetic cardiovascular modulation, increased slightly (17.6 vs. 20.4 mmHg2). During parasympathetic stimulation, the expiratory–inspiratory ratio (E/I ratio) increased slightly, while upon sympathetic stimulation, the ratio between the shortest RRI around the 15th heartbeat and the longest RRI around the 30th heartbeat after standing up (RRI 30/15 ratio) remained unchanged. Conclusion: Four months of adjunctive burstMCS was associated with an increase in parameters reflecting both total and parasympathetic autonomic modulation and baroreceptor reflex sensitivity. In contrast, sympathetic tone declined in our three patients, suggesting stimulation-associated improvement not only in subjectively perceived VAS pain scores, but also in objectifiable parameters of autonomic cardiovascular modulation.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Autonomic cardiovascular modulation; Burst motor cortex stimulation; Chronic post stroke pain; Objective outcome measures

The impact of dietary isoflavonoids on malignant brain tumors - Sehm, Tina; Fan, Zheng; Weiss, Ruth; Schwarz, Marc; Engelhorn, Tobias; Hore, Nirjhar; Dörfler, Arnd; Buchfelder, Michael; Eyüpoglu, Ilker Yasin; Savaskan, Nic E. (Cancer Medicine, 2014)
Poor prognosis and limited therapeutic options render malignant brain tumors one of the most devastating diseases in clinical medicine. Current treatment strategies attempt to expand the therapeutic repertoire through the use of multimodal treatment regimens. It is here that dietary fibers have been recently recognized as a supportive natural therapy in augmenting the body's response to tumor growth. Here, we investigated the impact of isoflavonoids on primary brain tumor cells. First, we treated glioma cell lines and primary astrocytes with various isoflavonoids and phytoestrogens. Cell viability in a dose-dependent manner was measured for biochanin A (BCA), genistein (GST), and secoisolariciresinol diglucoside (SDG). Dose-response action for the different isoflavonoids showed that BCA is highly effective on glioma cells and nontoxic for normal differentiated brain tissues. We further investigated BCA in ex vivo and in vivo experimentations. Organotypic brain slice cultures were performed and treated with BCA. For in vivo experiments, BCA was intraperitoneal injected in tumor-implanted Fisher rats. Tumor size and edema were measured and quantified by magnetic resonance imaging (MRI) scans. In vascular organotypic glioma brain slice cultures (VOGIM) we found that BCA operates antiangiogenic and neuroprotective. In vivo MRI scans demonstrated that administered BCA as a monotherapy was effective in reducing significantly tumor-induced brain edema and showed a trend for prolonged survival. Our results revealed that dietary isoflavonoids, in particular BCA, execute toxicity toward glioma cells, antiangiogenic, and coevally neuroprotective properties, and therefore augment the range of state-of-the-art multimodal treatment approach.
EVALuna2:22829

Two- to five-year follow-up of 78 patients after treatment with the Flow Redirection Endoluminal Device - Lücking, Hannes; Dörfler, Arnd; Gölitz, Philipp; Engelhorn, Tobias; Lang, Stefan; Hölter, Philip (Interventional Neuroradiology, 2019)
Background and purpose Flow-diverter stents are well-established for the treatment of cerebral aneurysms. Flow Redirection Endoluminal Device differs from other flow-diverter stents by its dual-layer design and has proved equality to other devices in numerous short-term surveys. However, follow-up data covering substantially more than one year are still limited for this device. We present our long-term experience with Flow Redirection Endoluminal Device.
CRIS-Team WoS Importer:2019-10-22

Two- to five-year follow-up of 78 patients after treatment with the Flow Redirection Endoluminal Device - Lücking, Hannes; Dörfler, Arnd; Gölitz, Philipp; Hölter, Philip; Engelhorn, Tobias; Lang, Stefan (Interventional Neuroradiology, 2020)
BACKGROUND AND PURPOSE: Flow-diverter stents are well-established for the treatment of cerebral aneurysms. Flow Redirection Endoluminal Device differs from other flow-diverter stents by its dual-layer design and has proved equality to other devices in numerous short-term surveys. However, follow-up data covering substantially more than one year are still limited for this device. We present our long-term experience with Flow Redirection Endoluminal Device. MATERIALS AND METHODS: Seventy-eight patients harboring distal internal carotid artery (91%) or vertebrobasilar (9%) cerebral aneurysms treated with Flow Redirection Endoluminal Device with or without adjunctive coiling met the inclusion criteria. All cases were evaluated for aneurysm occlusion (according to Modified Raymond Roy Classification, MRRC), for flow-diverter stents patency and configuration and for procedure- and device-related morbidity and mortality. RESULTS: Mean follow-up interval was 36.9 ± 9.5 months (<30 months: n = 18; 31-42 months: n = 31; >42 months: n = 24). Total and subtotal aneurysm occlusion after six months was assessed in 92.0% (MRRC1 = 77.3%, MRRC2 = 14.7%, MRRC3a =2.7%, MRRC3b = 4.1%) and increased to 95.9% (MRRC1 = 90.5%, MRRC2 = 5.4%, MRRC3a = 2.7%). There was one case of aneurysm growth requiring early re-treatment. Procedure-related morbidity was observed in three cases (3.8%; one transient hemiparesis, one suspected foreign-body reaction, and one micro-wire perforation). There was no procedure- or device-related mortality. In-stent stenosis due to intimal hyperplasia was observed in two cases and fish-mouthing in three cases. CONCLUSIONS: Our long-term data covering two to five years after flow diversion confirm that Flow Redirection Endoluminal Device is a safe and effective device for the treatment of cerebral aneurysms with progressive high aneurysm occlusion rates; recurrence rates were very low. Overall device-related morbidity was low and was not observed later than six months after intervention.
EVALuna2:212795

Ultra high-field SWI of the substantia nigra at 7T: reliability and consistency of the swallow-tail sign - Schmidt, Manuel; Engelhorn, Tobias; Marxreiter, Franz; Winkler, Jürgen; Lang, Stefan; Kloska, Stephan; Gölitz, Philipp; Dörfler, Arnd (BMC Neurology, 2017)
BACKGROUND: The loss of the swallow-tail sign of the substantia nigra has been proposed for diagnosis of Parkinson's disease. Aim was to evaluate, if the sign occurs consistently in healthy subjects and if it can be reliably detected with high-resolution 7T susceptibility weighted imaging (SWI). METHODS: Thirteen healthy adults received SWI at 7T. 3 neuroradiologists, who were blinded to patients' diagnosis, independently classified subjects regarding the swallow-tail sign to be present or absent. Accuracy, positive and negative predictive values (PPV and NPV) as well as inter- and intra-rater reliability and internal consistency were analyzed. RESULTS: The sign could be detected in 81% of the cases in consensus reading. Accuracy to detect the sign compared to the consensus was 100, 77 and 96% for the three readers with PPV reader 1/2/3 = 1/0.45/0.83 and NPV = 1/1/1. Inter-rater reliability was excellent (inter-class correlation coefficient = 0.844, alpha = 0.871). Intra-rater reliability was good to excellent (reader 1 R/L = 0.625/0.786; reader 2 = 0.7/0.64; reader 3 = 0.9/1). CONCLUSION: The swallow-tail sign can be reliably detected. However, our data suggest its occurrence is not consistent in healthy subjects. It may be possible that one reason is an individually variable molecular organization of nigrosome 1 so that it does not return a uniform signal in SWI.
EVALuna2:33135

Vasospasm in intracerebral hemorrhage with ventricular involvement: a prospective pilot transcranial Doppler sonography study - Kiphuth, Ines C.; Huttner, Hagen; Breuer, Lorenz; Engelhorn, Tobias; Schwab, Stefan; Köhrmann, Martin (Cerebrovascular Diseases, 2011)
Cerebral vasospasm (VSP) is a common complication after subarachnoid hemorrhage (SAH), but has rarely been reported after intracerebral hemorrhage (ICH) without subarachnoidal bleeding. The underlying pathophysiological mechanism is mainly mediated by circulating heme products within the cerebrospinal fluid, and thus patients with ICH and ventricular involvement (IVH) may also be in danger of developing VSP. The incidence and role of VSP in IVH, however, have not been systematically studied.We prospectively enrolled 115 patients with ICH with or without IVH into the study between April 2009 and April 2010. All patients received serial extracranial and transcranial Doppler sonography (TCD) at baseline, on days 3-5 and 7-9 to detect and monitor VSP. In addition, CT scans taken on admission, after 24 h and before discharge were evaluated for the occurrence of delayed cerebral ischemia.Three out of 53 patients (5.7%) with IVH showed a significant elevation of flow velocities over the examined timeframe. One of these patients developed severe VSP resulting in secondary ischemic infarction. None of the ICH patients without IVH showed significantly elevated flow velocities or secondary infarction.Cerebral VSP with secondary infarction may occur in patients with spontaneous IVH, though far less frequently than in SAH; thus, systematic screening of all patients with IVH may not be warranted. However, serial TCD should be considered in patients with secondary clinical worsening or extensive IVH.
EVALuna2:21961

Visualisation of tumour regression after local chemotherapy with magnetic nanoparticles - A pilot study - Lyer, Stefan; Tietze, Rainer; Jurgons, Roland; Struffert, Tobias; Engelhorn, Tobias; Schreiber, Eveline; Dörfler, Arnd; Alexiou, Christoph (Anticancer Research, 2010)
Magnetic drug targeting (MDT) is a new locoregional chemotherapy method that increases the drug dose in the tumour region, while simultaneously reducing the overall dose through the application of chemotherapeuticbound superparamagnetic nanoparticles, which are focused by an external magnetic field to the desired body compartment. An important factor in this kind of therapy is the vascularisation of the targeted tumour. In this pilot study, the visualisation of the tumour-vascularisation before and after MDT was investigated. Materials and Methods: In a rabbit VX-2 tumour model, mitoxantrone bound to Fe3O4-nanoparticles was applied through the femoral artery close to the tumour. The visualisation of vascularisation and tumour size before and after MDT was performed using a biplane angiographic system (Siemens Axiom Artis dBA) to obtain conventional angiographic series with a standard iodine contrast agent. In addition, cross-sectional images were obtained with the new technique of flat panel detector computed tomography (FD-CT) called DYNA-CT. Results: The tumours and the supplying vessels were clearly displayed by FD-CT before and after MDT. The tumours of the study group showed considerable size reductions and the angiography showed a drastic reduction of the tumour supporting vessels following MDT. Conclusion: MDT leads to significant tumour size reductions within several weeks after a single administration of chemotherapy. In this pilot study, FD-CT offered an excellent possibility to monitor the vascularisation and the size of the tumours before and after MDT.
CRIS-Team Scopus Importer:2022-06-27
Keywords: Angiography; Computed tomography; Flat-panel CT; Local chemotherapy; Magnetic drug targeting; Tumour vascularisation

Volumetry and Surgical Grading Systems for Vestibular Schwannoma Size Assessment and their Relationship to Postoperative Facial Nerve Function - Strauß, Catharina; Rampp, Stefan; Scheller, Christian; Prell, Julian; Strauss, Christian; Dörfler, Arnd; Engelhorn, Tobias (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background and Study Aims Treatment modalities in vestibular schwannoma (VS) are difficult to compare since different techniques for size measurements are used. The purpose of this study was to evaluate the relation between different tumor size grading systems regarding their compatibility as well as the relationship to facial nerve outcome facilitating comparisons of different studies.
CRIS-Team WoS Importer:2021-06-18

Why Does It Shine?-A Prognostic Analysis about Predisposing Factors for Blood-Brain Barrier Damage after Revascularisation of Cerebral Large-Vessel Occlusion. - Knott, Michael; Hock, Stefan; Soder, Liam; Mühlen, Iris; Kremer, Svenja; Sprügel, Maximilian; Sembill, Jochen; Kuramatsu, Joji; Schwab, Stefan; Engelhorn, Tobias; Dörfler, Arnd (Journal of Cardiovascular Development and Disease, 2023)
BACKGROUND: Hyperdense lesions in CT after EVT of LVO are common. These lesions are predictors for haemorrhages and an equivalent of the final infarct. The aim of this study based on FDCT was the evaluation of predisposing factors for these lesions. METHODS: Using a local database, 474 patients with mTICI ≥ 2B after EVT were recruited retrospectively. A postinterventional FDCT after recanalisation was analysed regarding such hyperdense lesions. This was correlated with a variety of items (demographics, past medical history, stroke assessment/treatment and short-/long-term follow-up). RESULTS: Significant differences were present in NHISS at admission, regarding time window, ASPECTS in initial NECT, location of the LVO, CT-perfusion (penumbra, mismatch ratio), haemostatic parameters (INR, aPTT), duration of EVT, number of EVT attempts, TICI, affected brain region, volume of demarcation and FDCT-ASPECTS. The ICH-rate, the volume of demarcation in follow-up NECT and the mRS at 90 days differed in association with these hyperdensities. INR, the location of demarcation, the volume of demarcation and the FDCT-ASPECTS could be demonstrated as independent factors for the development of such lesions. CONCLUSION: Our results support the prognostic value of hyperdense lesions after EVT. We identified the volume of the lesion, the affection of grey matter and the plasmatic coagulation system as independent factors for the development of such lesions.
EVALuna2:536989